Molecular intersections of traumatic brain injury and Alzheimer’s disease: the role of ADMSC-derived exosomes and hub genes in microglial polarization - Pengtao Li; Liguo Ye; Sishuai Sun; Yue Wang; Yihao Chen; Jianbo Chang; Rui Yin; Xiaoyu Liu; Wei Zuo; Houshi Xu; Xiao Zhang; Robert Chunhua Zhao; et al. (Metabolic Brain Disease, 2024)

Toward crop–livestock integration: a comprehensive framework for cropping system adaptation assessment to mitigate forage shortage - Dan Liu; Jianjun Jin; Xin Qiu; Rui He; Linna Li; Jie Yang (Environment, Development and Sustainability, 2024)

Wave forces and dynamic pressures on pile-supported breakwaters with inclined perforated plates under regular waves - Ziwang Li; Rui Liu; Zhenlu Wang; Bingchen Liang; Haofeng Xia; Xuehai Sun; Xinpeng Wang; Luming Shi (Frontiers in Marine Science, 2024)
The use of pile-supported breakwaters can be a cost-effective solution for wave energy dissipation when traditional rubble mound breakwaters are not suitable. For a cost-effective design of these barriers, it is essential to obtain accurate estimates of dynamic pressures and wave forces. Laboratory experiments were conducted to investigate the dynamic pressures and forces on a novel pile-supported breakwater with inclined perforated plates. The analysis focused on various wave and structural parameters, including incident wave height, wave period, plate porosity, and plate configuration. For double-layer configurations with the same porosity, dynamic pressures on the single-layer or front plate were significantly higher than on the rear plate, with rear plate forces being 20% to 60% less. The dynamic pressure on the rear plate exhibited a uniform vertical distribution. Varying plate porosity at different locations significantly impacted structural forces. Gradually decreasing porosity improved wave dissipation and reduced forces on the plates, with front and back plate forces reaching approximately 70% of those on single-layer plates. Optimal protection across various wave periods can be achieved by adjusting porosity and plate arrangement. These findings provide valuable insights for designing pile-supported breakwaters in coastal protection engineering.

Tracing contaminants of emerging concern and their transformations in the whole treatment process of a municipal wastewater treatment plant using nontarget screening and molecular networking strategies - Zhenguo Chen; Di Xia; Huangrui Liu; Rui Wang; Mingzhi Huang; Ting Tang; Guining Lu (Water Research, 2024)

A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

Improving the affordability and reducing greenhouse gas emissions of the EAT-Lancet diet in China - Meng Li; Yanan Wang; Shunan Zhao; Wei Chen; Yu Liu; Heran Zheng; Zhongxiao Sun; Pan He; Rui Li; Sun Zhang; Peixue Xing; Qiao Li (Sustainable Production and Consumption, 2024)

Response of soil carbon and nitrogen stocks to irrigation - A global meta-analysis - Weihao Sun; Zhibin He; Dengke Ma; Bing Liu; Rui Li; Shuai Wang; Arash Malekian (Science of The Total Environment, 2024)

Spatial and temporal evolution and factors influencing soil aggregate stability in the riparian zone during exposure: A case study of the water-level fluctuation zone of the Three Gorges Reservoir, China - Yuanzhen Ni; Zhenyao Xia; Yueshu Yang; Deyu Liu; Rui Xiang; Yu Ding; Huan Hong; Di Wang; Hai Xiao (Science of The Total Environment, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Enrichment characteristics of Cd and Hg and regulation of heavy metal transporter signaling in Pleurotus ostreatus - Qing Liu; Xiukun Zheng; Rui Du; Yuqiang Shao; Qing Wen; Xiaoye Shen; Fengqin Wang; Yuancheng Qi; Jinwen Shen; Yanru Hu (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Investigation of the interactions and influencing factors of the Water-Land-Energy-Carbon system in the Yellow River Basin - Jiaxin Li; Xiaopeng Liu; Li Wei; Xinyan Li; Haiyan Gao; Rui Chen; Yifeng Cui (Science of The Total Environment, 2024)

Global patterns of lake microplastic pollution: Insights from regional human development levels - Dan Chen; Ping Wang; Shiqi Liu; Rui Wang; Yaping Wu; A-Xing Zhu; Chunnuan Deng (Science of The Total Environment, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Construction of a triple-mode sensing platform for effective differentiation, speciation, and monitoring of mercury and methylmercury bioaccumulation in crayfish via cation exchange reaction - Yiman Wu; Jie Liu; Shuqi Li; Rui Jian; Xin Yuan; Ke Huang (Science of The Total Environment, 2024)

Global distribution, drivers, and potential hazards of microplastics in groundwater: A review - Jun Xu; Rui Zuo; Guanlan Wu; Jingchao Liu; Jiawei Liu; Chenxi Huang; Zhiwen Wang (Science of The Total Environment, 2024)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

A highly-efficient peroxymonosulfate activator using a sewage sludge derived biochar supported cobalt oxide: Mechanism and characteristics - Qiyu Shi; Rui Yang; Meiyu Liu; Yizhou Feng; Zhihua Li; Weihuang Zhu (Process Safety and Environmental Protection, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Identification modeling of ship manoeuvring motion based on ISSA-SVR - Rui Tian; Xiufeng Zhang; Xiuwen Liu (Ocean Engineering, 2024)

Cyclic response and load transfer mechanism of suction bucket jackets supporting offshore wind turbines in soft clay - Baofeng Zhang; Rui Liu; Lizhong Wang; Xuetao Wang; Lilin Wang; Wei Li; Yi Hong (Ocean Engineering, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Sensitive response of erosion and weathering to the Indian Summer Monsoon changes in South Asia during Dansgaard-Oeschger oscillations - Jingrui Li; Xuefa Shi; Shengfa Liu; Fangliang Li; Xiaoming Miao; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Outburst floods and their impact on Chinese Neolithic cultures during the 4.2 ka BP event: Evidence from Dayeze Lake in the lower reaches of the Yellow River - Jinjia Wu; Yuan Li; Yingying Liu; Xingxing Liu; Zhanfang Hou; Rui Zhang; Shiyue Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A review of nanoscale MnOx-based materials: Catalytic and oxidative properties for pollutant degradation in multiple mediums - Zi-Chun Lu; Hai-Zhu Liu; Rui Zhang; Bin Li; Jin-Xing Zhou; Hai-Feng Su (Journal of Water Process Engineering, 2024)

Boosting light harvesting and charge separation in Au nanoparticles and g-C3N4 co-modified TiO2 nanotube arrays for efficient photoelectrocatalytic reduction of nitrate in water - Rui Xu; Yong Guan; Lixue Cao; Xiaoxi Yu; Linsen Li; Bingrui Ma; Chunwei Liu (Journal of Water Process Engineering, 2024)

Effects of tauroursodeoxycholate on arsenic-induced hepatic injury in mice: A comparative transcriptomic analysis - Xiujuan Zheng; Jianbin Cao; He Wang; Lele Liu; Baiming Jin; Hua Zhang; Mingqi Li; Shijing Nian; Haonan Li; Rui He; Ningning Wang; Xuying Li; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Modelling of the trade-off between the deep soil moisture and vegetation restoration in the hilly area of the Loess Plateau, China - Yuqing Chang; Lei Han; Rui Chen; Zhao Liu; Yabei Li; Zilin Zhao; Yifeng Gao; Meili Yang; Xinxin Cao; Zheyuan Miao; Hongliang Kang (Journal of Hydrology, 2024)

Physical mechanism-based simulation methods for soil and ground heat flux from observations at multi-sites - Zhaofei Liu; Dong Jiang; Rui Wang; Mengmeng Hao; Xingxing Zhang (Journal of Hydrology, 2024)

Embryonic exposure to glycopeptides induces acute toxicity and developmental neurotoxicity in zebrafish (Danio rerio) - Kehui Liu; Jiyang Du; Yuanyuan Ma; Haicheng Hu; Xinyan Ma; Rui Zhang; Hao Wang; Liyan Yu; Jingpu Zhang; Ying Han (Journal of Hazardous Materials, 2024)

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Nanomineralogy of thorite in the supergiant Huayangchuan uranium ore deposit: Revealing a new geochemical behavior of actinide in environment - Rui Liu; Jianjun Wan; Peng Zhang; Yaqin Wang; Lei Zuo; Xiaoheng Zhang; José María González-Jiménez; Fernando Gervilla (Journal of Hazardous Materials, 2024)

Efficient biodegradation of poly(butylene adipate-co-terephthalate) in mild temperature by cutinases derived from a marine fungus - Fan Fei; Zhenjie Su; Rui Liu; Rongrong Gao; Chaomin Sun (Journal of Hazardous Materials, 2024)

Comparison of three spatial interpolation methods in predicting time-dependent toxicities of single substances and mixtures - Rui Qu; Yuanzhao Xiong; Ruiping Li; Jiwen Hu; Honglin Liu; Yingping Huang (Journal of Hazardous Materials, 2024)

Effect of clayey sediment compression on fluoride enrichment in the Quaternary groundwater system of Cangzhou Plain, China - Rui Liu; Haipeng Guo; Juan Chen; Haigang Wang; Xisheng Zang; Guijie Wang; Yunlong Wang; Juyan Zhu (Journal of Hazardous Materials, 2024)

ABA-regulated MAPK signaling pathway promotes hormesis in sugar beet under cadmium exposure - Xiaoxin Zhao; Shuoqi Huang; Qi Yao; Rui He; Hao Wang; Zhaodan Xu; Wang Xing; Dali Liu (Journal of Hazardous Materials, 2024)

Smartphone-assisted colorimetric sensor arrays based on nanozymes for high throughput identification of heavy metal ions in salmon - Shuo Wu; Muhammad Arif Khan; Tianzeng Huang; Xing Liu; Rui Kang; Hongbin Zhao; Hongmei Cao; Daixin Ye (Journal of Hazardous Materials, 2024)

Thermodynamic characteristics of nitrifiers reveal the potential NOB inhibition strategies at low temperatures - Ren Li; Lifang Yu; Rui Jiang; Tian Liu; Zhuoya Li; Dangcong Peng (Journal of Cleaner Production, 2024)

Landscape fragmentation of built-up land significantly impact on water quality in the Yellow River Basin - Jinghui Dou; Rui Xia; Kai Zhang; Chao Xu; Yan Chen; Xiaoyu Liu; Xikang Hou; Yingze Yin; Lina Li (Journal of Environmental Management, 2024)

Endogenous phosphorus release from plateau lakes responds significantly to temperature variability over the last 50 years - Chao Yan; Rui Xia; Yan Chen; Lixin Jiao; Xiaoyu Liu; Yingze Yin; Qiang Hu; Kai Zhang; Lina Li; Hao Liu (Journal of Environmental Management, 2024)

Insight into the effect of potassium amyl xanthate on copper pollution caused by chalcopyrite bio-dissolution - Rui Liao; Jun Wang; Shichao Yu; Xin Sun; Shitong Liu; Baojun Yang; Guanzhou Qiu (Journal of Environmental Management, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Visible light-assisted S-doped red mud-based Fe-Co PBA derivatives activated PMS for efficient degradation of oxytetracycline from acidic to alkaline conditions: Degradation mechanism, degradation pathways and toxicity evaluation - Shitong Liu; Jun Wang; Yang Liu; Min Cheng; Baojun Yang; Guangfu Wang; Shichao Yu; Rui Liao; Guanzhou Qiu (Journal of Environmental Chemical Engineering, 2024)

Comparative study of pre- and post-Cu modified calcium-based desulfurizers: Experimental and theoretical insights into adsorption vs. catalysis - Xiaodong Liao; Yulu Liu; Zongshe Liu; Qisong Liu; Wanglai Cen; Rui Fan; Long Li; Jing Shao; Yuxiao Shi (Journal of Environmental Chemical Engineering, 2024)

In-situ electrogenerated persulfate activated by co-existing Cu(II) for sustainable removal of sulfonamides from environmental waters - Yusheng Zhou; Yongfei Ma; Zhikang Deng; Chenyu Zeng; Rui Mu; Yifan Liu; Zulin Zhang (Journal of Environmental Chemical Engineering, 2024)

Highly selective separation of 99TcO4−/ReO4− with rapid liquid-liquid two-phase disengagement by amine-diamide ligands - Long Li; Xuanhao Huang; Xiaoyang Hu; Xingyue Liu; Rui Li; Hang Zhou; Fengfeng Li; Fangxiang Luo; Qingjiang Pan; Songdong Ding (Journal of Environmental Chemical Engineering, 2024)

Room-temperature synthesis of carbon polymer dots from biomass for advanced sensing and fluorescent applications - Lin Lan; Rui Bao; Xin Kong; Liang Liu; Jinsong Wang; Jianhong Yi (Journal of Environmental Chemical Engineering, 2024)

Tolerance of Cu-SSZ-13 catalysts to potassium sulfate: Strong Brønsted acid sites and copper species - Liping Liu; Yang Gao; Yue Ma; Xiaodong Wu; Letong Yang; Xiangju Meng; Rui Ran; Duan Weng (Journal of Environmental Chemical Engineering, 2024)

In situ generation of cuprous oxide in metal-organic framework for significantly enhanced room-temperature ammonia sensing: Synergy enabling excellent sensitivity and selectivity - Honglei Zhang; Zhuang Yan; Yue Ying; Fengbin Zheng; Rui Song; Zhiyong Tang; Yaling Liu (Journal of Environmental Chemical Engineering, 2024)

The influence of Cu2+ and Pb2+ on the characteristics of extracellular polymeric substances (EPSs) from Mucor mucedo and its relationship with pyrene biodegradation - Chunyun Jia; Xuqin Bai; Shiwei Wang; Yue Ding; Rui Liu; Xiaojun Li (Journal of Environmental Chemical Engineering, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Carvacrol acts on the larval midgut of Spodoptera frugiperda by destroying the tissue structure and altering the bacterial community - Jingjing Zhang; Cuiting Liu; Xinyi Xie; Xuanyue Yu; Yuting Huang; Rui Tang; Jian Zeng; Benshui Shu (Journal of Asia-Pacific Entomology, 2024)

Contrastive learning for real SAR image despeckling - Yangtian Fang; Rui Liu; Yini Peng; Jianjun Guan; Duidui Li; Xin Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Analysis of wheat fungal community succession in traditional storage structures using Illumina MiSeq sequencing technology - Ruihu Wang; Mengmeng Li; Rui Jin; Yuanxiao Liu; Erqi Guan; Sherif Ramzy Mohamed; Ke Bian (International Journal of Food Microbiology, 2024)

SoftFormer: SAR-optical fusion transformer for urban land use and land cover classification - Rui Liu; Jing Ling; Hongsheng Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Effective variance attention-enhanced diffusion model for crop field aerial image super resolution - Xiangyu Lu; Jianlin Zhang; Rui Yang; Qina Yang; Mengyuan Chen; Hongxing Xu; Pinjun Wan; Jiawen Guo; Fei Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Vacuum-thermal alteration of lunar soil: Evidence from iron whiskers on troilite in Chang’e-5 samples - Chen Li; Yang Li; Kuixian Wei; Xiumin Chen; Kairui Tai; Zhuang Guo; Rui Li; Han Yu; Xiongyao Li; Wenhui Ma; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2024)

Study on the high-temperature corrosion mechanism of boiler steel 15CrMoG in ammonia-coal co-firing environment - Tiantian An; Bo Wei; Rui Ma; Lijuan Chen; Shan Wang; Meng Xu; Kunpeng Liu (Fuel, 2024)

Impact of the long-term storage on flavor quality of Liupao tea using sensory evaluation combined with metabolomics analysis - Yingyi Huang; Huahong Liu; Jing Wang; Rui Zhang; Yun Zhang; Zhusheng Liu; Yuelan Pang; Chun Yang; Jinfang Nie (Food Research International, 2024)

Exploring the dynamic characteristic of typical kombucha induced by symbiotic microbiota succession from four Chinese regions: A comprehensive analytical framework - Shiqi Li; Ruinan Wang; Rong Liu; Leran Wang; Xingnan Wang; Jianping Wei; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2024)

Occurrence and distribution of phytic acid and its degradation products in soybeans in China: Analytical challenges - Jiayue Chen; Zhenjun Liu; Xinru Cui; Rui Yang; Xinru Guo; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2024)

Volatile flavor profiles of douchis from different origins and varieties based on GC-IMS and GC-O-QTOF/MS analysis - Xiaoqing Miao; Rui Zhang; Shan Jiang; Zhiyuan Song; Ming Du; Aidong Liu (Food Chemistry, 2024)

Protopanaxadiol triggers G0/G1 cell cycle arrest and apoptosis in human cervical cancer HeLa cells through the PPER pathway - Rui Lu; Juanjuan Liu; Kiran Thakur; Hui Cao; Juan Carlos Mejuto; Jesus simal Gandara; Jian-Guo Zhang (Food Bioscience, 2024)

The effect of LuxR solo EvgA on the spoilage potential of Pseudomonas fluorescens - Dangfeng Wang; Benyou Zhang; Yunting Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Fangchao Cui; Tingting Li; Jianrong Li (Food Bioscience, 2024)

Phosvitin phosphopeptides and peptides-calcium chelate promote calcium deposition in a three-cell co-culture system by modulating the OPG/RANKL/RANK signaling pathway - Jiaojiao Chen; Songming Li; Mahmoud Abou-Elsoud; Wei Liu; Rui Cui; Zuyue Li; Dewei Shu; Zhaoxia Cai; Xi Huang (Food Bioscience, 2024)

Fucoidan from Sargassum hemiphyllum (Turner) C. Agardh inhibits human hepatoma cell (HepG2) through cell cycle arrest and apoptotic induction - Yanzhe Chen; Xiaofei Liu; Jianping Chen; Baozhen Luo; Feifei Zhu; Rui Li; Zhuo Wang; Kit-Leong Cheong; Saiyi Zhong (Food Bioscience, 2024)

Planting Chinese milk vetch with phosphate-solubilizing bacteria inoculation enhances phosphorus turnover by altering the structure of the phoD-harboring bacteria community - Danna Chang; Yarong Song; Hai Liang; Rui Liu; Cheng Cai; Shuailei Lv; Yulin Liao; Jun Nie; Tingyu Duan; Weidong Cao (European Journal of Soil Biology, 2024)

Mechanisms of heavy metal-induced rhizosphere changes and crop metabolic evolution: The role of carbon materials - Bingyu Zhu; Yanling Deng; Renjie Hou; Rui Wang; Chao Liu; Zilin Jia (Environmental Research, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

Ticks carry various antibiotic resistance genes and can serve as vectors for their dissemination and as reservoirs by vertical propagation - Yi Wu; Yuechen Sun; Jingpeng Liu; Yixin Ma; Lizhu Fang; Yaming Zhang; Rui Qi (Environmental Research, 2024)

Curcumin protects porcine granulosa cells and mouse ovary against reproductive toxicity of aflatoxin B1 via PI3K/AKT signaling pathway - Sihong Li; Rui Li; Jun Jiang; Lu Liu; Xiang Ma; Tao Wang; Lili Zhao; Weifen Li; Dong Niu (Environmental Pollution, 2024)

Mechanisms of manganese-tolerant Bacillus brevis MM2 mediated oxytetracycline biodegradation process - Zhiyan Li; Jin Wang; Rui Deng; Liu Azuan; Mingzhu Chen; Xiao He; Zhengbo Yue (Environmental Pollution, 2024)

Grazing reduced vegetation biomass and root nutrition related to plateau zokor creating mounds in summer on the Tibetan Plateau - Zhiying Zhang; Bin Chu; Limin Hua; Rui Dong; Kechi Dong; Xincheng Cai; Jize Liu; Ruixun Gan; Longming Dong; Jing Zhang; Wenqian Sun; Jian Sun; et al. (Ecological Engineering, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Improved nitrate removal by polyvinyl alcohol/sodium alginate hydrogel beads entrapping salt-tolerant composite bioagent AHM M3 - Rui Han; Hongjing Ma; Xin Su; Jing Song; Peiwu Liu; Yinghai Wu; Ying Liu (Desalination, 2024)

Investigating the effects of diverse cavity morphologies on the mechanism of tensile crack-induced collapse: A phase field method approach - Shikuo Chen; Rui Wang; Yifan Hou; Jie Liu; Pingchao Yue; Weigang Shen (Computers and Geotechnics, 2024)

Black phosphorus-loaded anisotropic nanofiber sponges for random skin flaps regeneration - Sizhe Song; Jiahui Guo; Bin Kong; Rui Liu; Jinglin Wang; Ling Lu; Yuanjin Zhao (Chemical Engineering Journal, 2024)

Microalgae biofilm barrier to assist the simultaneous nitrogen and phosphorus removal in anammox: Molecular mechanism on sludge granulation and microbial metabolism - Xue Chen; Rui Hu; Mengting Xia; Shiliang Heng; Jiandong Wang; Zhaobin Liu; Jiahua Tian; Xueqin Lu; Guangyin Zhen (Chemical Engineering Journal, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Tailoring Na2FePO4F nanoparticles as the high-rate capability and Long-life cathode towards fast chargeable sodium-ion full batteries - Weihuang Wang; Shuhui Li; Yixin Jia; Dongqiang Cao; Rui Liu; Zheng Wang; Zicheng Xie; Lantian Zhang; Liangbing Wang (Chemical Engineering Journal, 2024)

Unraveling the chloride ion capture capability of nitrogen-doped porous carbon for capacitive deionization and desalination battery - Huazeng Yang; Rui Zhang; Zhiyuan Liu; Xin Xu; Yishuo Teng; Ming Hou; Guangshuai Zhang; Yongzhao Hou; Guangwu Wen; Dong Wang (Chemical Engineering Journal, 2024)

Waste lithium-ion batteries for selective transfer hydrogenation of bio-based ethyl levulinate: Experiments, kinetics and economic assessment - Jun Zhang; Zihao Li; Huiyu Liu; Rui Shan; Haoran Yuan; Yong Chen (Chemical Engineering Journal, 2024)

Sample-to-answer point-of-care testing platform for quantitative detection of small molecules in blood using a smartphone-and microfluidic-based nanoplasmonic biosensor - Hongli Fan; Rui Li; Youqian Chen; Qiang Da; Chenchen Xiong; Yiyi Zhang; Zhiguo Qin; Gang L. Liu; Liping Huang (Chemical Engineering Journal, 2024)

Feasibility of double nitrite supply through partial nitrification and partial denitrification driven by sludge fermentation - Jinjin Liu; Rui Wang; Shengjie Qiu; Yi Peng; Yongzhen Peng (Bioresource Technology, 2024)

Disentangling the effects of meteorology and emissions from anthropogenic and biogenic sources on the increased surface ozone in Eastern China - Min Shao; Shun Lv; Yueming Song; Rui Liu; Qili Dai (Atmospheric Research, 2024)

Mining of dynamic traffic-meteorology-atmospheric pollutant association rules based on Eclat method - Yonghong Liu; Xinru Yang; Kui Liu; Rui Xu; Yuzhuang Pian; Shikun Liu (Atmospheric Pollution Research, 2024)

Peroxymonosulfate Activation by MnO2/CoMoO4/NF for Degradation of Levofloxacin - Yonglei Xing; Huijuan Liu; Yu Ha; Xiaoyong Jin; Beibei Kou; Rui Yang; Gang Ni (Water, Air, & Soil Pollution, 2024)

Deep Learning Approach for Hydraulic Support Anomaly Detection: Utilizing Convolutional Autoencoders and Dynamic Time Warping Technology - Xigui Zheng; Cong Wang; Chao Kong; Cancan Liu; Kai Zhan; Rui Xu (Rock Mechanics and Rock Engineering, 2024)

Exploring the non-linear relations between the cropland expansion and driving factors in China - Liye Wang; Qiangqiang Xiong; Zhaomin Tong; Rui An; Yaolin Liu; Siyu Zhang (Regional Environmental Change, 2024)

Mir-204-5p alleviates mitochondrial dysfunction by targeting IGFBP5 in diabetic cataract - Jin Xie; Peng Chen; Shilan Mao; Xinyi Zang; Rui Cao; Wenhui Liu; Xiaolei Wang; Yunhai Dai (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Neuroprotective Effect of a Multistrain Probiotic Mixture in SOD1G93A Mice by Reducing SOD1 Aggregation and Targeting the Microbiota-Gut-Brain Axis - Zikai Xin; Cheng Xin; Jia Huo; Qi Liu; Hui Dong; Rui Li; Yaling Liu (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by the selective loss of motor neurons. A bidirectional communication system known as the “microbiota-gut-brain” axis has a regulatory function in neurodegenerative disorders. The impact of probiotics on ALS through the “microbiota-gut-brain” axis remains uncertain. A longitudinal investigation was conducted to examine the alterations in the structure of the ileum and colon in mutant superoxide dismutase 1 (SOD1 G93A ) transgenic mice models of ALS by using immunofluorescence and Western blotting. Subsequently, the mice were administered a multistrain probiotic mixture (LBE) or vehicle orally, starting from 60 days of age until the terminal stage of the disease. The effects of these agents on the behavior, gut microbiota, microbial metabolites, and pathological processes of the spinal and intestine of SOD1 G93A mice were analyzed, with a focus on exploring potential protective mechanisms. SOD1 G93A mice exhibit various structural abnormalities in the intestine. Oral administration of LBE improved the proinflammatory response, reduced aberrant superoxide dismutase 1 (SOD1) aggregation, and protected neuronal cells in the intestine and spinal cord of SOD1 G93A mice. Furthermore, LBE treatment resulted in a change in intestinal microbiota, an increase in short-chain fatty acid levels, and an enhancement in autophagy flux. SOD1 G93A mice exhibited various structural abnormalities in the intestine. LBE can improve the proinflammatory response, reduce aberrant SOD1 aggregation, and protect neuronal cells in the spinal cord and intestine of SOD1 G93A mice. The positive effect of LBE can be attributed to increased short-chain fatty acids and enhanced autophagy flux.

Circulating CD8 + LGALS9 + T Cell Population Exhibiting Low Cytotoxic Characteristics are Decreased in Patients with Systemic Lupus Erythematosus - Qi Li; Guochong Wang; Zihang Yuan; Rui Kang; Yaxin Li; Ayibaota Bahabayi; Ziqi Xiong; Zhonghui Zhang; Chen Liu (Immunologic Research, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

MiR-3571 modulates traumatic brain injury by regulating the PI3K/AKT signaling pathway via Fbxo31 - Yang Zhang; Zongying He; Qiongfang Hu; Huali Liu; Rongai Wen; Na Ru; Jinghua Yu; Shaokun Lv; Rui Tao (Cell Biochemistry and Biophysics, 2024)

A novel data-driven hybrid intelligent prediction model for reservoir landslide displacement - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Bulletin of Engineering Geology and the Environment, 2024)

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

Influence of staggered guide vane on hydraulic performance of reactor coolant pump - Binhao Liu; Daoxing Ye; Junlin Chen; Mengke Wu; Rui Deng; Junyu Zhang; Jiaming Han (Annals of Nuclear Energy, 2024)

Rapid and accurate bacteria identification through deep-learning-based two-dimensional Raman spectroscopy - Yichen Liu; Yisheng Gao; Rui Niu; Zunyue Zhang; Guo-Wei Lu; Haofeng Hu; Tiegen Liu; Zhenzhou Cheng (Analytica Chimica Acta, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Phylogenomic analyses and comparative genomic studies of Thermus strains isolated from Tengchong and Tibet Hot Springs, China - Inam Ullah Khan; Muhammad Saqib; Arshia Amin; Sadia Manzoor; Iftikhar Ahmed; Rui-Rui Liu; Jian-Yu Jiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Pilot study to reconstruct life history of Diaphus thiollierei from the Arabian Sea by otolith microstructure and microchemistry - Lisheng Wu; Wenxin Zhuang; Qiaohong Liu; Rui Wang; Yuan Li; Longshan Lin; Shufang Liu; Shaoxiong Ding (Acta Oceanologica Sinica, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

ZC3H13 promotes autophagy in bladder cancer through m6A methylation modification of PJA2 and ubiquitination of KSR1 - Beibei Liu; Mengjie Chen; Yujie Liang; Zhijie Mei; Wei Sun; Wuyue Gao; Tiantian Zhang; Rui Wang; Yuanyuan Guo (Human Cell, 2024)

Optimization of Preparation Technology for PET-Based Carbon Dots by Response Surface Method and Its Application - Chaohui Ma; Gaoling Jin; Puzhen He; Chuanjiang Tang; Linhan Bing; Botong Liu; Hanjiang Huang; Yu Fan; Rui Wang; Jianfei Wei (Journal of Fluorescence, 2024)

An Innovative Online Adaptive High-Efficiency Controller for Micro Gas Turbine: Design and Simulation Validation - Rui Yang; Yongbao Liu; Xing He; Zhimeng Liu (Journal of Marine Science and Engineering, 2024)
In this article, an innovative online adaptive high-efficiency control strategy is proposed to improve the power generation efficiency of a marine micro gas turbine under partial load. Firstly, a mathematical model of the micro-gas turbine is established, and a control strategy consisting of an on-board prediction model and an online update model is proposed. To evaluate the performance changes of the gas turbine, we applied deep learning techniques to enhance the extreme learning machine (ELM) algorithm, resulting in the development of a high-precision, high-real-time deep extreme learning machine (DL_ELM) prediction model. This model effectively monitors changes in the gas turbine’s performance. Furthermore, an online time-series deep extreme learning machine with a dynamic forgetting factor (DFF_DL_OSELM) model is designed to achieve the real-time tracking of performance variations. When the DL_ELM model detects a gas turbine’s performance change, a particle swarm optimization (PSO) algorithm is employed to iteratively calculate the DFF_DL_OSELM model, determining the optimal speed control scheme to ensure the gas turbine operates at maximum efficiency. To validate the superiority of the proposed control strategy, a comparison is made with traditional high-efficiency control strategies based on polynomial fitting and BP neural networks. The results demonstrate that although all three strategies can achieve efficient operation under constant conditions, traditional strategies fail to identify and adjust to performance changes in real time, leading to decreased control performance and potential engine damage as engine characteristics degrade. In contrast, the proposed online adaptive control strategy dynamically adjusts the speed control plan based on performance degradation, ensuring that the gas turbine operates efficiently while keeping the turbine inlet and exhaust temperatures within safe limits.

Small intestine structural and functional responses to environmental heavy metal stress in tree sparrow Passer montanus nestlings - Fei Jin; Yue Shen; Zhaocun Lin; Yuquan Miao; Yu Liu; Rui Su; Wenya Zhang; Yingmei Zhang (Environmental Science and Pollution Research, 2024)

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Innovative beverage creation through symbiotic microbial communities inspired by traditional fermented beverages: current status, challenges and future directions - Shiqi Li; Xiaoshuang Liu; Leran Wang; Kai Wang; Menghui Li; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Critical Reviews in Food Science and Nutrition, 2024)

Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Parasitic infestations present significant threats to the physiological health and ecological stability of aquatic species, frequently compromising immune defenses and elevating mortality rates. This study was conducted to elucidate the non-specific immune responses induced by Pallisentis (Neosentis) celatus infection in Monopterus albus, with a focus on intestinal histopathology and transcriptome gene expression. A histopathological examination revealed minor alterations in intestinal villi under low-level infection. A transcriptome analysis, performed using Illumina sequencing technology, identified 347 upregulated and 298 downregulated genes involved in critical biological pathways, such as lipid metabolism, immune responses, and the regulation of inflammatory processes. GO and KEGG analyses indicated the upregulation of immune-related pathways, including the RIG-I-like and IL-17 signaling pathways, highlighting a robust intestinal immune response. Conversely, the complement pathway was found to be downregulated, with significant suppression of C9, suggesting that the parasite may engage in immune evasion. Fluorescein-labeled C9 antibody assays confirmed reduced complement C9 levels in the infected tissues. A real-time PCR analysis identified the differential expression of eight genes, including C5, maats1, CFI, and gmnc, which were consistent with the sequencing results. These findings suggest that Pallisentis (Neosentis) celatus infection compromises intestinal health, induces inflammation, and activates non-specific immune responses in Monopterus albus. However, Pallisentis (Neosentis) celatus appears to evade the host immune response by suppressing the activation of complement components, thereby facilitating its reproductive parasitism.

Mechanisms underlying mitochondrial dysfunction and intestinal damage induced by ingestion of microplastics in Leuciscus waleckii: The role of the NF-κB/Nrf2 signaling pathway - Si Ying Liu; Deng Lai Li; Rui Zhu; Si Tong Meng; Yin Tao Wang; Liang Li; Zhi Yong Yang; Li Fang Wu (Chemosphere, 2024)

A multimodal classification method: Cow behavior pattern classification with improved EdgeNeXt using an inertial measurement unit - Yingqi Peng; Yingxi Chen; Yuxiang Yang; Meiqi Liu; Rui Hu; Huawei Zou; Jianxin Xiao; Yahui Jiang; Zhisheng Wang; Lijia Xu (Computers and Electronics in Agriculture, 2024)

Changes in phycospheric and environmental microbes in Neoporphyra haitanensis during the cultivation cycle - Qiqin Liu; Rui Yang; Yepengyu Gu; Denghui Gu; Juanjuan Chen; Qijun Luo; Haimin Chen (Aquaculture, 2024)

Characterising equivalent droplet indicators of sprinkler irrigation from a kinetic energy perspective - Rui Zhang; Yichuan Liu; Delan Zhu; Pute Wu; Changjuan Zheng; Xiaomin Zhang; Nazarov Khudayberdi; Changxin Liu (Biosystems Engineering, 2024)

Z-Ligustilide restricts rabies virus replication by inducing ferroptosis through the ACSL4-LPCAT3-POR pathway - Jianqing Zhao; Qianruo Wang; Zhenkun Liu; Meixin Sun; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Insights into source-specific PM2.5 mass, light extinction, and health risks in heavily polluted urban and suburban areas, northwestern China - Julian Shi; Chongshu Zhu; Suixin Liu; Yao Qu; Wenting Dai; Nan Wang; Luyao Wang; Yue Zhou; Rui Li; Yingqiang Shi; Junji Cao (Urban Climate, 2024)

Integrating street-view imagery and points of interest for refining population spatialization: A case study in Wuhan City - Yaxian Qing; Huayi Wu; Kunlun Qi; Zhipeng Gui; Yuhang Liu; Zhenqiang Li; Rui Li (Sustainable Cities and Society, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Quantifying spatial interaction centrality in urban population mobility: A mobility feature- and network topology-based locational measure - Jing Cai; Rui Li; Zhaohui Liu; Xinrui Liu; Huayi Wu (Sustainable Cities and Society, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Assessing soil remediation effect of Cr and Pb based on bioavailability using DGT, BCR and standardized determination method - Rui Chen; Jingyan Yang; Xuying Cai; Zean Liu; Wenyang Huang; Rongguang Shi; Tiantian Ma (Science of The Total Environment, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Green manuring combined with zeolite reduced nitrous oxide emissions in maize field by targeting microbial nitrogen transformations - Rui Liu; Danna Chang; Guopeng Zhou; Hao Liang; Jiudong Zhang; Qiang Chai; Weidong Cao (Science of The Total Environment, 2024)

Comparison of prenatal and postnatal exposure to neonicotinoids and their temporal trends in breast milk - Kaiqin Huang; Meiqing Lin; Jing Yi; Guocheng Liu; Rui Hua; Yangyang Liu; Yanji Qu; Cairong Chen; Shengtao Ma (Science of The Total Environment, 2024)

Increased stress from compound drought and heat events on vegetation - Shuang Zhou; Shaohong Wu; Jiangbo Gao; Lulu Liu; Delong Li; Rui Yan; Jie Wang (Science of The Total Environment, 2024)

Mechanisms of litter input changes on soil organic carbon dynamics: a microbial carbon use efficiency-based perspective - Jia Zeng; Xiangyang Li; Rui Song; Haoxuan Xie; Xiangnan Li; Weichao Liu; Hanyu Liu; Yaoyao Du; Miaoping Xu; Chengjie Ren; Gaihe Yang; Xinhui Han (Science of The Total Environment, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Ancient genomic time transect unravels the population dynamics of Neolithic middle Yellow River farmers - Shiwei Li; Rui Wang; Hao Ma; Zheng Tu; Limin Qiu; Haodong Chen; Li Jiang; Yuezu Geng; Hai Liu; Jifeng Wang; Qu Shen; Li Jin; et al. (Science Bulletin, 2024)

A novel AMSR2 retrieval algorithm for global C-band vegetation optical depth and soil moisture (AMSR2 IB): Parameters' calibration, evaluation and inter-comparison - Mengjia Wang; Philippe Ciais; Frédéric Frappart; Shengli Tao; Lei Fan; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; Jean-Pierre Wigneron (Remote Sensing of Environment, 2024)

Synergistic effects and comprehensive analysis of interaction during infrared co-pyrolysis of furfural residues and PVC - Yue Zhang; Moshan Li; Zuohua Liu; Jianglong Yu; Erfeng Hu; Rui Qu; Shuai Li (Process Safety and Environmental Protection, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

A novel 4-DOF marine stern bearing support model considering discrete distribution effects - Ziqi Chen; Ji Wang; Rui Li; Yujun Liu (Ocean Engineering, 2024)

Composited sea surface responses to tropical cyclones in the Bay of Bengal during 2003–2020 - Mengyuan Xu; Xiuting Wang; Liang Sun; Haihua Liu; Rui Liu; Gaopeng Lu (Marine Environmental Research, 2024)

Photo-induced BiVO4 to produce P25-like structure for enhancing piezo-photocatalytic activity - Ying Cheng; Zhiyuan Ni; Wenliang Wang; Xuefei Lei; Biao Wang; Xuanwen Liu; Rui Guo (Journal of Water Process Engineering, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

Corrigendum to “An urban agricultural block construction method based on low-carbon concepts: A case study of the Beijing-Tianjin area in China” [J. Clean. Product. 477 (2024) 143874] - Rui Zhang; Xiaojiao Li; Yukun Zhang; Xidong Ma; Huanjie Liu; Tianyi Chen (Journal of Cleaner Production, 2024)

Effective strategy to improve nitrification inhibitor efficiency and minimize environmental risk with microenvironments created by ecofriendly biocomposites - Dongjia Li; Ting Yang; Qi Wang; Saihong Wang; Yingying Sun; Rui Liu; Deli Chen (Journal of Environmental Management, 2024)

Unveiling the impact of low-molecular-weight organic acids on enrofloxacin sorption in North China agricultural soil: Insights and implications - Yufeng Jiang; Jiali Wu; Zhewei Liu; Rui He; Xiaozhen Zhang; Kui Huang; Yingqin Wu (Journal of Environmental Management, 2024)

Eliminated high lipid inhibition in the anaerobic digestion of food waste for biomethane production by engineered E. coli with cell surface display lipase - Shuai Zhao; Hanyan Li; Qiutong Wang; Rui Liu; Xinyan Lai; Tawatchai Sumpradit; Aman Khan; Jianhang Qu (Journal of Environmental Management, 2024)

Iron-modified biochars and their aging reduce soil cadmium mobility and inhibit rice cadmium uptake by promoting soil iron redox cycling - Tianren Si; Xin Chen; Rui Yuan; Siyu Pan; Yan Wang; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Stephen Joseph; Lianqing Li; Genxing Pan (Journal of Environmental Management, 2024)

Green modification of biochar with poly(aspartic acid) enhances the remediation of Cd and Pb in water and soil - Xinjun Zhu; Zhan Wang; Yunfei Teng; Yang Sun; Weizhe Wang; Hailing Zhang; Hengyu Chu; Jingxia Zhang; Rui Liu; Lianying Zhang (Journal of Environmental Management, 2024)

Unveiling the green path: How urban openness reduces pollution and paves the way to sustainability - Chao Zhong; Hongbo Cai; Lin Liu; Rui Xue; Yuli Shan (Journal of Environmental Management, 2024)

Orbital and suborbital climate cycles recorded in terrestrial strata from the late Paleocene-early Eocene in the Subei Basin, East China - Juan Liu; Yanzhen Li; Liangcheng Tan; Rui Zhang; Xingxing Liu; Ze Zhang; Anguo Xiao; David B. Kemp; Chunju Huang (Global and Planetary Change, 2024)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Synergistic effects of phosphorylation modification and protocatechuic acid copolymerization improve the physical and oxidation stability of high internal phase emulsion stabilized by perilla protein isolate - Qiaoli Zhao; Jinwei Li; Haili Qin; Rui Li; Kit Leong Cheong; Jianping Chen; Xiaofei Liu; Xuejing Jia; Bingbing Song; Zhuo Wang; Saiyi Zhong (Food Chemistry, 2024)

A pretreatment-free and eco-friendly rapid detection for mycotoxins in edible oils based on magnetic separation technique - Baoxia Ni; Jin Ye; Zhihong Xuan; Li Li; Rui Zhang; Hongmei Liu; Songxue Wang (Food Chemistry, 2024)

Rapid and accurate detection of fish allergen within 30 min using a food nucleic acid releaser combined with rapid real time PCR assay - Yanran Yang; Qianyue Cao; Yansong Liu; Hongri Zhao; Yongzhe Zhang; Lei Diao; Rui Yin (Food Control, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

Leader RNA facilitates snakehead vesiculovirus (SHVV) replication by interacting with CSDE1 and hnRNP A3 - Da Huang; Rui Cheng; Xiaodan Liu; JiaQi Zhang; Chi Zhang (Fish & Shellfish Immunology, 2024)

Stubble height and irrigation significantly influenced the carbon footprint of ratoon rice cropping system in South China - Xiangyu Hu; Youqiang Fu; Nanxun Huang; Xinyu Wang; Rui Hu; Xuhua Zhong; Junfeng Pan; Meijuan Li; Yanzhuo Liu; Qunhuan Ye; Yuanhong Yin; Kaiming Liang (Field Crops Research, 2024)

Implications of soil waterlogging for crop quality: A meta-analysis - Rui Yang; Chunhu Wang; Yinmiao Yang; Matthew Tom Harrison; Meixue Zhou; Ke Liu (European Journal of Agronomy, 2024)

Personalized federated learning for buildings energy consumption forecasting - Rui Wang; Ling Bai; Rakiba Rayhana; Zheng Liu (Energy and Buildings, 2024)

Astronomical forcing of terrestrial organic carbon burial in East Asia during the Eocene - Juan Liu; Juye Shi; Yongchao Lu; Xiaojie Fan; Ze Zhang; Rui Zhang; Zhixiang Wang; Ke Xu; Anguo Xiao; David B. Kemp; Chunju Huang (Earth and Planetary Science Letters, 2024)

Multilevel Schur-complement algorithms for scalable parallel reservoir simulation with temperature variation - Mei Zhang; Haijian Yang; Yong Liu; Rui Li (Computer Physics Communications, 2024)

Formate-facilitated recovery of wastewater anammox granular sludge from oxygen inhibition: Effects and mechanisms - Min Xu; Rui Xiao; Fengqian Xu; Wenbo Chai; Wenlong Liu; Huijie Lu (Chemical Engineering Journal, 2024)

Realizing single-layer graphene by simultaneous crystallization and top-down etching of amorphous graphene-like carbon obtained via CVD - Guoqing Li; Jingmei Tao; Xiaofeng Chen; Yichun Liu; Caiju Li; Rui Bao; Jianhong Yi (Chemical Engineering Journal, 2024)

Dynamics of impure CO2 and composite oil in mineral nanopores: Implications for shale oil recovery and gas storage performance - Lu Wang; Run Zou; Yifan Yuan; Yifan Zhang; Rui Zou; Liang Huang; Yisheng Liu; Zhan Meng; Hao Chen (Chemical Engineering Journal, 2024)

Enhancing electrocatalytic oxidation via spatial confinement in Ti4O7 Nanopore Membranes: Synthesis, Characterization, and Mechanistic insights - Rui Pang; Pingzhou Duan; Mingyue Li; Dan Li; Lixia Zheng; Yifei Zhang; Li Liu; Jian Wei; Feng Qian (Chemical Engineering Journal, 2024)

Zirconium based metal–organic frameworks with aggregation-induced electrochemiluminescence for sensitive analysis of aflatoxin B1 by signal dual-amplification strategy - Yuan Li; Xue Dong; Tingting Wu; Xiaoyue Zhang; Xiang Ren; Rui Feng; Yu Du; Jin Yong Lee; Xuejing Liu; Qin Wei (Chemical Engineering Journal, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

Precise regulation of layered-to-rock structure of spent Li-ion cathodes achieving ultrahigh lithium recovery rate - Xue Bai; Yanzhi Sun; Rui He; Zhenfa Liu; Junqing Pan (Chemical Engineering Journal, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

Structurally programmed bioderived polyimide for foldable humidity sensors with ultrafast response and recovery times - Caihong Gong; Huilong Liu; Shaoji Wu; Zhao Liu; Sutong Zheng; Yanhuang Tang; Zhiming Qiu; Rui Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

Mesenchymal stem cells-laden self-healing hydrogel microfiber fragments from microfluidic bubbles interrupted spinning for wound healing - Yingbo Shen; Rui Liu; Xiangyi Wu; Ying Lu; Bin Kong; Yuanjin Zhao (Chemical Engineering Journal, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Imitation expansion bolts structural bonding interface: Enhancing the bonding properties of bamboo composites through host–guest molecular recognition - Rui Zhao; Tongda Liu; Xin Ran; Jun Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2024)

Mn vacancy engineering design of Fe/Mn based cathodes for breaking the spell between “sodium limiting” in air-stabilization and “sodium promoting” on kinetics - Rui Huang; Shaohua Luo; Qi Sun; Xin Yan; Haoran Zhang; Lixiong Qian; Xin Liu; Xingzhong Cao; Peng Zhang; Shengxue Yan (Chemical Engineering Journal, 2024)

A superior material with antithrombotic properties serves as a secure adsorbent for the elimination of bilirubin in vitro and in pig models - Rui Su; Wei Liu; Gang Shi; Dongling Chen; Lihua Yan; Qian Li; Haichao Ni; Meili Yu; Liang Xu (Chemical Engineering Journal, 2024)

Multifunctional visible light photocatalytic carbon dots synergize with reactive oxygen species for anti-quorum sensing and anti-bacteria for salmon preservation - Fangchao Cui; Xin Wang; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Yilin Lu; Xuepeng Li; Tingting Li; et al. (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Half-antibody spur one-to-one recognition mechanism can function with chemical-staining technology for next-generation lateral flow immunoassay - Jingke Xu; Jing Zhou; Kai Liu; Tong Bu; Leina Dou; Rui Shu; Sijie Liu; Shaochi Wang; Xuechi Yin; Daohong Zhang; Ruiling Zhang; Jie Cheng; et al. (Chemical Engineering Journal, 2024)

Mechanism of o-cresol polymerization and its carbon recovery from aqueous solution by a cathode/Fe2+/H2O2 process - Sui-Qin Yang; Yu-Hong Cui; Wei-Jun Xue; Zheng-Qian Liu; Rui Hu; Xiao-Qian Ye (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Elevating electrochemical performance of Na4MnCr(PO4)3 cathode material for sodium ion batteries through the synergistic effect of Sc doping and RuO2/C coating - Qing Zhu; Jinxin Wu; Rui Tong; Xiuli Hu; Ningchen Tian; Botian Liu; Jiqiong Jiang; Yanwei Li; Jianwen Yang; Jianwei Zhao (Chemical Engineering Journal, 2024)

Preferred crystal surface exposure and near-crystal surface desolvation construct efficient Zn plating/stripping reversibility - Zihan Qi; Murong Xi; Zhenjie Liu; Rui Sheng; Wei Wang; Tianlong Wu; Yudai Huang (Chemical Engineering Journal, 2024)

“Four-in-One” multifunctional nanohybrids integrated magnetic colorimetric catalytic SERS-driven lateral flow immunoassay for ultrasensitive detection of MPXV - Xiaoxian Liu; Xingsheng Yang; Zongzheng Zhao; Xiao Li; Jing Liang; Yinuo Sun; Rui Xiao; Guanghui Wang (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

A miniaturized microfluidic nanoplasmonic sensor with cavity reflection enhancement for ultrasensitive molecular interaction analysis - Hongli Fan; Mingqian Chen; Rui Li; Youqian Chen; Shaoqi Zeng; Wenjun Hu; Gang L. Liu; Chunmeng Sun; Liping Huang (Chemical Engineering Journal, 2024)

Construction of a highly ordered SiC nanofiber@C fiber heterojunction hybrid with a fuzzy grass-like structure for enhanced microwave absorbing performance - Wenzhao Geng; Yilin Liu; Haoyuan Lei; Limeng Song; Hailong Wang; Gang Shao; Yanqiu Zhu; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2024)

Hybrid packed bed bioreactor using combined biodegradation and ozonation to enhance nitrogen and micropollutants removal from landfill leachate - Xuetong Yang; Ze Liu; Changtao Chen; Tao Zhang; Qintong Wang; Rui Zhang; Feng Duan; Xiang Tian; Mingshui Yao; Kristof Demeestere; Stijn W.H. Van Hulle (Bioresource Technology, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Establishment of high temporal-spatial resolution anthropogenic emission inventory of air pollutants in 2017 for Macao, China - Yongfan Wu; Yan You; Zhongcai Wang; Andi Zhang; Yuanxi Gao; Shuai Wang; Yang Liu; Rui He; Zhijiong Huang; Shaojun Zhang (Atmospheric Environment, 2024)

Quantifying night-time light change drivers in China’s Yangtze River economic zone - Pinglang Kou; Yuxiang Tao; Ali P. Yunus; Qiang Xu; Rui Liu; Zhao Jin; Wenli Liang; Ying Xia; Shuang Yuan (International Journal of Remote Sensing, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

MSC-mediated mitochondrial transfer restores mitochondrial DNA and function in neural progenitor cells of Leber’s hereditary optic neuropathy - Rui Wang; Feixiang Bao; Manjiao Lu; Xiaoyun Jia; Jiahui Xiao; Yi Wu; Qingjiong Zhang; Xingguo Liu (Science China Life Sciences, 2024)

Resuspended sediment in marine bottom water as a potential source for refractory dissolved organic matter - Xiaoqing Liu; Rui Bao (Science China Earth Sciences, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Exploring the sorption/desorption of nitenpyram in loess soils: implications for neonicotinoid fate and ecological risk assessment - Rui He; Yufeng Jiang; Zhewei Liu; Jiali Wu; Xiaozhen Zhang; Yingqin Wu (Environmental Geochemistry and Health, 2024)

Analysis of factors affecting microbial degradation of cyanobacterial toxins based on theoretical calculations - Jianglong Ling; Ye Ruan; Congchao Xu; Di Liu; Bowen Shi; Yihong Yang; Zihao Jia; Tianyu Zhang; Mingxuan Guo; Rui Li; Xixi Li (Environmental Geochemistry and Health, 2024)

Association of Plasma Metal Levels with Outcomes of Assisted Reproduction in Polycystic Ovary Syndrome - Dan Yin; Rui Mao; Die Wang; Ping Yu; Cuilan Zhou; Jun Liu; Suyun Li; Yulin Nie; Hongqing Liao; Cuiying Peng (Biological Trace Element Research, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

Vermicompost enhances the salt tolerance of maize by reshaping the rhizosphere microenvironment - Mengli Liu; Jia Cao; Chong Wang; Binglei Wang; Rui Xue (Applied Soil Ecology, 2024)

Source identification of nitrate in groundwater of an agro-pastoral ecotone in a semi-arid zone, northern China: Coupled evidences from MixSIAR model and DOM fluorescence - Anqi Chen; Yao Du; Zichen Wang; Xiaoliang Sun; Rui Xu; Yaojin Xiong; Liangping Yang; Junting Liu; Yiqun Gan (Applied Geochemistry, 2024)

Antibacterial effects and mechanisms of quercetin-β-cyclodextrin complex mediated photodynamic on Escherichia coli O157:H7 - Tao Liu; Yuzhang Zhu; Jiahui Wang; Xiangyu Hong; Mi Liu; Chaonan Kong; Rui Zhou; Xianke Li; Lifang Yang (Archives of Microbiology, 2024)

Flow Field Analysis and Development of a Prediction Model Based on Deep Learning - Yingjie Yu; Xiufeng Zhang; Lucai Wang; Rui Tian; Xiaobin Qian; Dongdong Guo; Yanwei Liu (Journal of Marine Science and Engineering, 2024)
The velocity of ocean currents significantly affects the trajectory prediction of ocean drifters and the safe navigation of intelligent vessels. Currently, most ocean current predictions focus on time-based forecasts at specific fixed points. In this study, deep learning based on the flow field prediction model (CNNs–MHA–BiLSTMs) is proposed, which predicts the changes in ocean currents by learning from historical flow fields. Unlike conventional models that focus on single-point current velocity data, the CNNs–MHA–BiLSTMs model focuses on the ocean surface current information within a specific area. The CNNs–MHA–BiLSTMs model integrates multiple convolutional neural networks (CNNs) in parallel, multi-head attention (MHA), and bidirectional long short-term memory networks (BiLSTMs). The model demonstrated exceptional modelling capabilities in handling spatiotemporal features. The proposed model was validated by comparing its predictions with those predicted by the MIKE21 flow model of the ocean area within proximity to Dalian Port (which used a commercial numerical model), as well as those predicted by other deep learning algorithms. The results showed that the model offers significant advantages and efficiency in simulating and predicting ocean surface currents. Moreover, the accuracy of regional flow field prediction improved with an increase in the number of sampling points used for training. The proposed CNNs–MHA–BiLSTMs model can provide theoretical support for maritime search and rescue, the control or path planning of Unmanned Surface Vehicles (USVs), as well as protecting offshore structures in the future.

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Evaluation and fusion of multi-source sea ice thickness products with limited in-situ observations - Tongtong Li; Yangjun Wang; Bin Wang; Kefeng Liu; Xi Chen; Rui Sun (Frontiers in Marine Science, 2024)
Sea ice thickness (SIT) is a critical and sensitive parameter in the climate system, with its dynamic changes profoundly influencing global climate models, navigational routes, and the potential for Arctic resource development. Given the widespread application of current satellite remote sensing technology in monitoring SIT, significant uncertainties remain. This study first underscores the importance of in-situ observations as a direct measurement method for SIT. However, the limitations of in-situ data in terms of acquisition cost, spatiotemporal coverage continuity, and distribution uniformity significantly hinder the effective evaluation of multi-source SIT products. To address this, the study innovatively introduces the Triple Collocation (TC) method, which effectively mitigates the impact of errors from individual data sources on the overall evaluation results through a mutual validation mechanism among multiple satellite data sources. This allows for a scientific assessment of multi-source SIT products even in the context of scarce in-situ observations. The findings indicate that the TC method not only successfully resolves the challenges of multi-source data evaluation but also facilitates data integration among these products, significantly enhancing the overall accuracy and spatiotemporal consistency of SIT data.

Regional water-energy-carbon footprint in the context of sustainable development based on EE-MRIO: cases of Jiangsu, Zhejiang and Shanghai - Huanyu Wang; Qiang Yue; Rui Liu; Yujie Zhang; Heming Wang; Qi Wang (Environment, Development and Sustainability, 2024)

Recovering chromium from electroplating sludge using an integrated technology of bipolar membrane electrodialysis and H2O2 oxidation - Rui Lian; Yaoxing Liu; Yan Pan; Jianguo Ding; Xiaoyun Wu; Mingzhi Lv; Xiaoyu Wu; Riyao Chen; Rui Ding; Jianxi Liu; Bart Van der Bruggen (Chemosphere, 2024)

Deltamethrin increased susceptibility to Aeromonas hydrophila in crucian carp through compromising gill barrier - Xiping Yuan; Hao Wu; Jinwei Gao; Can Yang; Zhenzhen Xiong; Jiayu Wu; Chongrui Wang; Dong Liu; Jianzhong Shen; Rui Song (Chemosphere, 2024)

Simulating droplet distribution characteristics in sprinkler irrigation using a modified ballistic model under multifactor coupling - Rui Zhang; Yichuan Liu; Delan Zhu; Pute Wu; Ke Xin; Xiaomin Zhang; Nazarov Khudayberdi; Changxin Liu (Computers and Electronics in Agriculture, 2024)

Effects of replacing fish meal with biofloc meal on growth performance, nutrients metabolism, immune response and intestinal microbiota of common carp (Cyprinus carpio) - Xiao-Fang Wei; Si-Tong Meng; Yin-Tao Wang; Liang Li; Rui Zhu; Deng-Lai Li; Si-Ying Liu; Li-Fang Wu (Aquaculture, 2024)

Exploring the multiscale island terrestrial ecosystem service relationships and coastal vulnerability under the influence of coastal ecosystems - Rui Du; Baiqiong Liu; Zhou Chen; Min Xu (Ocean & Coastal Management, 2024)

A comprehensive conceptual framework for signaling in-lake CO2 through dissolved organic matter - Maofei Ni; Rui Liu; Weijun Luo; Junbing Pu; Shengjun Wu; Zhikang Wang; Jing Zhang; Xiaodan Wang; Yongmei Ma (Water Research, 2024)

Exhaust emissions and energy conversion of hybrid and conventional CNG buses - Rui Hu; Xinyi Chen; Li Li; Fanling Kong; Yonghong Liu (Transportation Research Part D: Transport and Environment, 2024)

Emulsion-filled surimi gel: A promising approach for enhancing gel properties, water holding capacity, and flavor - Qiaoli Zhao; Bin Zheng; Jinwei Li; Kit Leong Cheong; Rui Li; Jianping Chen; Xiaofei Liu; Xuejing Jia; Bingbing Song; Zhuo Wang; Saiyi Zhong (Trends in Food Science & Technology, 2024)

Exploring the gradient impact of climate and economic geographical factors on city-level building carbon emissions in China: Characteristics and enlightenments - Rui Li; Yanhui Yu; Weiguang Cai; Yuan Liu; Yan Li (Sustainable Cities and Society, 2024)

Nanoscale chestnut soil pore characteristics changes induced by non-growing season precipitation in a temperate grassland - Yifan Song; Tiejun Liu; Rui Jiao; Yajing Lu; Kai Sun; Keke Zhao; Yunhao Wen; Wei Shi; Shaomai Song (Science of The Total Environment, 2024)

Atmospheric brown carbon in China haze is dominated by secondary formation - Xiaodi Liu; Can Wu; Zheng Li; Rongjie Li; Fanglin Wang; Shaojun Lv; Rui Li; Fan Zhang; Haoyang Wang; Chenlong Liang; Lei Zhang; Gehui Wang (Science of The Total Environment, 2024)

A global urban heat island intensity dataset: Generation, comparison, and analysis - Qiquan Yang; Yi Xu; TC Chakraborty; Meng Du; Ting Hu; Ling Zhang; Yue Liu; Rui Yao; Jie Yang; Shurui Chen; Changjiang Xiao; Renrui Liu; et al. (Remote Sensing of Environment, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

New data on Silurian (Llandovery) sinacanthids from Wuhan, South China and their biostratigraphic and paleobiogeographic implications - Yi-Long Liu; Jia-Yi Yin; Ruo-Ying Fan; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Discovery of the earliest Devonian conodonts from Xinjiang, Northwest China - Jia-Yi Yin; Ladislav Slavík; Jian-Feng Lu; Juan Ma; Yi-Long Liu; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

S-nitrosoproteomics profiling elucidates the regulatory mechanism of S-nitrosylation on beef quality - Qin Hou; Tianyi Gao; Rui Liu; Chao Ma; Wangang Zhang (Meat Science, 2024)

Complete genome sequence of the 4-hydroxybenzoate-degrading bacterium Gymnodinialimonas sp. 57CJ19, a potential novel species from intertidal sediments - Dong-Hui Li; Ning Zheng; Zhen-Hai Liu; Xiao-Rui Dong; Chen Zhao; Shi-Gan Yan; Bin-Bin Xie (Marine Genomics, 2024)

Tectonosedimentary patterns of multiple interacting source-to-sink systems of the permian Shanxi Formation, Ordos Basin, China: Insights from sedimentology and detrital zircon U-Pb geochronology - Dan Li; Lei Liu; Zhiwei Wang; Cong Hu; Hongde Chen; Shuyue Zhu; Rui Zhang; Fei Zhao (Marine and Petroleum Geology, 2024)

Sulfur availability and nodulation modify the response of Robinia pseudoacacia L. to lead (Pb) exposure - Caixin Xue; Rui Liu; Zhuyuan Xia; Jin Jia; Bin Hu; Heinz Rennenberg (Journal of Hazardous Materials, 2024)

An urban agricultural block construction method based on low-carbon concepts: A case study of the Beijing-Tianjin area in China - Rui Zhang; Xiaojiao Li; Yukun Zhang; Xidong Ma; Huanjie Liu; Tianyi Chen (Journal of Cleaner Production, 2024)

Environmental safety performance dynamics and estimation of the deterioration of leachate containment elements: Implications for the lifespan of hazardous waste landfills - Rui Xiang; Can Qian; Guangyuan Yao; Yuqiang Liu; Heyu Du; Ya Xu; Qifei Huang (Journal of Cleaner Production, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

Disinfection of bacteria and viruses under near infrared light by tunable self-assembled nanomaterial NH2-MIL-101-xAu based on photothermal and photodynamic mechanisms - Nian Li; Zi-jian He; Jia-min Gan; Xing-rui Qi; Shu-nuo Bian; Yu-fang Chen; Bo Liu; Hua-jie Lai; Tao Jin (Journal of Environmental Chemical Engineering, 2024)

Novel nitrification inhibitor produced by immobilizing 3,4-dimethylpyrazole using biogenic substances instead of chemicals have potential for sustainable agriculture - Dongjia Li; Qi Wang; Ting Yang; Rui Liu; Deli Chen (Journal of Environmental Chemical Engineering, 2024)

Research progress and prospect of covalent organic frameworks (COFs) and composites: From synthesis to application in water contaminants - Rui Li; Fengfei Sun; Zhen Liu; Yuwei Shi; Sizhe He; Junfeng Chen (Journal of Environmental Chemical Engineering, 2024)

Reducing moisture content can promote the removal of pathogenic bacteria and viruses from sheep manure compost on the Qinghai-Tibet Plateau - Rongrong Li; Rui Cai; Xi Luo; Yuru Liu; Lu Zhang; Wenbo Yu; Zhe Yang (Journal of Environmental Chemical Engineering, 2024)

Iron-based materials for immobilization of heavy metals in contaminated soils: A critical review - Yaxin Tian; Guangfei Qu; Rui Xu; Xinxin Liu; Caiyue Jin (Journal of Environmental Chemical Engineering, 2024)

Thermo-economic analysis and multi-objective optimization of cryogenic CO2 capture systems based on liquefied natural gas cold energy utilization - Gequn Shu; Borui Liu; Hua Tian; Ligeng Li; Rui Sun; Xuan Wang (Journal of Environmental Chemical Engineering, 2024)

Enhanced photocatalytic Cr(VI) degradation and real-time detection using dual-fluorescent quantum dot-infused polysulfone microspheres - Rui Zhao; Feihong Hu; Shan Li; Chao Liu; Zhiwei Wang; Zhaoping Song; Dandan Ji; Xiaona Liu; Huili Wang; Wenxia Liu; Fengshan Zhang; Dehai Yu (Journal of Environmental Chemical Engineering, 2024)

Self-cleaning of metal-organic framework membranes achieved by photocatalytic ZIFs for dye and antibiotic separation - Jie He; Rui Zhang; Dong Chen; Ziyin Chen; Jiacheng Jiang; Maoqing Xu; Yujie Liu; Zixi Li; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Environmental Chemical Engineering, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Migration mechanism of atrazine in the simulated lake icing process at different freezing temperatures based on density function theory - Yan Zhang; Hao Lin; Aixin Yu; Xiaozhuang Wang; Yucan Liu; Tongshuai Liu; Chen Zhao; Rui Mei (Journal of Environmental Sciences, 2024)

In-orbit detection of the spectral smile for the Mars Mineral Spectrometer - Bing Wu; Rui Xu; Chengyu Liu; Zhiping He (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

CO2 retention in high-pressure/high-temperature reservoirs of the Yinggehai Basin, northwestern South China Sea - Jinyan Lin; Rui Liu; Niklas Heinemann; Johannes M. Miocic; Jinqiang Tian; Zengyu Chen; Lin Hu; Yazhen Zhang; Julien Amalberti; Lichao Wang (International Journal of Greenhouse Gas Control, 2024)

Reaction mechanism for NH3-SCR of NOx over CrMn1.5O4 catalyst - Zheng-nan Yuan; Rui-tang Guo; Xiao-jing Liu; Yi-feng Xu; Lu Liu; Wei-guo Pan (Fuel, 2024)

Controlled dispersion and morphology in MoS2/SBA-15 catalysts for enhanced COS hydrodesulfurization - Li Yubiao; Cao Rui; Liu Yu; Wang Langlang; Ning Ping; Wang Xueqian; Ma Yixing (Fuel, 2024)

In vitro digestion and functional properties of bovine β-casein: A comparison between adults and infants - Xiaoqian Chen; Rui Fan; Xinyu Wang; Lina Zhang; Caiyun Wang; Zhanqun Hou; Chun Li; Libo Liu; Jian He (Food Research International, 2024)

Characterization of selenium-containing broccoli (Brassica oleracea L. var. italica planch) proteins and evaluation of antioxidant activity by electron spin resonance - Jinjing Yin; Wei Liu; Muci Wu; Ming Chen; Xun Pei; Yuzhen He; Fangxiong Shen; Rui Zhang; Jingren He (Food Chemistry, 2024)

Olfactory perceptual interactions of maltol with key food odorants in binary mixtures: Scatter matrix statistical analysis of odor intensity in heterogeneous perceptual situation - Wei Guan; Runhu Xin; Miao Liang; Yuanhao Zhou; Rui Wang; Yuping Liu (Food Chemistry, 2024)

Exploring Jiangshui-originated probiotic lactic acid bacteria as starter cultures: Functional properties and fermentation performances in pear juice - Du-xin Jin; Yu-xuan Jin; Wei Zhang; Wei Cao; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Food Bioscience, 2024)

Dietary flavonoids: Role in preventing neurodegenerative diseases caused by brain aging by modulating the gut microbiota - Siyu Liu; Haochen Dai; Rui Wang; Xin Zhang (Food Bioscience, 2024)

Relationship between microorganisms and the flavour of douchi obtained from different regions: Analysis using high-throughput sequencing and GC–MS - Rui Zhang; Jing Li; Xiaoqing Miao; Zhiyuan Song; Shan Jiang; Aidong Liu (Food Bioscience, 2024)

Self-assembly metal phenolic network coating improves the controlled release and bacteriostatic properties of Litsea cubeba essential oil-loaded ε-polylysine-pectin nanoparticles - Pengcheng Zhao; Rui Cui; Weiwei Li; Fang Zhang; Xianghong Meng; Bingjie Liu (Food Bioscience, 2024)

Biosynthesis pathway of flavor compound 3-methylbutanal derived from leucine by Lactococcus lactis 517: From a transcriptomics perspective - Lei Chen; Rui Liu; Chenxiang He; Mangang Wu; Qingfeng Ge; Hai Yu (Food Bioscience, 2024)

Inhibition effect of marine active peptides SF on dual-species biofilms of Vibrio parahaemolyticus and Aeromonas sobria - Xinran Lv; Wenqi Yang; Shuilin Liu; Xueqing Liu; Shuo Yuan; Le An; Anqi Ren; Fengling Bai; Jianrong Li; Xuepeng Li; Yuqiong Meng; Rui Ma (Food Bioscience, 2024)

Protective effect of Cyanidin-3-O-glucoside from blueberry anthocyanin extracts against hyperglycemia-induced outer BRB damage by suppressing REDD1-mediated VEGFA upregulation - Rui Li; Shumeng Du; Zhan Ye; Wei Yang; Zhansheng Ding; Yuanfa Liu (Food Bioscience, 2024)

Different regulatory effects of Lycium barbarum polysaccharide components on gut microbiota in vivo and in vitro - Xin An; Shuo Sun; Jiangshan Sun; Rui Liao; Ruisen Ma; Haoan Zhao; Qian Liu (Food Bioscience, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

An effective potential Bifidobacterium animalis F1-7 delivery strategy: Supramolecular hydrogel - sodium alginate/tryptophan-Sulfobutylether-β-cyclodextrin (Alg/Trp-SBE-β-CD) - Xiaoyang Huang; Jing Wang; Rui Liu; Chunrong Yang; Yanchun Shao; Xiaohong Wang; Huaxi Yi; Youyou Lu (Food Hydrocolloids, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

The effects of kelp powder and fucoidan on the intestinal digestive capacity, immune response, and bacterial community structure composition of large yellow croakers (Larimichthys crocea) - Qiqin Liu; Guoyi Li; Sifeng Zhu; Juanjuan Chen; Min Jin; Chengwei Huang; Liyue Chai; Liegang Si; Rui Yang (Fish & Shellfish Immunology, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Spatial distribution and enrichment characteristics of selenium in paddy soil and rice around the Dongting Lake - Rui Liu; Weijun Zhou; De Yu; Guiduo Shang; Yuzhou Zhou; Zhangqian Xu; Dou Tang; Haojie Cui; Chaolin Liao (Environmental Pollution, 2024)

Triple effective water treatment agent: P(AA/AMPS) capped sulfur quantum dots boast remarkable antiscale, antibacterial, and real-time tracking capabilities - Hengtong Xia; Rui Ding; Chao Xia; Ruodong Yang; Zhihao Chen; Hui Xu; Xiaoshuang Yin; Ying Liu; Wenzhong Yang (Desalination, 2024)

Effect of micro and nanobubble size and concentration on membrane fouling: Strategies for energy-saving and ultrafiltration efficiency enhancement - Nachael Mwanga; Xitong Wang; Pan Li; Yanling Liu; Shengji Xia; Daqiang Yin; Min Rui; Yubin Ye (Desalination, 2024)

Recovery of boron and zinc from wastewater via electrodialytic metathesis - Mingzhi Lv; Yaoxing Liu; Jie Jiang; Rui Lian; Hun Xue; Riyao Chen; Rui Ding; Jianxi Liu (Desalination, 2024)

Monitoring crack opening via seismic velocity variation to assess that fatal effect of precipitation for landslide motion - Zhiqiang Liu; Chuntao Liang; Christoph Sens-Schönfelder; Wei Hu; Xinlei Sun; Tuo Zhang; Rui Xu; Zhiyu Jiang; Hao Jiang (Earth and Planetary Science Letters, 2024)

Evaluation of the Methods of Particle Morphology Characterization: CT Scanning, Digital Imaging and Light Microscopy - Karim Kootahi; Anthony Kwan Leung; Zhenliang Jiang; Jianbin Liu; Rui Qi; Sérgio D.N. Lourenço; Zhengshou Lai; Zhiwei Gao (Computers and Geotechnics, 2024)

Bismuth nanosheets guided zinc deposition enabled long-life aqueous zinc-based flow batteries - Yizhe Nie; Huang Chen; Jiajun Wu; Rui Nie; Lihong Yu; Le Liu; Jingyu Xi (Chemical Engineering Journal, 2024)

Hybrid plasma catalysis-thermal system for non-oxidative coupling of methane to ethylene and hydrogen - Rui Liu; Eduardo Morais; Dongxing Li; Pengfei Liu; Qian Chen; Shangkun Li; Li Wang; Xiaoxia Gao; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2024)

Electric field-driven assembly of (110) oriented metal–organic framework ZIF-8 monolayer with high hydrogen selectivity - Chunxin Jin; Shuai Liu; Rui Zheng; Yanhong Li; Xiaofang Chen; Jürgen Caro; Jianwen Jiang; Aisheng Huang (Chemical Engineering Journal, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

An efficient Au/ZnO catalyst for the photocatalytic conversion of methane to formaldehyde - Yan-Qun Chen; Lei-Xin Mao; Rui-Xin Zhang; Xin-Yu Zhang; Zhi-Hua Gao; Lei Liu; Wei Huang; Zhi-Jun Zuo (Chemical Engineering Journal, 2024)

Visible light assisted periodate activation with porous C3N5 for tetracycline degradation: Enhanced electron-hole separation and reactive oxygen species formation - Sitong Liu; Shicheng Liu; Taojin Wang; Letong Yang; Letao Li; Xiaodong Wu; Zhichun Si; Rui Ran; Hui Wu (Chemical Engineering Journal, 2024)

Polystyrene shell-based “coconut-like” and “pomegranate-like” microencapsulated phase change materials: Formation mechanism, thermal conductivity/stability enhancement and their application in thermal management - Wei Zhang; Rui Pan; Jihua Yang; Mengru Liu; Yunle Yao; Awang Zhang; Yi Gong; Zhengya Gan; Rui Hu; Jianjun Ding; Lin Chen; Xian Zhang; et al. (Chemical Engineering Journal, 2024)

Comparing the effects and mechanisms of granular activated carbon and magnetite nanoparticles in dry anaerobic digestion: Focusing on microbial electron transfer and metagenomic evidence - Siqi Wang; Shenwei Cheng; Keqiang Zhang; Fuyuan Liu; Rui Liu; Xingliang Gao; Jiajia Li; Lianzhu Du (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Multifunctional molecular bridge enabled interface passivation and strain release for stable and efficient all-inorganic perovskite solar cells - Zhiwei Ma; Benlin He; Rui Tui; Xinyi Zhang; Qihang Cheng; Changqing Liu; Haiyan Chen; Jialong Duan; Qunwei Tang (Chemical Engineering Journal, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Dual-active sites and reversible-structural covalent organic framework for highly stable alkali metal-ion batteries - Kang Hua; Longhai Zhang; Quanwei Ma; Hongbao Li; Rui Wang; Peng Xiong; Shilin Zhang; Tengfei Zhou; Yangyang Liu; Chaofeng Zhang (Chemical Engineering Journal, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Tracking the Molecular-Scale Mechanistic Pathway of Trapping-Bonding CTAB/Fe3O4-AS for High-Performance Cr(VI) Adsorption - Binqiao Ren; Yu Jin; Xiaoxiao Song; Luyang Zhao; Xue Han; Yuying Zhang; Chongwei Cui; Rui Liu; Han Cui (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Anion vacancy engineering in carbon coating VS4 microspheres assembled by nanorod arrays for high-performance rechargeable Mg-Li hybrid batteries - Xu Zhang; Qinke Tang; Yana Liu; Yunfeng Zhu; Jiguang Zhang; Jun Wang; Rui Shi (Chemical Engineering Journal, 2024)

Dynamic covalent adhesives and their applications: Current progress and future perspectives - Zhipeng Liu; Ying Tang; Yuxuan Chen; Zhiyan Lu; Zebao Rui (Chemical Engineering Journal, 2024)

Spatial control of nanoreactions on cellulose nanofibers using drop evaporation - Rui Ding; Min Zhang; Lujia Xuan; Zhengyuan Ma; Yixiao Qu; Zheng Liu; Hui He; Ruoyang Chen (Chemical Engineering Journal, 2024)

Facile generation of unsaturated-coordinated and atomically-dispersed hafnium active sites for the highly efficient catalytic transfer hydrogenation of levulinic acid - Rulu Huang; Yue Wang; Feiyi Chen; Huai Liu; Rui Zhang; Wenlong Jia; Lincai Peng; Yong Sun; Junhua Zhang (Chemical Engineering Journal, 2024)

The potential of biomimetic nanoparticles for macrophage repolarisation and phagocytosis in tumour immunotherapy - Zhihong Sun; Rui Zhou; Jie Liu; Qi Zhao; Chengming Sun; Yong Sun (Chemical Engineering Journal, 2024)

Outstanding comprehensive energy storage performances in multiscale synergistic regulation-engineered (Bi0.5Na0.5)TiO3-based multilayer ceramics - Hang Xie; Zhenhao Fan; Linjing Liu; Shuai Yang; Qiangwei Kou; Rui Lv; Jian Dai; Hongliang Du; Yunfei Chang; Fei Li (Chemical Engineering Journal, 2024)

Enhancing reaction kinetics in aprotic magnesium-air batteries using a freestanding flexible metal-free carbon fiber cathode - Wenbo Liu; Ning Wang; Rui Zhong; Fanfan Liu; Yongjun Wu; Qianyi Zhang; Xiaoyan Chen; Yanmei Li; Minghui Yu; Rui Xu; Yifei Yuan; Dan Luo; et al. (Chemical Engineering Journal, 2024)

Multifunctional-Element doping of NASICON-Structured cathode enables High-Rate and stable sodium storage - Xi Liu; Chengcheng Zhu; Tianhe Xu; Chang Li; Xinyu Guo; Nan Jiang; Yan Chen; Yushuang Xu; Runduo Zhu; Wenxia Zou; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2024)

Highly stretchable, self-healing, antibacterial, conductive, and amylopectin-enhanced hydrogels with gallium droplets loading as strain sensors - Feihong Hu; Baoting Dong; Dehai Yu; Rui Zhao; Wei Chen; Zhaoping Song; Peng Lu; Fengshan Zhang; Zhaojiang Wang; Xiaona Liu; Huili Wang; Wenxia Liu; et al. (Carbohydrate Polymers, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Investigating thermal exposure during daily walking through a human-scale approach: An analysis of a hot summer in Wuhan - Jiwei Xu; Xinkun Xu; Zimeng Wang; Huiting Chen; Qiran Ren; He Huang; Yao Cui; Rui An; Yaolin Liu (Building and Environment, 2024)

Effect of Dissolved Oxygen on Poly(3-Hydroxybutyrate-co-3-Hydroxyvalerate) Solid-Phase Denitrification: Simultaneous Nitrification and Denitrification Performance and Microbial Community - Peng Zhou; Ying Liu; Xin Su; Peiwu Liu; Rui Han (Water, Air, & Soil Pollution, 2024)

QTL mapping and omics analysis to identify genes controlling kernel dehydration in maize - Xining Jin; Xiaoxiang Zhang; Pingxi Wang; Juan Liu; Huaisheng Zhang; Xiangyuan Wu; Rui Song; Zhiyuan Fu; Shilin Chen (Theoretical and Applied Genetics, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Advances in the Differentiation of hiPSCs into Cerebellar Neuronal Cells - Yingxin Wang; Wenzhu Liu; Yichang Jiao; Yitong Yang; Didi Shan; Xinbo Ji; Rui Zhang; Zexin Zhan; Yao Tang; Dandan Guo; Chuanzhu Yan; Fuchen Liu (Stem Cell Reviews and Reports, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Emodin derivatives as promising multi-aspect intervention agents for amyloid aggregation: molecular docking/dynamics simulation, bioactivities evaluation, and cytoprotection - Rui Shen; Wenshuang Zhao; Xiangyu Li; Juanjuan Liu; Aihong Yang; Xiaodi Kou (Molecular Diversity, 2024)

Earthworms and Arbuscular Mycorrhizal Fungi Alleviated Salt Stress in Maize Seedlings by Regulating the Root Endodermis Diffusion Barrier - Binglei wang; Chong Wang; Lei Zhao; Xuelian Liu; Rui Xue; Jia Cao; Siping Li; Mengyao Guo; Huiying Huang (Journal of Plant Growth Regulation, 2024)

WNT2B high‑expressed fibroblasts induce the fibrosis of IBD by promoting NK cells secreting IL-33 - Yanling Cheng; Shuzhe Xiao; Lin Lan; Danqiong Liu; Rui Tang; Jianbiao Gu; Li Ma; Zhihua He; Xirong Chen; Lanlan Geng; Peiyu Chen; Huiwen Li; et al. (Journal of Molecular Medicine, 2024)

The association between the scarlet fever and meteorological factors, air pollutants and their interactions in children in northwest China - Donghua Li; Yanchen Liu; Wei Zhang; Tianshan Shi; Xiangkai Zhao; Xin Zhao; Hongmiao Zheng; Rui Li; Tingrong Wang; Xiaowei Ren (International Journal of Biometeorology, 2024)

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

Rosiglitazone attenuates Acute Kidney Injury from hepatic ischemia–reperfusion in mice by inhibiting arachidonic acid metabolism through the PPAR-γ/NF-κB pathway - Xiaoyan Qin; Zhengli Tan; Qi Li; Shiyi Zhang; Dingheng Hu; Denghui Wang; Liangxu Wang; Baoyong Zhou; Rui Liao; Zhongjun Wu; Yanyao Liu (Inflammation Research, 2024)

Effects of active vitamin D analogs and calcimimetic agents on PTH and bone mineral biomarkers in hemodialysis patients with SHPT: a network meta-analysis - Xing Liu; Yichen Liu; Peimin Zheng; Xun Xie; Zhouzhou Li; Rui Yang; Lie Jin; Ziwei Mei; Peipei Chen; Limei Zhou (European Journal of Clinical Pharmacology, 2024)

Predicting the impacts of climate change on the geographic distribution of moso bamboo in China based on biomod2 model - Rui Gu; Songpo Wei; Jiarui Li; Shihui Zheng; Zhiteng Li; Guanglu Liu; Shaohui Fan (European Journal of Forest Research, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Lightweight seamless lane-level positioning with the integration of BDS-3 PPP-B2b and VINS: a case study using smartphone - Rui Shang; Chengfa Gao; Xiaolin Meng; Zhenhao Xu; Qi Liu; Qianqian Chen; Xiangdong An (GPS Solutions, 2024)

Co-incorporation of wheat straw and hairy vetch reduced soil N2O emission via regulating nitrifier and denitrifier structure on the Qinghai plateau - Rui Liu; Peng Jiang; Guopeng Zhou; Danna Chang; Hao Liang; Qiang Chai; Weidong Cao (Applied Soil Ecology, 2024)

Global research trends in Rhizodeposition-mediated soil carbon cycle: A bibliometric analysis - Dongming Chen; Fei Yan; Xuemei Fang; Jiqiong Zhou; Xingpeng Hu; Xiaoming Ma; Xin Zheng; Rui Yin; Feida Sun; Yanfu Bai; Zhouwen Ma; Yakov Kuzyakov; et al. (Applied Soil Ecology, 2024)

A dynamic snow depth retrieval model based on time-series clustering optimization for GPS-IR - Tianyu Wang; Rui Zhang; Yunjie Yang; Anmengyun Liu; Yao Jiang; Jichao Lv; Jinsheng Tu; Yunfan Song (Advances in Space Research, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

The role of male hormones in bacterial infections: enhancing Staphylococcus aureus virulence through testosterone-induced Agr activation - Zhaoxia Luo; Huimin Xi; Wei Huang; Mei-fang Liu; Lei Yuan; Qiang Chen; Yanghua Xiao; Qing Zhu; Rui Zhao; Yi-yun Sheng (Archives of Microbiology, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Structure and Evolution of Multi-Trend Faults in BZ19-6 Buried Hill of the Bohai Bay Basin, Eastern China - Rui Lou; Yonghe Sun; Fujie Jiang; Yumin Liu; Tian Gao (Journal of Marine Science and Engineering, 2024)
Defining the structure and evolution of multi-trend faults is critical for analyzing the accumulation of hydrocarbons in buried hills. Based on high-resolution seismic and drilling data, the structural characteristics and evolutionary mechanism of multi-trend faults were investigated in detail through the structural analysis theory and quantitative calculations of fault activity, allowing us to determine the implication that fault evolution exerts on hydrocarbon accumulation in the BZ19-6 buried hill. There are four kinds of strike faults developed on the buried hill: SN-, NNE-, NE–ENE-, and nearly EW-trending, which experienced the Mesozoic Indosinian, Yanshan, and Cenozoic Himalayan tectonic movements. During the Indosinian, the BZ19-6 was in a SN-oriented compressional setting, with active faults composed of SN-trending strike-slip faults (west branch of the Tanlu fault zone) and near EW-trending thrust faults (Zhang-peng fault zone). During the Yanshanian, the NNE-trending normal faults were formed under the WNW–ESE tensile stress field. Since the Himalayan period, the BZ19-6 buried hill has evolved into the rifting stage. In rifting stage Ⅰ, all of the multi-trend pre-existing faults were reactivated, and the EW-trending thrust faults became normal faults due to negative inversion. In rifting stage II, a large number of NE–ENE-trending normal faults were newly formed in the NW–SE-oriented extensional setting, which made the structure pattern more complicated. In rifting stage III, the buried hill entered the post-rift stage, with only part of the NNE- and NE–ENE-trending faults continuously active. Multi-trend faults are the result of the combination of various multi-phase stress fields and pre-existing structures, which have great influence on the formation of tectonic fractures and then control the distribution of high-quality reservoirs in buried hills. The fractures controlled by the NNE- and EW-trending faults have higher density and scale, and fractures controlled by NE–ENE trending faults have stronger connectivity and effectiveness. The superposition of multi-trend faults is the favorable distribution of high-quality reservoirs and the favorable accumulation area of hydrocarbon.

Digital twin-driven safety management and decision support approach for port operations and logistics - Kan Wang; Hang Xu; Hao Wang; Rui Qiu; Qianqian Hu; Xiaolei Liu (Frontiers in Marine Science, 2024)
Ports are of great significance in processing cargo containers and facilitating global marine logistics. Nevertheless, the susceptibility of the container shipping network for hazardous cargo is likely to intensify in the event of a significant disruption at a major port, such as adverse weather conditions, inadequate management practices, or unforeseen catastrophes. Such situations require the deployment of port protection emergency response and prevention in advance. This study proposes a digital twin (DT) model that employs extensive and trajectory data within containers to comprehensively analyze the occurrence of hazardous cargo failures within the port storage process. The virtual models of physical entities in the port are created through a data-driven approach, and the behavior of these entities in a port environment with big data is then simulated. A combination of a convolutional neural network (CNN) and a long short-term memory (LSTM) algorithm is employed to provide predictions for the service layer of the DT system. The predicted correlation coefficients of temperature and humidity in the container reach 0.9855 and 0.9181, respectively. The developed system driven by DT models integrated with a CNN and the LSTM algorithm can more effectively assist the safety manager in achieving prevention in port operations. This study enables marine authorities and decision-makers to optimize emergency procedures, thereby reducing the probability of accidents in port operations and logistics.

Combined Effects of Fishing and Environment on the Growth of Larimichthys polyactis in Coastal Regions of China - Zhuo Yin; Yun Xia; Chi Zhang; Rui Zhang; Dan Liu; Yang Liu (Fishes, 2024)
In fisheries’ stock assessments, the concept of “growth plasticity”—the ability of organisms to modulate their growth rates in response to environmental conditions—has gained attention in recent years. Historically, the impacts of fishing activities and environmental fluctuations were considered separately, while their combined effects have recently come into focus. This study collected 834 adult small yellow croakers (Larimichthys polyactis) from the northern Yellow Sea, the central Yellow Sea, the southern Yellow Sea, and the northern East Sea by trawling during 2020–2021. Using otolith increments as a proxy for annual somatic growth, the study reconstructed otolith chronologies during 2015–2020 for these four stocks. The results of the mixed-effects modeling suggested that temperature during spawning and previous overwintering seasons had comparable importance for the annual growth of small yellow croakers, with higher temperature promoting growth. The growth of small yellow croakers was also found to be correlated with ENSO events, with a lag of 1 to 2 years. A further investigation into combined effects revealed that higher fishing pressure might inhibit the small yellow croaker’s response to favorable environmental conditions. Furthermore, considering the potential differences in growth plasticity among stocks, an analysis was conducted on the spatial variations in growth response to these factors. The analysis revealed that, compared to the stocks in the Yellow Sea, the stock from the East China Sea could exhibit higher growth, superior adaptability to temperature, and a distinctive response to fishing pressure. In conclusion, the present study, while primarily focusing on temperature, preliminarily analyzed the combined effects of fishing and environment and underscored the differences in growth plasticity between stocks in the Yellow Sea and the East China Sea. Despite the limited factors analyzed in this study, it suggests a direction for future studies, highlighting the necessity to include more environmental factors, and even population factors (e.g., the biomass of preys), for a more comprehensive understanding of the combined effects. Based on the observed differences between the two potential subpopulations, this study also provides new insights for the management of the small yellow croaker based on metapopulation dynamics.

Tropical cyclone tracking from geostationary infrared satellite images using deep learning techniques - Chang-Jiang Zhang; Liu Zhang; Chen-Miao Rui; Lei-Ming Ma; Xiao-Qin Lu (International Journal of Remote Sensing, 2024)

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

Salinity-induced variations in bacterial composition and co-occurrence patterns within Salicornia-based constructed wetlands in mariculture - Xiaona Ma; Tangfang Zhai; Xinyuan Wang; Chen Cai; Denggao Qiu; Rui Yin; Jiayu Li; Gang Liu (Chemosphere, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

Extracellular-proton-transfer driving high energy-conserving methanogenesis in anaerobic digestion - Haoyu Liu; Ying Xu; Xinyu Li; Hong Wang; Rui Liu; Xiaohu Dai (Water Research, 2024)

Magnetic porous microspheres altering interfacial thermodynamics of sewage sludge to drive metabolic cooperation for efficient methanogenesis - Hui Geng; Ying Xu; Rui Liu; Jun Xu; Xiang Li; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Screening structure and predicting toxicity of pesticide adjuvants using molecular dynamics simulation and machine learning for minimizing environmental impacts - Zhenping Bao; Rui Liu; Yanling Wu; Songhao Zhang; Xuejun Zhang; Bo Zhou; Paul Luckham; Yuxia Gao; Chenhui Zhang; Fengpei Du (Science of The Total Environment, 2024)

Proteins in hydrothermal carbonization liquor of sewage sludge interfere with vivianite crystallization for phosphorus recovery - Yue Zhang; Xiaofan Yang; Xinran Zhang; Dezhi Sun; Xinyi Liu; Rui Lan; Min Zheng; Mark C.M. van Loosdrecht; Xiang Cheng (Resources, Conservation and Recycling, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Fracture stratigraphy in oil-rich shale of the Upper Xiaganchaigou Formation (upper Eocene), western Qaidam Basin - Rui Liu; Shuanglong Shi; Kunyu Wu; John N. Hooker; Guoyong Liu; Songtao Wu; Qinghui Zhang; Lu Xu; Guoxin Li; Xiucheng Tan (Marine and Petroleum Geology, 2024)

Construction of g-C3N4@Bi-MOF@BiOCl double Z-type heterojunctions for photodegradation of antibiotics under visible light irradiation: Mechanism, pathway, and toxicity assessment - Maoqin Xu; Rui Zhang; Jie He; Zixi Li; Yujie Liu; Dong Chen; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Water Process Engineering, 2024)

Renewable polybutene (2,5-furan dicarboxylate)-functional nanocomposites constructed from TiO2 nanowires: Expanding the photocatalytic degradation of antibiotics - Guannan Zhou; Lu Li; Shaowei Wu; Lixin Liu; Guangfeng Wu; Rui Wang; Guangyuan Zhou (Journal of Water Process Engineering, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Global sensitivity analysis of water level response to harmonic aquifer disturbances through a Monte-Carlo based surrogate model with random forest algorithm - Yixuan Xing; Quan Liu; Rui Hu; Hongbiao Gu; Reza Taherdangkoo; Thomas Ptak (Journal of Hydrology, 2024)

Construction of an S-scheme electron transfer channel in Cu0/CuFe2O4 magnetic plate column reactor for the LEV degradation: New strategy of visible Photo-Fenton system application - Rui Wang; Aiwen Wang; Yunhao Pan; Jiaxin Ni; Yingjie Deng; Zhe Tao; Xiongying Liang; Jingrui Tang; Xunming Tian; Tiancheng Zha; Dongmei Liu; Jun Ma (Journal of Hazardous Materials, 2024)

Farmland’s silent threat: Comprehensive multimedia assessment of micropollutants through non-targeted screening and targeted analysis in agricultural systems - Yang Qiu; Lijun Liu; Caifei Xu; Bo Zhao; Hang Lin; He Liu; Weixuan Xian; Han Yang; Rui Wang; Xingjian Yang (Journal of Hazardous Materials, 2024)

Energy and environmental evaluation and comparison of a diesel-electric hybrid tractor, a conventional tractor, and a hillside mini-tiller using the life cycle assessment method - Wei Liu; Rui Yang; Li Li; Chunjiang Zhao; Guanglin Li (Journal of Cleaner Production, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Anaerobic oxidation of methane and greigite formation: Evidence of isotopically heavy pyrite in Pleistocene coastal sediments from the South Yellow Sea - Xiaoxiao Yu; Xi Mei; Jianxing Liu; Baichuan Duan; Rui Zhang; Tiegang Li; Gangjian Wei; Mang Lin (Global and Planetary Change, 2024)

Zr-decorated hyper-cross-linked polymers for highly selective upgrading of furfural to furfuryl alcohol - Ying Qiu; Huiyu Liu; Rui Shan; Wei Zhao; Junhua Zhang; Jun Zhang; Haoran Yuan (Fuel, 2024)

TiO2 thermal stress deformation induced to promote photocatalytic CO2 reduction - Yixuan Shen; Kaifeng Gong; Le Chen; Jiafan Wang; Tao Wang; Yuan Gao; Jie Niu; Rui Zhu; Qizhen Liu; Jiang Wu; Ping He (Fuel, 2024)

Directional synthesis and application of long-chain ethers from biomass-derived carbonyls - Yuan Liu; Fang Liu; Li Yang; Feiqiang Guo; Shiliang Wu; Rui Xiao (Fuel, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

The study on green rapid synthesis of Cu-ZK-5 zeolite catalyst in NH3-SCR reaction - Qing Li; Yuchao Zang; Yanhua Wang; Caixia Liu; Qingling Liu; Rui Han; Ziyin Zhang (Fuel, 2024)

Enzymatically green-produced bacterial cellulose nanoparticle-stabilized Pickering emulsion for enhancing anthocyanin colorimetric performance of versatile films - Shiqi Li; Rong Liu; Jiale Zhao; Shuo Zhang; Xuerong Hu; Xingnan Wang; Zhenpeng Gao; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Chemistry, 2024)

Release dynamics, risk evolution and driving mechanisms of heavy metals in superalkaline fly ash co-disposed by MSW landfill - Zhaozhi Jia; Ya Xu; Rongbin Xu; Rui Xiang; Shuna Sun; Changxin Nai; Yuqiang Liu (Environmental Pollution, 2024)

Higher risk of spring frost under future climate change across China's apple planting regions - Renwei Chen; Jing Wang; Yang Li; Rui Bai; Mingxia Huang; Zhenzhen Zhang; Lingxuan Zhao; Zhenjiang Qu; Lu Liu (European Journal of Agronomy, 2024)

Maize and legume intercropping enhanced crop growth and soil carbon and nutrient cycling through regulating soil enzyme activities - Rui Liu; Lu Yang; Jiudong Zhang; Guopeng Zhou; Danna Chang; Qiang Chai; Weidong Cao (European Journal of Agronomy, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Efficient photocatalytic degradation of 24 imidazolium ionic liquids in an N-ZnO/simulated sunlight irradiation system and its mechanism - Jiaoqin Liu; Jingjing Zhang; Mengye Jia; Rui Ma; Ruijuan Qu; Zunyao Wang; Zhaoguo Liu; Yu Jiang; Haoxiang Zhang; Yujia Bai; Riya Jin; Yina Qiao; et al. (Chemical Engineering Journal, 2024)

Thermally-driven electrokinetic power generation system utilizing microporous NiO wicks and nanoporous AAO membranes for low-grade heat harvesting - Changzheng Li; Zhenquan Li; Tao Rui; Zheng Liu; Xiantao Zhang (Chemical Engineering Journal, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Photo-crosslinking modified gelatin-silk fibroin hydrogel for accelerating wound repair of open abdomen - Ye Liu; Sicheng Li; Jinjian Huang; Xuanheng Li; Ze Li; Canwen Chen; Guiwen Qu; Kang Chen; Yitian Teng; Rui Ma; Xiuwen Wu; Jianan Ren (Chemical Engineering Journal, 2024)

Unveiling the synergy of volatile fatty acids and ammonia nitrogen in optimizing methane production during dry anaerobic digestion of pig manure and corn straw - Zhuowu Li; Danni Li; Shenwei Cheng; Yingjun Ma; Fuyuan Liu; Xingliang Gao; Keqiang Zhang; Rui Liu; Jingquan Yang; Lianzhu Du (Chemical Engineering Journal, 2024)

Hydrogen bond regulation to promote the direct production of diosgenin from Dioscorea zingiberensis rhizomes - Yongxian Niu; Xi zhang; Wenbing Yu; Han Yin; Rui Lu; Zhenggang Liu; Fang Lu (Chemical Engineering Journal, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

A Janus textile mimics leaf stoma for dynamic thermal regulation through a shape memory coating - Yuanxiang Xiao; Rui Cai; Shuangfei Xiang; Shujun Zhao; Feiya Fu; Hongyan Diao; Xiangdong Liu (Chemical Engineering Journal, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

A triple-benefit strategy of microstructure, electronic property and active site modulation on ZnIn2S4 photocatalyst by Sn atom doping - Zhongtian Zeng; Liang Mao; Rui Zhang; Yanan Liu; Yihan Ling; Xiaoyan Cai; Junying Zhang (Chemical Engineering Journal, 2024)

Strategic design of magnetic ionic covalent organic frameworks incorporating amino acid ionic liquids for enhanced selectivity adsorption of benzimidazoles - Rui Chen; Xiaofeng Xue; Fengmao Liu; Dawei Zhen; Xuehui Chen (Chemical Engineering Journal, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

A fully degradable flexible membrane via green synthesis for highly effective separation of oil-water emulsions - Yunhao Pan; Tiancheng Zha; Xunming Tian; Liuqian An; Aiwen Wang; Rui Wang; Yibo Zhang; Jinxin Yao; Dongmei Liu; Shouzhu Li; Wei Wang (Chemical Engineering Journal, 2024)

Strategies, perspectives, and challenges of improving the initial coulombic efficiency and tap density of Sn-based anode materials for lithium-ion batteries - Hui Liu; Shuzhong Wang; Lu Liu; Junan Zhao; Wenjin Zhang; Rui Bao; Lijie Wang; Jianqiao Yang; Yanhui Li; Zefeng Jing (Chemical Engineering Journal, 2024)

Efficient degradation of sulfadiazine by UV-triggered electron transfer on oxalic acid-functionalized corn straw biochar for activating peroxyacetic acid: Performance, mechanism, and theoretical calculation - Chenyu Zeng; Yongfei Ma; Ping Li; Xi Chen; Hongtao Liu; Zhikang Deng; Rui Mu; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2024)

Progressive Freezing-Melting Method for Removal Boron from Simulated Seawater - Yihong Zou; Yan Zhang; Chen Zhao; Rui Mei; Lin Lin; Chunbo Liu; Yucan Liu; Yepeng Tian; Futian Chen (Water, Air, & Soil Pollution, 2024)

Mutations in wheat TaAPA2 gene result in pleiotropic effects on plant architecture - Shengsheng Bai; Guiping Wang; Rui Song; Yanna Liu; Lei Hua; Jinwei Yang; Lijun Zhang; Shams ur Rehman; Xiaohua Hao; Lifeng Hou; Chaozhong Zhang; Hongna Li; et al. (Science China Life Sciences, 2024)

OsSPL11 positively regulates grain size by activating the expression of GW5L in rice - Xinhai Zeng; Kai Fan; Yu Shi; Rui Chen; Wanyu Liu; Xin Wang; Guixiang Ye; Wenxiong Lin; Zhaowei Li (Plant Cell Reports, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

Correction: Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

Ceftriaxone Modulates Ubiquitination of α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid Receptors to Improve Long-Term Potentiation Impairment Induced by Exogenous β-Amyloid in a Glutamate Transporter-1 Dependent Manner - Rui Jiang; Li Li; Bu Wang; Lizhe Liu; Lirong Liu; Xiaohui Xian; Wenbin Li (Molecular Neurobiology, 2024)

Desmoglein-2 Affects Vascular Function in Moyamoya Disease by Interacting with MMP-9 and Influencing PI3K Signaling - Ajun Wang; Nan Li; Nan Zhang; Jian Liu; Tao Yang; Dongxue Li; Changwen Li; Rui Li; Tongcui Jiang; Chengyu Xia (Molecular Neurobiology, 2024)
The pathogenesis and development of Moyamoya disease are still unclear. This study aimed to investigate the effect of desmoglein-2 (DSG2) on Moyamoya disease and determine the inhibitory effect of DSG2 in vascular remodeling in Moyamoya disease. RNA sequencing, immunohistochemistry (IHC), and western blotting were used to detect the expression of DSG2 in the superficial temporal artery (STA) tissues of Moyamoya disease. The association between DSG2 and endothelial cells’ biological activities was investigated by cell counting kit-8 (CCK-8), migration assay, tube formation assay, flow cytometry with Annexin V-FITC/PI staining, and TUNEL apoptotic cell detection kit. Pathways affected by overexpression or knockdown of DSG2 were identified in endothelial cells. The expression of DSG2 in the STA tissues of Moyamoya disease was lower than that in normal controls. Overexpression of DSG2 inhibits the proliferation and migration but promotes apoptosis in endothelial cells, and low DSG2 levels result in impaired angiogenesis. In addition, there was an interaction between DSG2 and MMP-9, and DSG2 acted through the PI3K signaling in endothelial cells. Our results indicate that DSG2 affects PI3K signaling in vascular endothelial cells, and MMP-9 is involved in DSG2-mediated vascular changes in Moyamoya disease.

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

Changing Drip Fertigation Strategy to Decrease Greenhouse Agroecosystem Soil Nitrate Residue and Improve Tomato Production in Northwest of China - You Wu; Jiale Zhang; Shicheng Yan; Wei Si; Rui Liu; Jianhua Yang; Zhenxin Qiu; Junliang Fan; Fucang Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Migration characteristics of microplastics in riparian soils and groundwater - Dongdong Cheng; Huatai Liu; Weixu Qian; Rui Yao; Xinhong Wang (Environmental Monitoring and Assessment, 2024)

Adsorption/desorption of enrofloxacin in farmland soil as the effect of pH and coexisting ions: implications for enrofloxacin fate and risk in loess soil - Jiali Wu; Yufeng Jiang; Rui He; Zhewei Liu; Xiaozhen Zhang; Wenjing Wang; Weichen Kong; Gang Wang; Yingqin Wu (Environmental Geochemistry and Health, 2024)

Quantile delta-mapped spatial disaggregation analysis for summertime compound extremes over China - Rui Zhao; Xiong Zhou; Yongping Li; Jing Liu; Guohe Huang; Pangpang Gao (Climate Dynamics, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

Characterization and projection of spatial and temporal changes in habitat quality of Sanjiangyuan based on land use change - Rui Jiang; Jingfeng Liu (Journal of Geographical Sciences, 2024)

How territorial function determines CO2 emissions in China: An approach of spatial dimension - Jie Fan; Zheng Wang; Daojing Zhou; Rui Guo; Dong Chen; Baoyin Liu; Hanchu Liu; Qin Qiao; Jianxiong Wu (Journal of Geographical Sciences, 2024)

A new algorithm of critical control rod position search in MC code - Rui Li; Yuanguang Fu; Peng Liu; Dunfu Shi; Li Deng; Haibo Xu (Annals of Nuclear Energy, 2024)

Analyzing fishery data and exploring the resource status of Antarctic krill based on its environmental dependence - Rui Wang; Shigang Liu; Ran Zhang; Hai Li; Puqing Song; Yuan Li; Longshan Lin (Fisheries Oceanography, 2024)
Antarctic krill Euphausia superba is a key species in the Southern Ocean ecosystem and has important ecological value. It is also one of the main fishery resources in the Southern Ocean with high economic value. In recent years, with the development of krill fishery and rapid climate change, the conservation and management of krill resources have faced unprecedented challenges. The krill resource is different from the general fishery resources. Due to the krill schooling characteristics, fishery data has some advantages over scientific survey data. Reviewing and analyzing the krill fishery data is necessary. Therefore, in this study, four fishery resource indices (FRIs) were calculated based on Antarctic krill fishery data, and based on the environmental dependence of Antarctic krill, the FRI with the strongest environmental dependence was screened by using the Gradient Forest Model, and the step changes of the FRI with strongest environmental dependence was examined by using the sequential t‐test analyses of regime shifts (STARS). The generalized additive model (GAM) to analyze the correlation between the FRI with the strongest environmental dependence and the main environmental factors, and then explore the resource status of Antarctic krill in the study area. The model results showed that the “FRI_hual” had the strongest environmental dependence and was a better indicator of the status of the Antarctic krill in the study area than the others. In the 2009–2010 year, “FRI_hual” had an obvious regime shift. The interaction of environmental factors “ice_area_2” and “SSH_1” has a great impact on “FRI_hual”. Methods used and results obtained in the study can provide new ideas and a scientific reference for future work, including integrated stock assessment of krill and krill resource monitoring, conservation, and management based on the ecosystem.

Significantly underestimated traffic-related ammonia emissions in Chinese megacities: Evidence from satellite observations during COVID-19 lockdowns - Peilin Chen; Qin'geng Wang; Min Shao; Rui Liu (Chemosphere, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Full title: The performance evaluation of marine ecological civilization construction (MECC): A case study of coastal cities in Jiangsu Province, China - Yang Yang; Dingwu Liu; Rui Xu; Zhuona Li; Chenwei Shi; Xiaodong Zhu; Xiang Sun (Ocean & Coastal Management, 2024)

The BLV-miRNAs pathway of BLV inhibits the expression of Lactoferrin, Lactoperoxidase, Alpha-lactalbumin and Beta-lactoglobulin proteins - Shuai Lian; Han Zhang; Yandi Wang; Jiahe Song; Pengfei Liu; Zijian Geng; Rui Wu; Di Wang; Jianfa Wang (Veterinary Microbiology, 2024)

Integrated assessment of bioaerosol dispersion patterns and infection risk in a typical urban environment: Implications for urban biosecurity management - Zhijian Dong; Zhijian Liu; Chenxing Hu; Xuqiang Shao; Haokang Yang; Yongjun Jin; Rui Rong (Sustainable Cities and Society, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

Exploring the relationship between land use change patterns and variation in environmental factors within urban agglomeration - Rui Xiao; Hanyu Yin; Ruoxin Liu; Zhonghao Zhang; Sukhbaatar Chinzorig; Kun Qin; Wenfang Tan; Yi Wan; Zhi Gao; Chen Xu; Lumeng Liu; Tao Jia (Sustainable Cities and Society, 2024)

In situ real-time pathway to study the polyethylene long-term degradation process by a marine fungus through confocal Raman quantitative imaging - Wanying He; Rui Liu; Fan Fei; Shichuan Xi; Zengfeng Du; Zhendong Luan; Chaomin Sun; Xin Zhang (Science of The Total Environment, 2024)

Multi-medium residues and ecological risk of herbicides in a typical agricultural watershed of the Mollisols region, Northeast China - Hanqiang Liu; Rui Li; Wenyou Hu; Le Jian; Biao Huang; Ya'nan Fan; Yongcun Zhao; Hongyan Zhang; Khalid Saifullah Khan (Science of The Total Environment, 2024)

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

An emerging antibacterial nanovaccine for enhanced chemotherapy by selectively eliminating tumor-colonizing bacteria - Linfu Chen; Zheyu Kang; Jingjing Shen; Rui Zhao; Yu Miao; Lin Zhang; Zixuan Zheng; Zhemin Zhang; Nanhui Liu; Cheng Wang; Huapan Fang; Jun Zhou; et al. (Science Bulletin, 2024)

Zircon U–Pb geochronology and geochemistry of Paleoproterozoic quartz monzonite in the Northern Yangtze Craton: Petrogenesis and geological implications - Wen-Xiang Zhang; Rui Li; Guang-Yan Zhou; Zhi-Fu Liu; Yuan-Bao Wu (Precambrian Research, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Identification and detection of the V1848I indoxacarb resistance mutation in the beet armyworm, Spodoptera exigua - Xianxia Zhang; Ruiming Zhang; Mengqi Yu; Rui Liu; Naijing Liu; Haiyuan Teng; Yakun Pei; Zhaonong Hu; Yayun Zuo (Pesticide Biochemistry and Physiology, 2024)

Evaluating the necessity of autumn irrigation on salinized soil by considering changes in soil physicochemical properties - Hang ZHAO; Jingwei WU; Changsen LI; Yawen LIU; Rui ZHANG; Qiang ZHAO (Pedosphere, 2024)

First complete Niobe yangtzeensis Lu, 1975 (Asaphidae, Trilobita) from the Middle Ordovician of South China, and its systematic and palaeogeographic implications - Xiao-Qi Du; Yi-Long Liu; Rui-Wen Zong (Palaeoworld, 2024)

Feasibility of nanofiltration process for efficient separation of gallic acid from the extract of black tea in aqueous solution - Yiwei Dong; Rui Zhao; Chunyan Xu; Jinxin Liu; Zhiguo Dong; Ziqi Chen; Jinfeng He; Chuanrun Li; Haiyang Yan; Li Sun (Journal of Water Process Engineering, 2024)

The effects and mechanisms of heat stress on mammalian oocyte and embryo development - L.I. Lang; Zhen-zhen Wang; Bin Liu; S.H.E.N. Chang-qing; T.U. Jing-yi; W.A.N.G. Shi-cheng; L.E.I. Rui-ling; P.E.N.G. Si-qi; X.I.A.O. Xiong; Z.H.A.O. Yong-ju; Xiao-yan Qiu (Journal of Thermal Biology, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Compositional analysis and quantitative evaluation of organic emissions from asphalt materials: Improvements and refinements - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Huailei Cheng; Jia Liu; Rui Li (Journal of Cleaner Production, 2024)

Optimization of ecological network function and structure by coupling spatial operators and biomimetic intelligent algorithm - Zhaomin Tong; Ziyi Zhang; Yanchi Lu; Yaolin Liu; Rui An; Xuan Luo; Sui Liu; Bin Zhang (Journal of Cleaner Production, 2024)

Exploring the spatial patterns of landslide susceptibility assessment using interpretable Shapley method: Mechanisms of landslide formation in the Sichuan-Tibet region - Jichao Lv; Rui Zhang; Age Shama; Ruikai Hong; Xu He; Renzhe Wu; Xin Bao; Guoxiang Liu (Journal of Environmental Management, 2024)

Mechanism study of synergistic aluminum extraction and purification by ammonium for high-value conversion of secondary aluminum dross - Wen Deng; Qinglin Xie; Rui Zhou; Haorui Tuo; Xueming Liu; Hong Deng; Zhang Lin (Journal of Environmental Chemical Engineering, 2024)

A novel, green, and environmentally friendly PBS/nano-CaCO3 hybrid membrane - Ming Jing; Yanhong Ji; Liuchun Zheng; Xi Liu; Zunbo Han; Jiayi Cai; Rui Bai; Benqiao He (Journal of Environmental Chemical Engineering, 2024)

Enhanced capacitive deionization for Cr(VI) removal from electroplating wastewater: Efficacy, mechanisms, and high-voltage flow electrodes - Rui Zhou; Jingyang Li; Yunbo Dai; Fangyuan Liu; Shuzheng Yang; Hejun Ren; Chunpeng Zhang (Journal of Environmental Chemical Engineering, 2024)

Artificial phytoremediation solar interface evaporator for efficient heavy metal salt separation and saline soil remediation - Yaping Xu; Chenyang Dang; Xiangkun Elvis Cao; Yunteng Cao; Jiu Huang; Yuxiang Xu; Minghui Shan; Rui Liu; Peng Li; Guiyin Xu; Meifang Zhu (Journal of Environmental Chemical Engineering, 2024)

Ultra-high capacity and anti-interference for Cr(VI) removal by tannin-polyvinylimine modified graphite carbon nitride - Wen Sun; Rui Wang; Lingfei Li; Jun Zhao; Bianhua Liu (Journal of Environmental Chemical Engineering, 2024)

Energy control and block performance optimization of bench blasting - Ming Tao; Yuanquan Xu; Rui Zhao; Yulong Liu; Chengqing Wu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Impact-dispersed Fe–Fe1−S core–shell particles in Chang’e-5 lunar soil impact glass - Chen Li; Yang Li; Kuixian Wei; Zhuang Guo; Rui Li; Xiongyao Li; Jianzhong Liu; Wenhui Ma (Geochimica et Cosmochimica Acta, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Demineralization effects on physicochemical and combustion characteristics of biomass: Insights into distributed kinetics, flue gas evolution, and slag formation - Peiyong Ma; Bowen Li; Rui Diao; Xiaohao Liu; Zhusong Cheng; Fenglei Qi (Fuel, 2024)

Pilot-tests of the coal-fired power plant indirect coupling with multi-source organic solid waste incineration technology - Rui Zhang; Jun Cao; Ling Lei; Yufei Cao; Dong Liu (Fuel, 2024)

Exploring the neural correlates of fat taste perception and discrimination: Insights from electroencephalogram analysis - Tianyi Yang; Peng Zhang; Jin Hu; Wei Xu; Wei Jiang; Rui Feng; Yajun Lou; Xiaofei Jin; Zhiyu Qian; Fan Gao; Keqiang Gao; Rui Liu; et al. (Food Chemistry, 2024)

Fluorescent solid-state strips based on SiO2 shell-stabilized perovskite nanocrystals applying for magnetic aptasensing detection of aflatoxin B1 toxin in food - Mingfei Pan; Xiaochun Hu; Rui Gao; Boxi Zhou; Jingming Sun; Dan Zhang; Xuan Liu; Yixin Wang; Shuo Wang (Food Chemistry, 2024)

Highly selective and sensitive immunoassays for flurogestone acetate analysis in goat milk: From rational hapten design and antibody production to assay development - Rui Liu; Xingya Sun; Yingjie Zhang; Peipei Li; Li Nan; Qing Shen; Kai Wen; Xuezhi Yu; Jianzhong Shen; Yantong Pan; Zhanhui Wang (Food Chemistry, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Probiotics encapsulated by gelatin and hyaluronic acid via layer-by-layer assembly technology for enhanced viability - Leran Wang; Xinyi Zhong; Shiqi Li; Xiaoshuang Liu; Kai Wang; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Hydrocolloids, 2024)

Synergistic impact of various straw-return methods and irrigation regimes on winter wheat physiological growth and yield - Fuying Liu; Mingliang Gao; Haoze Zhang; Huabin Yuan; Bin Hu; Rui Zong; Mingming Zhang; Yuzhao Ma; Quanqi Li (Field Crops Research, 2024)

Assessment of microorganisms in drinking water disinfected by catalytic ozonation with fluorinated ceramic honeycomb and NaClO disinfectants under laboratory and pilot conditions - Wei Lan; Jian Pan; Haiyang Liu; Rui Weng; Yaxiong Zeng; Lili Jin; Qiucheng Shi; Yunsong Yu; Baohong Guan; Yan Jiang (Environmental Pollution, 2024)

Silica's silent threat: Contributing to skin fibrosis in systemic sclerosis by targeting the HDAC4/Smad2/3 pathway - Bingsi Tang; Yaqian Shi; Zhuotong Zeng; Xinglan He; Jiangfan Yu; Ke Chai; Jiani Liu; Licong Liu; Yi Zhan; Xiangning Qiu; Rui Tang; Yangfan Xiao; et al. (Environmental Pollution, 2024)

A computationally affordable and reasonably accurate approach for annual outdoor thermal comfort assessment on an hourly basis - Rui Sun; Dayi Lai; Wei Liu (Energy and Buildings, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Molecular-level insight into the origin-dependent adsorption fractionation of dissolved organic matter on ferrihydrite in aquatic environment: Implications for carbon sink in eutrophic lakes - Chengyu Suo; Wensi Zhao; Shasha Liu; Rui Fu; Yi Ren; Yue Qiu; Yuxin Zhang; Zhongqi He; Baoshan Xing; Fengchang Wu (Chemical Engineering Journal, 2024)

Promotion and monitor wound healing by anthocyanin enhanced light curing ε-poly-l-lysine hydrogel encapsulated Cu-MOF - Xiawei Zhao; Rui Liu; Tiantian Tang; Zihao Liu; Xiaozhi Liu; Kai Yu; Ye Zhang; Hao Wang (Chemical Engineering Journal, 2024)

Nitrate-promoted gas–solid reactions of H2 and CaCO3 for mid-temperature integrated CO2 capture and methanation - Lifei Wei; Rui Han; Mingke Peng; Zhiyong Li; Caidong Zhang; Qingling Liu (Chemical Engineering Journal, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Manganese oxides/graphene aerogels as lightweight microwave absorbers for extreme environment application - Jieping Wang; Shaohua Shi; Yongzhu Yan; Gengping Wan; Haoxiang Zhai; Xiang Yuan; Liang Li; Changlong Du; Rui Liu; Guizhen Wang (Chemical Engineering Journal, 2024)

Removal of artificial sweeteners in wastewater treatment plants and their degradation during sewage sludge composting with micro- and nano-sized kaolin - Jishao Jiang; Rui Hou; Huilin Cui; Zhuyu Tang; Yousif Abdelrahman Yousif Abdellah; Caspar C.C. Chater; Ke Cheng; Fuqiang Yu; Dong Liu (Bioresource Technology, 2024)

Interfacial exchange of airflow and bacteria-carrying particles induced by door opening and foot traffic in an operating room - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong (Building and Environment, 2024)

Unlocking energy and economic benefits of integrated green envelopes in office building retrofits - Rui Guo; Yunran Min; Yafeng Gao; Xiangjie Chen; Huizhong Shi; Changqiao Liu; Chaoqun Zhuang (Building and Environment, 2024)

The potential regulatory role of the non-coding RNAs in regulating the exogenous estrogen-induced feminization in Takifugu rubripes gonad - Xufang Shen; Hongwei Yan; Mingtao Hu; Huiting Zhou; Jia Wang; Rui Gao; Qi Liu; Xiuli Wang; Ying Liu (Aquatic Toxicology, 2024)

Environmentally relevant estrogens impaired spermatogenesis and sexual behaviors in male and female zebrafish - Mei-Ling Tan; Yan-Jun Shen; Qi-Liang Chen; Feng-Rui Wu; Zhi-Hao Liu (Aquatic Toxicology, 2024)

Adsorption retention of spiramycin in agricultural calcareous loess soils: Assessing the impact of influential factors and mechanisms - Zhewei Liu; Yufeng Jiang; Rui He; Jiali Wu; Xiaozhen Zhang; Kui Huang; Yingqin Wu (Water, Air, & Soil Pollution, 2024)

Nitrogen transformations in plastic-film mulched soils - Hao Zhang; Zihao Zhang; Zhe Liu; Tingting Lei; Jinbo Zhang; Christoph Müller; Abeer S. Aloufi; Ekaterina Filimonenko; Yakov Kuzyakov; Rui Jiang (Plant and Soil, 2024)

Identification of key genes involved in lignin and flavonoid accumulation during Tilia tuan seed maturation - Lei Liu; Cui Long; Xuri Hao; Rui Zhang; Chenqi Li; Yuepeng Song (Plant Cell Reports, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Methylene Blue Pretreatment Protects Against Repeated Neonatal Isoflurane Exposure-Induced Brain Injury and Memory Loss - Chongyun Wu; Qianting Deng; Ling Zhu; Timon Cheng-yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2024)

Computational biology-based study of the molecular mechanism of spermidine amelioration of acute pancreatitis - Yan Shen; Hongtao Duan; Lu Yuan; Aiminuer Asikaer; Yiyuan Liu; Rui Zhang; Yang Liu; Yuanqiang Wang; Zhihua Lin (Molecular Diversity, 2024)

Analysis of the impact of terrain factors and data fusion methods on uncertainty in intelligent landslide detection - Rui Zhang; Jichao Lv; Yunjie Yang; Tianyu Wang; Guoxiang Liu (Landslides, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

LncRNA MIR4697HG Alleviates Endothelial Cell Injury and Atherosclerosis Progression in Mice via the FUS/ANXA5 Axis - Xue Liu; Rui Huang; Jiye Wan; Tiesheng Niu (Biochemical Genetics, 2024)

Projected changes in wind erosion climatic erosivity over high mountain Asia: results from dynamical downscaling outputs - Rui Mao; Yuanyuan Xu; Jianze Zhu; Xuezhen Zhang; Shuaifeng Song; Dao-Yi Gong; Lianyou Liu; Peijun Shi (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Targeting gut microbiota for immunotherapy of diseases - Ya-Jie Yu; Xiao-Dong Liu; Cai Liao; Rui Yu; Xin Wang; Ming Li; Yun Wang (Archives of Toxicology, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

A review of distribution and functions of extracellular DNA in the environment and wastewater treatment systems - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Bo Zhang (Chemosphere, 2024)

An approach for multi-depth soil moisture prediction in alfalfa based on a dual-branch combined model - Rui Liu; Lifeng Lu; Yongqi Ge; Liguo Dong; Juan Zhou (Computers and Electronics in Agriculture, 2024)

Riemann–Hilbert approach for the inhomogeneous discrete nonlinear Schrödinger equation with nonzero boundary conditions - Ya-Hui Liu; Rui Guo; Jian-Wen Zhang (Wave Motion, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Incorporating historical information into the multi-type ant colony optimization model to optimize patch-level land use allocation - Zhaomin Tong; Yaolin Liu; Ziyi Zhang; Bowen Pang; Rui An; Yanchi Lu; Bin Zhang; Haofeng Wang (Sustainable Cities and Society, 2024)

Stackelberg game-based method towards carbon-economy equilibrium for the prefabricated construction supply planning: A case study from China - Mengyuan Zhu; Yu Wang; Rui Liu; Lurong Fan (Sustainable Cities and Society, 2024)

Seasonal anthropogenic heat fluxes over 200 cities in China: An investigation of driving factors with three-dimensional building forms - Meizi Yang; Shisong Cao; Dayu Zhang; Rui Liu; Ling Cui; Yile Cai (Sustainable Cities and Society, 2024)

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Biodegradable film mulching increases soil microbial network complexity and decreases nitrogen-cycling gene abundance - Hao Zhang; Duntao Shu; Jiaqi Zhang; Xuejun Liu; Kai Wang; Rui Jiang (Science of The Total Environment, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

The cellular response and molecular mechanism of superoxide dismutase interacting with superparamagnetic iron oxide nanoparticles - Hao Ju; Yue Liu; Yameng Wang; Rui Lu; Bin Yang; Deyi Wang; Jing Wang (NanoImpact, 2024)

Synergistic inhibition of polyaspartic acid and D-glutamic acid on carbon steel corrosion in acidic environments - Yutong Li; Shichu Gong; Rui Zhang; Xiangmei Liu; Shuguang Wang; Xiaohan Zhang; Chao Song (Journal of Water Process Engineering, 2024)

The non-linear associations between blood manganese level and sarcopenia in patients undergoing maintenance hemodialysis: A multicenter cross-sectional study - Rui Hu; Qiangying Zeng; Qingdong Xu; Hongmei Zhou; Rongshao Tan; Xiaoshi Zhong; Yan Liu; Yi Li; Yun Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

Wastewater surveillance together with metaviromic data revealed the unusual resurgence of infectious diseases after the first wave of the COVID-19 outbreak - Ziqiang Zhang; Fenglan He; Liu Yi; Zhiqiang Deng; Rui Wang; Lixin Shen; Songzhe Fu (Journal of Hazardous Materials, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Transformation of metoprolol in UV/PDS process: Role and mechanisms of degradation and polymerization - Sui-Qin Yang; Rui-Qiu Ye; Yu-Hong Cui; Zheng-Qian Liu; Kai Sun; Yu-Ze Yu (Journal of Hazardous Materials, 2024)

Development and characterization of a bacterial enzyme cascade reaction system for efficient and stable PET degradation - Chengyong Wang; Rui Long; Xiran Lin; Wei Liu; Liying Zhu; Ling Jiang (Journal of Hazardous Materials, 2024)

Geological study of an outburst flood event in the upper Yangtze River and risk of similar extreme events - Gang Hu; Guanghui Dong; Tao Liu; Rui Min; Zhijian Yang; Qihui Gao; Huiying Wang; Ping Wang; Jie Chen; Jiafu Zhang; Changsong Wang; Chaoying Zhao; et al. (Global and Planetary Change, 2024)

Study on the influence of a single fracture on the performance of backfill heat exchangers in underground stopes - Bo Zhang; Wenxuan Zhang; Rui Zhan; Lang Liu; Chao Huan; Yujiao Zhao; Xiaoyan Zhang (Geothermics, 2024)

Hydrogen-donating behavior and hydrogen-shuttling mechanism of liquefaction solvents under Fe- and Ni-based catalysts - Haiyun Liu; Rui Zhang; Xin Zheng; Jing Xie; Bowen Tang; Zhi Li; Erguang Guo; Haoquan Hu; Lijun Jin (Fuel, 2024)

Enhancement effects and mechanisms of iron filings on the performance of anaerobic co-digestion of hulless barley straw and pig manure - Rui Han; Bingyu Ning; Li Liu; Yi Li (Fuel, 2024)

Carboxymethylcellulose-induced depletion attraction to stabilize high internal phase Pickering emulsions for the elderly: 3D printing and β-carotene delivery - Jingjie Hou; Guixin Tan; Afeng Wei; Shan Gao; Huajiang Zhang; Wentao Zhang; Yujia Liu; Rui Zhao; Yunze Ma (Food Chemistry, 2024)

Electrochemiluminescence detection of diazinon in vegetables based on the synergistic interaction of WO3-x dots with Au@SiO2 nanocapsules - Wenzheng Liu; Haifang Wang; Peisen Li; Chengqiang Li; Donghan Li; Zhenying He; Yuhao Zhang; Jingcheng Huang; Jin Hua; Rui Xu; Lianming Xia; Yemin Guo; et al. (Food Chemistry, 2024)

Direct infusion–multiple reaction monitoring cubed (DI–MRM3) enables widely targeted bi-omics of Colla Corii Asini (Chinese name: Ejiao) - Ting Li; Ke Zhang; Rui Liu; Luyao Ren; Xiaoyun Li; Jun Li; Wenjing Liu; Yuelin Song (Food Chemistry, 2024)

Inoculation fermentation with Lactobacillus fermentum L28 and Staphylococcus epidermidis S24 for improving the protein degradation of air-dried goose - Mangang Wu; Chen Gu; Likun Duan; Peipei Yin; Tianhao Zhu; Yuyu Xu; Qing Yin; Rui Liu; Qingfeng Ge; Hai Yu (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Destabilization of a model O/W/O double emulsion: From bulk to interface - Zijian Zhi; Hao Li; Indi Geurs; Benny Lewille; Rui Liu; Paul Van der Meeren; Koen Dewettinck; Filip van Bockstaele (Food Chemistry, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

The role of hormones in the regulation of lactogenic immunity in porcine and bovine species - Kexin Hua; Dan Liu; Qianshuai Xu; Yuna Peng; Yu Sun; Rongrong He; Rui Luo; Hui Jin (Domestic Animal Endocrinology, 2024)

Dynamic analysis of unsaturated porous media under moving loads by the time domain FEM using moving coordinates - Yanfei Pei; Qian Su; Rui Su; Kaiwen Liu; David P. Connolly; Tengfei Wang (Computers and Geotechnics, 2024)

Multi-source monitoring data filtering assisted deformation analysis model updating of ultra-high rockfill dam - Zhitao Ai; Gang Ma; Guike Zhang; Rui Liu; Shaohui Deng; Xiaolin Chang; Wei Zhou (Computers and Geotechnics, 2024)

Performance modeling and running strategy of parallel cdugksFOAM program - Yunlan Wang; Yufeng Liu; Rui Zhang; Tianhai Zhao; Sha Liu; Congshan Zhuo; Chengwen Zhong (Computer Physics Communications, 2024)

Super Fe3+ competing ability, high biocompatibility, and mild antibacterial carbon dots for food preservation - Fangchao Cui; Rongsen Fan; Dangfeng Wang; Likun Ren; Qianqian Wang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

CaO/SiC alkaline fillers for High-Temperature reduction of mercury (II) - Haiyang Li; Lina Sun; Xiaoshuo Liu; Jiangyi Tong; Yuxing Zhou; Rui Jin; Yufeng Duan; Haitao Hu (Chemical Engineering Journal, 2024)

Boosting peroxymonosulfate activation over partial Zn-substituted Co3O4 for florfenicol degradation: Insights into catalytic performance, degradation mechanism and routes - Xinyang Wang; Xinyu Luo; Rui Li; Yu Chang; Jianbiao Peng; Weilai Wang; Haijin Liu; Guangxuan Yan; Pengkun Wei; Zhiguo Cao (Chemical Engineering Journal, 2024)

A novel two-stage continuous capacitive deionization system with connected flow electrode and freestanding electrode - Rui Chen; Xun Liu; Mengxia Wang; Yufei Shu; Meng Zhang; Bei Liu; Zhongying Wang (Chemical Engineering Journal, 2024)

Deciphering the stability mechanism of Pt-Ni/Al2O3 catalysts in syngas production via DRM - Rui Zhao; Kun Cao; Rongli Ye; Yuanting Tang; Chun Du; Fudong Liu; Yunkun Zhao; Rong Chen; Bin Shan (Chemical Engineering Journal, 2024)

Efficient nitrogen removal from mainstream sewage in tidal flow constructed wetlands: Targeted migration and conducive spatial distribution for pollutants removal - Rui Ma; Caocong Liu; Yiyuan Zhuo; Jiangsen Ma; Linsong Cheng; Fangying Ji; Xiaoming Wang (Chemical Engineering Journal, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Toxic Metal Soil Speciation, Corn Accumulation and Health Risk Assessment in Acidic red soil Farmland in Mineral Industry Area - Yu Qian; Xiaoqi Li; Jie Yang; Rui Zhou; Zijin Hong; Change Liu; Shiyu Li; Yonggui Zhao; Denggao Fu; Ying Pan; Huan Feng; Marek Kolenčík; et al. (Water, Air, & Soil Pollution, 2024)

Roundup® induces premature senescence of mouse granulosa cells via mitochondrial ROS-triggered NLRP3 inflammasome activation - Heliang Ni; Xiangdong Hu; Nannan Yang; Xiaoyang Liu; Wenyang Cai; Rui Zhong; Tiancheng Wang; Mingxi Yu; Shuang Tang (Toxicological Research, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

BODIPY Based OFF-ON Fluorescent Probe for Endogenous Carbon Monoxide Imaging in Living Cells - Lei Zhao; Rui Chen; Cheng Jia; Jiandong Liu; Guohua Liu; Tanyu Cheng (Journal of Fluorescence, 2024)

Comparative analysis of micro-physical characteristics of sprayed droplets using various measurement technologies - Rui Zhang; Yichuan Liu; Delan Zhu; Pute Wu; Wenbo Xia; Changjuan Zheng; Xiaomin Zhang (Irrigation Science, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Diclofenac sodium effectively inhibits the biofilm formation of Staphylococcus epidermidis - Huimin Xi; Zhaoxia Luo; Mei-fang Liu; Qiang Chen; Qing Zhu; Lei yuan; Yi-yun Sheng; Rui Zhao (Archives of Microbiology, 2024)

Invalidation of geraniin as a potential inhibitor against SARS-CoV-2 main protease - Rui Zhang; Haohao Yan; Jiahao Zhou; Xiaoping Liu; Yunyu Chen (Natural Product Research, 2024)

An application of hierarchical MgAl hydrotalcite in the highly efficient treatment of oilfield macromolecular contaminants - Chenye Yang; Qi Liu; Tao Li; Rui Zhou; Chengtun Qu; Ying Tang (Environmental Science and Pollution Research, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Spatiotemporal coda Q variations in the northeastern margin of the Qinghai–Tibet Plateau, China - Zhaocheng Liang; Xiao Guo; Rui Zou; Xuzhou Liu; Manzhong Qin; Shaohua Li (Journal of Earth System Science, 2024)

YOLOv5-T: A precise real-time detection method for maize tassels based on UAV low altitude remote sensing images - Rui Gao; Yishu Jin; Xin Tian; Zheng Ma; Siqi Liu; Zhongbin Su (Computers and Electronics in Agriculture, 2024)

Effects of pH-varying thermal modification on sewage sludge: A focus on releasing nitrogen- and phosphorus-containing substances - Rui Liu; Ying Xu; Jiachang Cao; Hui Geng; Renjie Chen; Haoyu Liu; Yongdong Chen; Shijie Yuan; Xiaohu Dai (Water Research, 2024)

Sediment resuspension as a driving force for organic carbon transference and rebalance in marginal seas - Xiaoqing Liu; Chunyuan Lan; Longhai Zhu; Caiqing Yan; Nan Wang; Haibiao Chen; Guangjin Zheng; Yangli Che; Zuosheng Yang; Rui Bao (Water Research, 2024)

Soil erosion is a major drive for nano & micro-plastics to enter riverine systems from cultivated land - Yanting Wang; Siyuan Jing; Peiyu Hou; Rui Ni; Lili Niu; Thomas Cherico Wanger; Weiping Liu; Kai Liu (Water Research, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Reduction of heavy metals in municipal solid waste incineration fly ash followed by making transparent glass - Hanlin Shen; Bingjie Lou; Bo Liu; Junjie Zhang; Xiaoyan Zhang; Jun Liu; Rui Zhang; Mingcui Chen; Shengen Zhang (Waste Management, 2024)

Thermal parameter identification of concrete dams based on hybrid particle swarm optimization using distributed optical fiber monitoring data - Chi Zhao; Feng Wang; Xinxin Jiang; Rui Song; Ao Zhang; Xueli Liu (Swarm and Evolutionary Computation, 2024)

Corrigendum to “Polycyclic aromatic hydrocarbon (PAH)-containing soils from coal gangue stacking areas contribute to epithelial to mesenchymal transition (EMT) modulation on cancer cell metastasis” [Sci. Total Environ. 580 (2017) 632–640] - Yang Yun; Rui Gao; Huifeng Yue; Xiaofang Liu; Guangke Li; Nan Sang (Science of The Total Environment, 2024)

Tracing the impacts of ecological water replenishment on the sources and transformation of groundwater nitrate through isotope and microbial analysis - Congchao Xu; Bowen Shi; Zihao Jia; Di Liu; Weiwu Hu; Chuanping Feng; Rui Li (Science of The Total Environment, 2024)

In situ profiling reveals spatially metabolic injury in the initiation of polystyrene nanoplastic-derived intestinal epithelial injury in mice - Xianan Zhang; Jing Wang; Yuansheng Liu; Hemin Wang; Bin Li; Qing Li; Yi Wang; Yuru Zong; Jiajia Wang; Qingtao Meng; Shenshen Wu; Rongzhang Hao; et al. (Science of The Total Environment, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

A new Late Devonian plant assemblage in West Junggar, Xinjiang, China and its floral evolution during the Devonian - Bing-Cai Liu; Kai Wang; Rui-Wen Zong; Jiao Bai; Yao Wang; Ning Yang; Yi Wang; Hong-He Xu (Review of Palaeobotany and Palynology, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Enhancing long-term river water quality prediction: Construction and validation of an improved hybrid model - Yadan Yu; Yangwu Chen; Shunbo Huang; Rui Wang; Houzhen Zhou; Chuankun Liu; Wei Wang; Zhouliang Tan (Process Safety and Environmental Protection, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Number of denatured rigor cross-bridges determines the intracellular volume shrinkage in porcine muscle fibre under PSE-inducing condition - Cong Yin; Siyang Wu; Nan Yang; Tingyang Ai; Jiawei Wan; Qin Rui; Hong Liu; Hairong Xiong; Jiao Liu (Meat Science, 2024)

Flow-through inactivation of pathogenic Escherichia coli by titanium suboxide reactive electrochemical membranes: Unlocking the coupled mechanics of electrochemical and subcellular alterations - Zimeng Zhang; Chunpeng Zhang; Lin Zhu; Ying Liu; Rui Wei; Aijie Wang (Journal of Water Process Engineering, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

A biotechnological approach for suspended solids removal in biogas slurry via microbially induced calcite precipitation (MICP) - Rui Wang; Chao-Sheng Tang; Xiaohua Pan; Zhengtao Shen; Yujia Liu; Xiancai Lu (Journal of Cleaner Production, 2024)

Response of different plants to ecological floating bed-microbial fuel cells: Decontamination and power generation - Liangjing Zhang; Peng Lv; Yu Wang; Shucong Lv; Yunlong Liu; Rui Wang; Lusan Liu (Journal of Cleaner Production, 2024)

Carbon performance analysis of upgraded wastewater treatment plants in key control areas of the Ziya River Basin in China - Jiahao Liu; Zhongqian Wang; Tonggang Zhang; Rui Liu; Weiguang He; Xiangye Kong; Yaolong Shi; Jianfeng Xie (Journal of Environmental Management, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

Critical factors in soil organic carbon mineralization induced by drying, wetting and wet-dry cycles in a typical watershed of Loess Plateau - Yi Zhang; Xiaojun Liu; Peng Li; Lie Xiao; Shixuan Zhou; Xing Wang; Rui Wang (Journal of Environmental Management, 2024)

Ammonium addition reduces phosphorus leaching in a long-term mineral or organic fertilized calcareous soil during flooding conditions - Lulu Wei; Yan Zhou; Guiming Yin; Jianyu Cui; Junhui Yin; Rui Liu; Qing Chen; Shuai Zhang (Journal of Environmental Management, 2024)

Multifunctional BiOBr/BiOI 3D microspheres for improving visible-light-driven photocatalytic degradation and disinfection efficiency - Saifeng Zhang; Jian Guo; Saisai Deng; Rui Zhang; Qiuyu Zhu; Yuanxu Liu; Xiangang Lin; Yangyang Li (Journal of Environmental Chemical Engineering, 2024)

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

Facet effect on nanosheet Co3O4 catalysts for toluene oxidation: Decisive role of Co3+ and reaction-induced oxygen vacancy - Rui Liu; Yuting Chu; Yiming Li; Kaijie Li; Tong Li; Hongbo Yu; Rui Liang; Yipei Chen; Tao Wu; Hongfeng Yin (Journal of Environmental Chemical Engineering, 2024)

MgO-modified biochar for the removal of dissolved humus from water and its potential application as a fertilizer - Tao Liu; Jinqi Zhu; Tingwei Rui; Hongyi Sun; Ningxin Wang; Lijie Pu (Journal of Environmental Chemical Engineering, 2024)

MOF derived highly dispersed bimetallic Fe-Ni nitrogen-doped carbon for enhanced peroxymonosulfate activation and tetracycline degradation - Lingyun Jing; Shasha Liu; Tong Wang; Zeqiang Zhang; Xia Zhao; Zhili Sun; Pengbo Hao; Yeqiang Hu; Wenhan Yang; Rui Quan; Xinyong Li; Dongnian Zhang; et al. (Journal of Environmental Chemical Engineering, 2024)

Purification, characterisation and visualisation of soybean protein hydrolysis by aspergillopepsin I from mangrove Aspergillus tubingensis - Hongli Yao; Shuangping Liu; Rui Chang; Tiantian Liu; Dongna Ma; Xiao Han; Congyu Lin; Zhilei Zhou; Jian Mao (International Biodeterioration & Biodegradation, 2024)

Methane emissions from the natural gas industry in China – A systematically accounting based on the bottom-up approach - Nu Li; Jianliang Wang; Rui Liu; Hongxun Huang; Jakob Willerström; Mikael Höök (Gas Science and Engineering, 2024)

Culturing the uncultured marine fungi in the omics age: Opportunities and challenges - Zhi-Feng Zhang; Fang Liu; Li-Rui Liu; Meng Li; Lei Cai; Shuangping Liu; Jian Mao (Fungal Biology Reviews, 2024)

Synergistic multifactor influence and management of commercial vanadium-based catalyst lifetimes - Yi-feng Xu; Xiao-jing Liu; Rui-tang Guo; Tong Wu; Hong-lei Ding; Dong Ye; Wei-guo Pan (Fuel, 2024)

High-pressure microfluidization enhanced the stability of sodium caseinate-EGCG complex-stabilized fish oil emulsion - Wei Tang; Rui Wang; Minghui Li; Qingchun Zhang; Jianfei He; Dan Liu; Yuqi Feng; Weilin Liu; Jianhua Liu (Food Chemistry, 2024)

Regulating the defects of MIL-101(Cr) for the efficient and simultaneous determination of eleven plant growth regulators in fresh fruit juice - Rui Cheng; Yiqun Wan; Xuejin Mao; Hao Wan; Fan Liu; Lan Guo; Bingzhen Zhang (Food Chemistry, 2024)

Development and comprehensive SBSE-GC/Q-TOF-MS analysis optimization, comparison, and evaluation of different mulberry varieties volatile flavor - Di Ma; Tianbao Lin; Huiyu Zhao; Yougui Li; Xinquan Wang; Shanshan Di; Zhenzhen Liu; Mingqi Liu; Peipei Qi; Suling Zhang; Rui Jiao (Food Chemistry, 2024)

Multi-omics Analysis of Volatile Flavor Components in Pacific Chub and Spanish Mackerel during Freezing using GC–MS–O - Yi-Zhen Huang; Yu Liu; Rui Zhu; Xiaoxiao Ma; Songlin Xin; Beiwei Zhu; Xiu-Ping Dong (Food Chemistry, 2024)

Highly sensitive detection of aflatoxin B1 byCRISPR/Cas12a-assisted single nanoparticle counting - Chengchao Zhang; Xin Zhao; Zili Huang; Ziyan Li; Jianyu Hu; Rui Liu; Yi Lv (Food Chemistry, 2024)

Correlation of glass transition features and macroscopic, mesoscopic properties of dough regulated by molecular weight of dextran - Shunqin Li; Jing Mao; Yunjiao Zhao; Wenjie Sui; Tao Wu; Rui Liu; Min Zhang (Food Hydrocolloids, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Annual burying of pelletized straw benefits grain amino acid by increasing soil mineral elements: A case study in Northeast China - Peixin Wang; Xiquan Wang; Rui Zong; Xinbo Wang; Haiping Ni; Lumin Liu; Yan Yang; Yubo Hao; Yiteng Zhang; Huancheng Pang; Chunrong Qian (Field Crops Research, 2024)

High-spatial resolution ground-level ozone in Yunnan, China: A spatiotemporal estimation based on comparative analyses of machine learning models - Xingwei Man; Rui Liu; Yu Zhang; Weiqiang Yu; Fanhao Kong; Li Liu; Yan Luo; Tao Feng (Environmental Research, 2024)

Machine learning: An accelerator for the exploration and application of advanced metal-organic frameworks - Ruolin Du; Ruiqi Xin; Han Wang; Wenkai Zhu; Rui Li; Wei Liu (Chemical Engineering Journal, 2024)

Study on the effect of NO2 impurity gas on the performance and local current density distribution of PEMFC - Rui Lin; Yuan Jing; Wenbo Dai; Shiyang Hua; Dengcheng Liu; Zhixian Hao (Chemical Engineering Journal, 2024)

Solvent-promoted selective chemocatalytic hydroxymethylation of biomass furanic compounds - Weipeng Song; Junhua Zhang; Yong Sun; Rui Zhang; Lincai Peng; Huai Liu (Chemical Engineering Journal, 2024)

Manipulating cationic ordering toward highly efficient and zero-thermal-quenching cyan photoluminescence - Hongzhi Zhang; Hong Li; Conglin Liu; Hongming Jiang; Junpeng Li; Yuxin Liu; Jiayi He; Rui Wang; Wanbiao Hu; Jing Zhu (Chemical Engineering Journal, 2024)

Low temperature catalytic activity of molybdenum promoted two-dimensional boron nitride in propane oxidative dehydrogenation reaction - Yixiang Zhu; Rui Chen; Yixuan Yang; Yu Liu; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2024)

Photoactive cationic conjugated microporous polymers containing pyrimidine with an ‘adsorption-kill’ antibacterial strategy for infected wound healing - Ga Liu; Shengfei Bao; Jiahao Shi; Chunyu Xie; Fuying Liao; Lingshuang Wang; Fan Zheng; Rui L. Reis; Subhas C. Kundu; Bo Xiao; Xiao Yang; Lian Duan (Chemical Engineering Journal, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Temperature-driven dynamic evolution process of Ag species on silver-loaded Zr0.2Sn0.8O2 catalyst for selective catalytic oxidation of ammonia - Yan Zhang; Zongxiang Yang; Meng Wang; Min Zhang; Caixia Liu; Qingling Liu; Weichao Wang; Ziyin Zhang; Rui Han; Na Ji (Chemical Engineering Journal, 2024)

Single aptamer hairpin DNA-based response system combined with COF-based signal amplification strategy for ultrasensitive detection of cancer-associated thrombin - Youfa Wang; Jin Wang; Rui Wang; Yang Liu; Geoffrey I.N. Waterhouse; Xiong Ding; Vijaya Raghavan (Chemical Engineering Journal, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Climate and soil: Key Drivers of Plant Traits and Community Functional Differences in the Lakeshore Wetlands of Northern China - Rui Zhang; Zhichao Xu; Huamin Liu; Hongbo Yu; Feng Niu; Haitao Fang; Linqian Ma; Yunhao Wen; Lu Wen; Yi Zhuo; Lixin Wang (Wetlands, 2024)

Influence of ion size on the charge storage mechanism of MXenes: a combination of experimental and computational study - Huiwen Wan; Rui Wang; Huiyang Fan; Hongbo Gao; Yucheng Chen; Zhu Liu (Waste Disposal & Sustainable Energy, 2024)

Adaptive strategies of high and low nucleic acid prokaryotes in response to declining resource availability and selective grazing by protozoa - Chen Hu; Liuqian Yu; Xiaowei Chen; Jihua Liu; Yao Zhang; John Batt; Xilin Xiao; Qiang Shi; Rui Zhang; Tingwei Luo; Nianzhi Jiao; Dapeng Xu (Science China Earth Sciences, 2024)
Prokaryotes play a fundamental role in global ocean biogeochemical cycles. However, how the abundance and metabolic activity of ecologically distinct subgroups (i.e., high nucleic acid (HNA) and low nucleic acid (LNA) cells), and their regulating factors, change in response to changing marine environmental conditions remains poorly understood. Here, we delved into the time-evolving dynamic responses of the HNA and LNA prokaryotic subgroups to declining resource availability and selective grazing by protozoa by conducting a 73-day incubation experiment in a large-volume (117,000 L) macrocosm that facilitates community-level exploration. We found that the metabolic activity of the HNA subgroup was higher than that of the LNA subgroup when the macrocosm was resource replete but that the HNA subgroup declined more rapidly than the LNA subgroup as the resources became increasingly scarce, leading to a steadily increasing contribution of LNA cells to prokaryotic activity. Meanwhile, as resources in the macrocosm became limited, protozoan grazing preference shifted from the HNA to the LNA subgroup and the contributions of the LNA subgroup to the carbon flow within the macrocosm increased. The findings highlight the resilience of LNA cells in resource-limited environments, illuminate the critical role of selective grazing by protozoa in balancing distinct prokaryotic subgroups under changing resource conditions, and demonstrate the complex and adaptive interactions between protozoa and prokaryotes across diverse environmental contexts.

Improved seed yield and phosphorus accumulation in soybean are associated with the enhanced root exudates in south-west China - Hong-Lan Zhang; Nian Liang; Rui Dong; Chang-An Liu; Chun-Ling Hao; Kadambot H. M. Siddique; Jin He (Plant and Soil, 2024)

Investigating the therapeutic potential of sinomenine in rheumatoid arthritis: anti-inflammatory, antioxidant, and immunomodulatory mechanisms - Juan Li; Junjie Cao; Qingping Chen; Dan Liu; Rui Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Potential in exosome-based targeted nano-drugs and delivery vehicles for posterior ocular disease treatment: from barriers to therapeutic application - Xingru Peng; Tingting Zhang; Rui Liu; Xin Jin (Molecular and Cellular Biochemistry, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Migration and transformation mechanisms of iron in clayey sediments during compaction: studies using simulation experiments - Rui Liu; Teng Ma; Xinyan Liu; Yantao Jian; Juan Chen (Hydrogeology Journal, 2024)

Genome-wide identification and expression-pattern analysis of sulfate transporter (SULTR) gene family in cotton under multiple abiotic stresses and fiber development - Yu Chen; Xianghui Xiao; Rui Yang; Zhihao Sun; Shuhan Yang; Haibo Zhang; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Yuzhen Shi; Youlu Yuan; et al. (Functional & Integrative Genomics, 2024)

Variations in Column Concentration of Greenhouse Gases in China and Their Response to the 2015–2016 El Niño Event - Ningwei Liu; Lingjun Xia; Youjun Dou; Shaorou Dong; Jing Wen; Ying Wang; Rui Feng; Ruonan Wang; Yuhe Li (Journal of Meteorological Research, 2024)

Numerical simulation prediction of critical heat flux for 5 × 5 rod bundle with multiple grid spacers and different cladding materials - Kexin Liu; Kejia Li; Yulong Mao; Rui Zhang; Ming Ding; Xiaxin Cao (Annals of Nuclear Energy, 2024)

Multiple signal-enhanced electrochemiluminescence aptamer sensors based on carboxylated ruthenium (II) complexes for acetamiprid detection - Chenchen Li; Bingxin Zhang; Zhourui Wu; Ying Liu; Rui Xu; Yaoguang Wang; Yong Zhang; Qin Wei (Analytica Chimica Acta, 2024)

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

Evaluating the fracture resistance and drainage difficulty of coal reservoirs using log data - Zhi-di Liu; Bin-rui Yang; Xiao-yan Tang; Wei Wang; Liang Ji; Zhi-hao Jiang (Applied Geophysics, 2024)

Evaluation and Projection of Population Exposure to Temperature Extremes over the Beijing–Tianjin–Hebei Region Using a High-Resolution Regional Climate Model RegCM4 Ensemble - Peihua Qin; Zhenghui Xie; Rui Han; Buchun Liu (Advances in Atmospheric Sciences, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Cytotoxicity sesquiterpenoids from the leaves of Datura stramonium L. - Juan Pan; Yan Liu; Ao-Fei Wang; Jia-Tong Wu; Rui Yang; Wei Guan; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

Social determinants of health and their relation to suboptimal health status in the context of 3PM: a latent profile analysis - Lai Kun Tong; Yue Yi Li; Yong Bing Liu; Mu Rui Zheng; Guang Lei Fu; Mio Leng Au (EPMA Journal, 2024)

Two aromatic acid derivatives and a xanthone from Hypericum hengshanense - Jiaqi Zhao; Feng Wei; Hong Liu; Rui Qin; Xinzhou Yang (Natural Product Research, 2024)

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Current status and trends in island ecosystem services research: A bibliometric analysis from 2000 to 2023 - Rui Du; Baiqiong Liu; Min Xu (Marine Policy, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Advanced acoustic leak detection in water distribution networks using integrated generative model - Rongsheng Liu; Tarek Zayed; Rui Xiao (Water Research, 2024)

Evaporation-driven interfacial restructuring induces highly efficient methanogenesis of waste biomass - Ying Xu; Haoyu Liu; Hui Geng; Rui Liu; Xiaohu Dai (Water Research, 2024)

Magnetic porous microspheres enhancing the anaerobic digestion of sewage sludge: Synergistic free and attached methanogenic consortia - Hui Geng; Ying Xu; Rui Liu; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Assessing ammonium pollution and mitigation measures through a modified watershed non-point source model - Feng Han; Qing Tian; Nengwang Chen; Zhaoping Hu; Yao Wang; Rui Xiong; Peng Xu; Wei Liu; Alejandra Stehr; Ricardo O. Barra; Yi Zheng (Water Research, 2024)

Hypoxia inducible factor-1α facilitates transmissible gastroenteritis virus replication by inhibiting type I and type III interferon production - Yunhang Zhang; Xue Rui; Yang Li; Yue Zhang; Yifei Cai; Chen Tan; Ning Yang; Yuanyuan Liu; Yuguang Fu; Guangliang Liu (Veterinary Microbiology, 2024)

H5N1 high pathogenicity avian influenza virus in migratory birds exhibiting low pathogenicity in mallards increases its risk of transmission and spread in poultry - Qiuyan Mao; Zhixin Li; Yuecheng Li; Yaxin Zhang; Shuo Liu; Xin Yin; Cheng Peng; Rui Ma; Jinping Li; Guangyu Hou; Wenming Jiang; Hualei Liu (Veterinary Microbiology, 2024)

Modeling the long-range transmission of airborne bioaerosol releases in a high-density urban environment - Zhijian Dong; Zhijian Liu; Chenxing Hu; Yongjun Jin; Chenglin Ye; Yuchen He; Rui Rong (Urban Climate, 2024)

Influence of the anchor angle on the seismic response of anchored stabilizing piles: Centrifuge modeling tests - Yu Wang; Tong Zheng; Rui Sun; Zhiliang Sun; Zhinan Xie; Zhendong Shan; Hongshuai Liu; Wenhao Qi; Yu Bai (Soil Dynamics and Earthquake Engineering, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Release potential, neglected leakage and reduction countermeasures of COD and Ammonia in MSWLs - Haonan Yang; Qifei Huang; Ya Xu; Rui Xiang; Yuqiang Liu (Science of The Total Environment, 2024)

Characteristics of second-hand exposure to aerosols from e-cigarettes: A literature review since 2010 - Tong Cui; Rui Lu; Chuan Liu; Zehong Wu; Xingtao Jiang; Yiqiao Liu; Song Pan; Yanpeng Li (Science of The Total Environment, 2024)

Stable continuous flow CANDAN process transitioning from anammox UASB reactor by facilitating indigenous nitrite-producing denitrification community - Rui Du; Meihui Tang; Qingtao Liu; Shenbin Cao; Yongzhen Peng (Science of The Total Environment, 2024)

Encapsulate Co3O4 within ultrathin graphene sheets to enhance peroxymonosulfate activation by tuning surface electronic structures - Taobo Huang; Rui An; Jie Li; Wen Liu; Xiuping Zhu; Haodong Ji; Ting Wang (Science of The Total Environment, 2024)

Biomineralization of phosphorus during anaerobic treatment of distillery wastewaters - Lei Zhang; Yiyang Yuan; Chengyuan Li; Yingdi Zhang; Huijuan Sun; Rui Xu; Yang Liu (Science of The Total Environment, 2024)

Regional scale terrace mapping in fragmented mountainous areas using multi-source remote sensing data and sample purification strategy - Zicheng Liu; GuoKun Chen; Bohui Tang; Qingke Wen; Rui Tan; Yan Huang (Science of The Total Environment, 2024)

Redox condition changes caused by impacts: Insights from Chang’e-5 lunar glass beads - Runlian Pang; Jing Yang; Rui Li; Shirong Liu; Qiong Li; Dan Zhu; Wei Du; Yun Liu (Science Bulletin, 2024)

Cooling and optimizing urban heat island based on a thermal knowledge-informed multi-type ant colony model - Zhaomin Tong; Jiaming Yang; Yaolin Liu; Ziyi Zhang; Sui Liu; Yanchi Lu; Bowen Pang; Rui An (Remote Sensing of Environment, 2024)

A novel stress concentration inspection method for marine oil and gas pipeline based on UNSM - Jiaxing Xin; Jinzhong Chen; Renyang He; Rui Li; Xiaolong Li; Chang Liu; Run-kun Lu; Zhengda Su; Wenbo Han (Ocean Engineering, 2024)

Records of deep-sea turbidity current activity in the Bengal Fan since the Last Glacial Maximum - Jingrui Li; Xin Shan; Xuefa Shi; Shengfa Liu; Shuqing Qiao; Hui Zhang; Kaikai Wu; Xiaoming Miao; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Using shell to enhance the phosphorus adsorption capability of aluminum-based drinking water treatment residue-dominant sintered ceramsite - Nannan Yuan; Rui Liu; Dongsiao Li; Lingli Yao; Changhui Wang (Journal of Water Process Engineering, 2024)

Regulatory effects of non-growing season precipitation on the community structure, biomass allocation, and water-carbon utilization in a temperate desert steppe - Yifan Song; Denghua Yan; Yajing Lu; Tiejun Liu; Tianling Qin; Baisha Weng; Rui Jiao; Yunhao Wen; Wei Shi (Journal of Hydrology, 2024)

Self-assembly of metal-polyphenolic network on biomass for enhanced organic contaminant capturing from water with a high cost-to-benefit ratio - Xin Jin; Xueyi Li; Yubo Liu; Yilong Cui; Yunyi Liang; Qin Wang; Jin Wang; Rui Yang; Jianwei Zhao; Changlei Xia (Journal of Hazardous Materials, 2024)

Association between air pollution and male sexual function: A nationwide observational study in China - Ziyuan Shen; Feng Zhang; Zihan Guo; Rui Qu; Yiqiu Wei; Jingxuan Wang; Weiqian Zhang; Xing Xing; Yan Zhang; Jue Liu; Dongdong Tang (Journal of Hazardous Materials, 2024)

A near-infrared fluorescent ratiometric probe with large Stokes shift for multi-mode sensing of Pb2+ and bioimaging - Cuibing Bai; Junxiong Yao; Qian Meng; Yajie Dong; Mengyu Chen; Xinyi Liu; Xinyu Wang; Rui Qiao; Huanan Huang; Biao Wei; Changqing Qu; Hui Miao (Journal of Hazardous Materials, 2024)

Comprehensive utilization for hydrothermal conversion products of food waste - Rui Bao; Shuzhong Wang; Jiaqi Feng; Kai Liu; Hui Liu; Fan Zhang; Yuanwang Duan; Zicheng Li; Jianqiao Yang (Journal of Cleaner Production, 2024)

Performance enhancement, bacterial communities optimization and emerging pollutants elimination by microalgal-bacterial consortium for treating aquaculture pond sediments - Xuda Wang; Shilei Li; Rui Mi; Ying Dong; Jingwei Jiang; Xiaoyan Guan; Xiaoyue Wang; Bo Ye; Danni Liu; Zhenjun Zhao; Xuewen Gao; Zunchun Zhou (Journal of Environmental Management, 2024)

Uncovering the coupling effect with energy-related carbon emissions and human development variety in Chinese provinces - Liu Chen; Yiqi Tan; Gengpei Lv; Weiguang Cai; Xiaofeng Gao; Rui Li (Journal of Environmental Sciences, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Effects of ultrasonic treatment on the texture quality of aged rice flour - Yubao Guo; Rui Song; Shimin Zhu; Xinyu Liu; Xinyu Wang (Journal of Cereal Science, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Insights into “wheat aroma”: Analysis of volatile components in wheat grains cultivated in saline–alkali soil - Qianqian Sun; Rui Zhang; Yu Liu; Liya Niu; Hongyan Liu; Peifang Ren; Bianna Xu; Boli Guo; Bo Zhang (Food Research International, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Covalent organic framework-sodium alginate-Ca2+-polyacrylic acid composite beads for convenient dispersive solid-phase extraction of neonicotinoid insecticides in fruit and vegetables - Ling-Zhi Liu; Rui Zhou; Yong-Li Li; Yue-Hong Pang; Xiao-Fang Shen; Jun Liu (Food Chemistry, 2024)

Nonmetal catalyst boosting amplification of both colorimetric and electrochemical signal for multi-mode nitrite sensing - Ying Li; Yuyang Zhang; Rida Javed; Rui Li; Hongbin Zhao; Xing Liu; Chenghui Zhang; Hongmei Cao; Daixin Ye (Food Chemistry, 2024)

Development of an analytic method for organosulfur compounds in Welsh onion and its use for nutritional quality analysis of five typical varieties in China - Pingxiang Liu; Peng Wu; Jingxiu Bi; Yuying Jiang; Rui Gao; Lei Gao; Yonghua Li; Tong Zhao; Xiao Zhang; Chao Zhang; Yutao Wang (Food Chemistry, 2024)

Cytotoxic withanolides from the stems and leaves of Physalis ixocarpa - Ke Xiang; Yan Liu; Rui Zhu; Yang Xu; Dejuan Sun; Yueying Yang; Yushu Yan; Bingyou Yang; Hua Li; Lixia Chen (Food Chemistry, 2024)

Snakehead vesiculovirus (SHVV) leader RNA interacts with host antiviral factors RPS8 and L13a and promotes virus replication - Yan Ji; Rui Cheng; Xuan Zhou; Jiaqi Zhang; Xiaodan Liu; Suhong Sheng; Chi Zhang (Fish & Shellfish Immunology, 2024)

Relationship of solid fuels use with cognitive function and efficacy of switching to cleaner fuels or using ventilation: A systematic review and meta-analysis - Rui Yang; Jie He; Kang-kang Zhong; Ming-xuan Fan; Teng Bao; Xue-Chun Liu; Qi Zhong (Environmental Research, 2024)

Factors controlling accumulation and bioavailability of selenium in paddy soils: A case study in Luxi County, China - Zhangqian Xu; Weijun Zhou; Yuzhou Zhou; Haojie Cui; Rui Liu; Guiduo Shang (Environmental Pollution, 2024)

Effect of nano-SiO2 modification on the seismic performance of recycled aggregate concrete shear walls - Yingwu Zhou; Liu Fan; Feng Xing; Wenwei Lin; Rui Hu; Menghuan Guo; Zhongfeng Zhu (Engineering Structures, 2024)

Evaluating the influence of Cynodon dactylon on the wave force and wave erosion in the water-level fluctuation zone of the Three Gorges Reservoir Area - Hai Xiao; Deyu Liu; Feng Gao; Rui Xiang; Wenqi Zhang; Zirui Liu; Chaohuan Ye; Lun Zhang; Zhenyao Xia (Ecological Engineering, 2024)

Mechanistic insights into the stepwise lithium-mediated electrochemical nitrogen reduction for enhanced ammonia synthesis - Peng Yang; Feng Gong; Chaozhen Liu; Shenglin Liu; Enkang Fu; Yuhang Jing; Junjie Feng; Wenbo Tang; Rui Xiao (Chemical Engineering Journal, 2024)

The carbon dots with near-infrared electrochemiluminescence emission and low excitation potential for ultrasensitive analysis of microRNA-222 - Yu-Zhuo Guo; Rui Liu; Ying Zeng; Ye-Yu Liao; Jia-Li Liu; Ya-Qin Chai; Ruo Yuan (Chemical Engineering Journal, 2024)

Synergistic enhancement of phase change materials through three-dimensional porous layered covalent triazine framework/expanded graphite composites for solar energy storage and beyond - Long Geng; Jiapeng Wang; Xulong Yang; Jiaping Jiang; Rui Li; Yabo Yan; Jiateng Zhao; Changhui Liu (Chemical Engineering Journal, 2024)

Evaluation of benefits and risks of immunosuppressive drugs in biomaterial-based neural progenitor cell transplantation for spinal cord injury repair - Bo Guo; Xinhao Zhao; Yunlong Zou; Xiaokang Cheng; Zheng Sun; Xiaoyu Xue; Man Yin; Chen Jin; Zhenni Chen; Rui Quan; Wenbin Liu; Bin Chen; et al. (Chemical Engineering Journal, 2024)

Current advances in porous organic nanoplatforms for tumor theranostics - Wanhao Qi; Bin Liu; Yian Li; Zhu Liu; Shiqiao Rui; Shuaipeng Feng; Junya Lu; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2024)

Hybrid deterministic and stochastic approach for dynamic simulation of photoinduced atom-transfer radical polymerization processes with microscopic resolution - Rui Liu; Xiaowen Lin; Xi Chen; Antonios Armaou (Chemical Engineering Journal, 2024)

BDTX-189, a novel tyrosine kinase inhibitor, inhibits cell activity via ERK and AKT pathways in the EGFR C797S triple mutant cells - Rui Wang; Wenrui Cui; Lanxin Li; Xiangkai Wei; Chunhong Chu; Guoliang Zhang; Chenxue Liu; Huixia Xu; Chenyang Liu; Ke Wang; Yanming Li; Lei An (Chemico-Biological Interactions, 2024)

Insights into the Degradation and Mechanism of the Enhanced Persulfate Degradation of Tetracycline using an Efficient 3D Copper Metal–Organic Frameworks - Rui Zhou; Congyang Zou; Yong Wang; Zhuyou Zhou; Menghe Liu; Yufeng Ji (Water, Air, & Soil Pollution, 2024)

Exploiting genomic tools for genetic dissection and improving the resistance to Fusarium stalk rot in tropical maize - Junqiao Song; Yubo Liu; Rui Guo; Angela Pacheco; Carlos Muñoz-Zavala; Wei Song; Hui Wang; Shiliang Cao; Guanghui Hu; Hongjian Zheng; Thanda Dhliwayo; Felix San Vicente; et al. (Theoretical and Applied Genetics, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Beneficial action of cinnamic acid against ovarian cancer via network pharmacology analysis and the pharmacological activity assessment - Rong Fan; Zining Liang; Qing Wang; Sizhe Chen; Shiting Huang; Jiansu Liu; Rui Huang; Jie Chen; Feilan Zhao; Wei Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Key factors controlling nitrogen transformation and efflux at the sediment–water interface: a comparative study from different trophic reservoirs - Jie Ren; Guilin Han; Xiaolong Liu; Rui Qu; Ziyang Ding (Journal of Soils and Sediments, 2024)

Integration of the Metabolome and Transcriptome Reveals Diurnal Variability in the Effects of Melatonin on Salt Tolerance in Maize Seedlings - Jiajie Wang; Di Yan; Zhenzong Lu; Rui Liu; Yue Hong; Ye Wang; Zhen Peng; Chunxin Yu; Yuerong Gao; Ziyan Liu; Liusheng Duan; Runzhi Li (Journal of Plant Growth Regulation, 2024)

Analysis on the causes of massive stranding of Yellow Sea green tide on Lianyungang and Rizhao coasts in 2022 - Lingjuan Wu; Juan Huang; Yi Ding; Guiyan Liu; Shuai Huang; Song Gao; Chao Yuan; Jiangling Xu; Ping Wu; Rui Huang; Ruobing Wen; Jie Mei (Journal of Oceanology and Limnology, 2024)

Influence of building spatial patterns on wind environment and air pollution dispersion inside an industrial park based on CFD simulation - Qiang Zhao; Rui Li; Kaifa Cao; Mingjian Yi; Hao Liu (Environmental Monitoring and Assessment, 2024)

Development of a heat transfer model for the film boiling regime in a fouling layer - Xiaowen Wang; Rui Zhang; Maolong Liu; Tenglong Cong; Limin Liu; Li Liu; Hanyang Gu (Annals of Nuclear Energy, 2024)

Exquisite visualization of mitophagy and monitoring the increase of lysosomal micro-viscosity in mitophagy with an unusual pH-independent lysosomal rotor - Rui Yang; Wei He; Changxin Zhu; Xifeng Yang; Yawei Kuang; Tao Zhu; Jingyang Xu; Yuang Zhao; Tingwang Jiang; Yushen Liu; Mengmeng Wei (Analytica Chimica Acta, 2024)

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

An Underwater Localization Method Based on Visual SLAM for the Near-Bottom Environment - Zonglin Liu; Meng Wang; Hanwen Hu; Tong Ge; Rui Miao (Journal of Marine Science and Engineering, 2024)
The feature matching of the near-bottom visual SLAM is influenced by underwater raised sediments, resulting in tracking loss. In this paper, the novel visual SLAM system is proposed in the underwater raised sediments environment. The underwater images are firstly classified based on the color recognition method by adding the weights of pixel location to reduce the interference of similar colors on the seabed. The improved adaptive median filter method is proposed to filter the classified images by using the mean value of the filter window border as the discriminant condition to retain the original features of the image. The filtered images are finally processed by the tracking module to obtain the trajectory of underwater vehicles and the seafloor maps. The datasets of seamount areas captured in the western Pacific Ocean are processed by the improved visual SLAM system. The keyframes, mapping points, and feature point matching pairs extracted from the improved visual SLAM system are improved by 5.2%, 11.2%, and 4.5% compared with that of the ORB-SLAM3 system, respectively. The improved visual SLAM system has the advantage of robustness to dynamic disturbances, which is of practical application in underwater vehicles operated in near-bottom areas such as seamounts and nodules.

Remote modulation of sub-seasonal soil moisture on clustered extreme precipitation in Northern China - Jiang Liu; Jie Zhang; Yibo Du; Rui Hu; Qianrong Ma; Heng Kan; Sha Sha; Yuxin Kuang (Climate Dynamics, 2024)

The role of exogenous hydrogen sulfide in mitigating cadmium toxicity in plants: A comprehensive meta-analysis - Hanping Cao; Kejin Song; Yingying Hu; Qingxiao Li; Tengfei Ma; Rui Li; Nan Chen; Shunqin Zhu; Wanhong Liu (Environmental Science and Pollution Research, 2024)

Visualized Enzyme-Activated Fluorescence Probe for Accurately Detecting β-Gal in Living Cells and BALB/c Nude Mice - Xiaoli Huang; Le Chang; Jianxin Ge; Ping Wang; Rui Yin; Guanqi Liu; Guopin Wang (Journal of Fluorescence, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Two microbes assisting Miscanthus floridulus in remediating multi-metal(loid)s-contaminated soil - Yunhua Xiao; Jingjing Ma; Rui Chen; Sha Xiang; Bo Yang; Liang Chen; Jun Fang; Shuming Liu (Environmental Science and Pollution Research, 2024)

Transcriptomic and biochemical analysis of metabolic remodeling in Bacillus subtilis MSC4 under Benzo[a]pyrene stress - Rui Chen; Na Liu; Yuan Ren; Tangbing Cui (Chemosphere, 2024)

Advances in chemical removal and degradation technologies for microplastics in the aquatic environment: A review - Tianhong Zhou; Shangjian Song; Rui Min; Xin Liu; Guozhen Zhang (Marine Pollution Bulletin, 2024)

Mechanisms of the novel pesticide sodium dodecyl benzene sulfonate in the mitigation of protozoan ciliated pathogens during microalgal cultivation - Gaojingwen Sun; Ruiqi Jia; Yan Zhang; Zhaoji Zhang; Yunlong Wang; Rui Ma; Yaxin Wang; Zhiyang Jiang; Mingjian Liu; Yong Jiang (Marine Pollution Bulletin, 2024)

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Hypoxia preconditioning of human amniotic mesenchymal stem cells enhances proliferation and migration and promotes their homing via the HGF/C-MET signaling axis to augment the repair of acute liver failure - Qian Wang; Yuwen Li; Hui Yuan; Linya Peng; Zixing Dai; Ye Sun; Rui Liu; Wenting Li; Jun Li; Chuanlong Zhu (Tissue and Cell, 2024)

Multi-timescale variation characteristics of PM2.5 in different regions of China during 2014–2022 - Rui Liu; Min Shao; Qin'geng Wang (Science of The Total Environment, 2024)

Regulation of wheat growth by soil multifunctionality and metagenomic-based microbial functional profiles under mulching treatments - Yang Liu; Rui Liu; Zhen Feng; Rong Hu; Fazhu Zhao; Jun Wang (Science of The Total Environment, 2024)

Vanadium isotope evidence for seawater contribution to V enrichment/mineralization in early Cambrian metalliferous black shales - Lin-Hui Dong; Wei Wei; Lingang Xu; Yi-Bo Lin; Ze-Rui Liu; Songqi Pan; Zhenhua Jing; Fang Huang (Science Bulletin, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Experimental investigation of propeller blade back cavitation induced pressure pulses by synchronous observation - Rui Wu; Heng Liu; Weiqi Chen; Sheng Ji; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Competition between ocean thermal structure and tropical cyclone characteristics modulates ocean environmental responses in the Yellow and Bohai Seas - Xiuting Wang; Jiagen Li; Liang Sun; Mengyuan Xu; Haihua Liu; Rui Liu (Marine Environmental Research, 2024)

Enhancing nitrogen removal efficiency for anammox granular sludge at low temperature by fulvic acids from different sources - Li-Li Qiao; Yun-Rui Feng; Shao-Yang Liu; Peng Yan (Journal of Water Process Engineering, 2024)

Hollow α-Bi2O3/TiO2 nanotube arrays hierarchical heterojunction with strong interface interaction for efficient photocatalytic ciprofloxacin degradation - Bingrui Ma; Yuxin Zha; Rui Xu; Jincheng Li; Yajing Guo; Jie Liu; Songxue Wang; Boyin Yan; Yunlong Lan; Baoxiu Zhao; Haijiao Xie (Journal of Water Process Engineering, 2024)

Detecting anomalous commuting patterns: Mismatch between urban land attractiveness and commuting activities - Zhaomin Tong; Ziyi Zhang; Rui An; Yaolin Liu; Huiting Chen; Jiwei Xu; Shihang Fu (Journal of Transport Geography, 2024)

Geothermal fluid chemistry and isotope for interpreting the formation of complex geothermal system in the Gonghe Basin, northeastern Tibetan Plateau - Rui Lu; Wenping Xie; Bo Liu; Shengsheng Zhang; Jinshou Zhu; Wenjing Lin (Journal of Hydrology, 2024)

Improving prediction of soil heavy metal(loid) concentration by developing a combined Co-kriging and geographically and temporally weighted regression (GTWR) model - Huijuan Wang; Menglu Zhao; Xinmiao Huang; Xiaoyong Song; Boya Cai; Rui Tang; Jiaxun Sun; Zilin Han; Jing Yang; Yafeng Liu; Zhengqiu Fan (Journal of Hazardous Materials, 2024)

Asymmetric response of transition metal cationic orbitals to applied electric field - Xinmin Liu; Wanglin Chen; Ying Tang; Shuang Xiao; Qinyi Li; Wuquan Ding; Laosheng Wu; Rui Tian; Rui Li; Hang Li (Journal of Hazardous Materials, 2024)

Significance of phosphorus deficiency for the mitigation of mercury toxicity in the Robinia pseudoacacia L.– rhizobia symbiotic association - Rui Liu; Bin Hu; Michael Dannenmann; Anette Giesemann; Christoph-Martin Geilfus; Canbo Li; Lan Gao; Emmanouil Flemetakis; Robert Haensch; Dingyong Wang; Heinz Rennenberg (Journal of Hazardous Materials, 2024)

Mineral exploration model for Lhasa Area, eastern Gangdese metallogenic belt: Based on knowledge-driven compositional data analysis and catchment basin division - Bingli Liu; Wenbao Zheng; Lu Wang; Cheng Li; Yunhui Kong; Rui Tang; Dejiang Luo; Miao Xie (Journal of Geochemical Exploration, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Application of iron tailings in the coagulation of landfill leachate by bipolar membrane electrodialysis - Yanchao Jin; Guodong Wang; Zheng Li; Chun-Yan Lin; Li-Ping Li; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Journal of Cleaner Production, 2024)

A novel framework for high resolution air quality index prediction with interpretable artificial intelligence and uncertainties estimation - Junhao Wu; Xi Chen; Rui Li; Anqi Wang; Shutong Huang; Qingli Li; Honggang Qi; Min Liu; Heqin Cheng; Zhaocai Wang (Journal of Environmental Management, 2024)

Medical waste incineration fly ash-based magnesium potassium phosphate cement: Calcium-reinforced chlorine solidification/stabilization mechanism and optimized carbon reduction process strategy - Runjie Liu; Shiwei Liu; Shichang Sun; Xing Cao; Junhao Lin; Juan Peng; Fei Ji; Rui Ma (Journal of Environmental Management, 2024)

Differentiated impacts of environmental contexts on residents' environmental attitudes towards ecological restoration programs of China's drylands - Tianjing Wu; Yanxu Liu; Xutong Wu; Zhifeng Liu; Rui Xiao (Journal of Environmental Management, 2024)

Constructing of Fe-Cu bimetallic MOFs derived electro-Fenton cathode for efficient norfloxacin removal - Yixin Du; Zhenpeng Li; Rui Feng; Qing Liu; Yanming Yang; Meng Sun; Yanxia Zhao; Tao Yan; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

Enhanced coking wastewater advanced treatment by using particle electrodes excited persulfate in the three-dimensional electrocatalytic reactors - Tingting Zhang; Weida Wang; Zhe Liu; Rui Yang; Xueyou Fang; Liang Chen; Yiming Qin; Yongjun Liu (Journal of Environmental Chemical Engineering, 2024)

Synergistic removal of sulphur-containing malodourous gases via peroxydisulfate activation in three-dimensional electrode system - Rui Luo; Shugen Liu; Chen Li; Xiaofeng Huang; Ping Ning; Senlin Tian (Journal of Environmental Chemical Engineering, 2024)

Seedless hydrothermal growth of piezoelectric photocatalytic ZnO nanowires on laser-ablated copper mesh for oil/water separation - Xiaohan Xing; Rui Zhou; Huangping Yan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2024)

Oxygen-enriched vacancy spinel Mn-Co oxides by deep thermal reduction for enhanced antibiotics degradation efficiency - Xiai Zhang; Rui Zhou; Ruohong Bi; Tong Wang; Qikui Fan; Hao Zhu; Zhimao Yang; Xiaofei Liu; Chuncai Kong (Journal of Environmental Chemical Engineering, 2024)

Experimental analysis of a CO2 closed heat pump drying system combined with rotary dehumidification for drying banana slices drying - Zhili Sun; Qianqian Wang; Yingying Yuan; Dandan Wang; Qiang Zhou; Chunwei Xu; Kexin Meng; Haowei Peng; Lei Yan; Rui Jin; Lei Li; Haowei Liu; et al. (International Journal of Refrigeration, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effect of berry-derived phenolic products on blood lipid profiles: A systematic review and meta-analysis - Chunxiao Ji; Rui Wang; Dongliang Wang; Yongle Luo; Zaiming Huang; Jianying Liu; Anwei Cheng (Food Bioscience, 2024)

Pilot-scale investigation of performance and microbial community in a novel system combining fixed and suspended activated sludge - Dongni Rui; Kunlong Liu; Yanyan Ma; Kailong Huang; Mengxue Chen; Fei Wu; Xuxiang Zhang; Lin Ye (Environmental Research, 2024)

Enhancing compound confidence in suspect and non-target screening through machine learning-based retention time prediction - Dehao Song; Ting Tang; Rui Wang; He Liu; Danping Xie; Bo Zhao; Zhi Dang; Guining Lu (Environmental Pollution, 2024)

Enhancing soil redox dynamics: Comparative effects of Fe-modified biochar (N–Fe and S–Fe) on Fe oxide transformation and Cd immobilization - Tianren Si; Rui Yuan; Yanjie Qi; Yuhao Zhang; Yan Wang; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Stephen Joseph; Lianqing Li; Genxing Pan (Environmental Pollution, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

Self-enhanced nanohydrogel electrochemiluminescence biosensor based on CRISPR/Cas12a and gold platinum nanoparticles modification for high-sensitivity detection of Burkholderia pseudomallei - Yuexin Wang; Bo Shen; Nini Luo; Cai Li; Haiping Wu; Yanshuang Wang; Shen Tian; Xuemiao Li; Rui Liu; Xinmin Li; Junman Chen; Wei Cheng; et al. (Chemical Engineering Journal, 2024)

Structural regulation of ultra-microporous biomass-derived carbon materials induced by molten salt synergistic activation and its application in CO2 capture - Zhi Cheng; Xiaohao Liu; Rui Diao; Fenglei Qi; Peiyong Ma (Chemical Engineering Journal, 2024)

A polypyrrole-dopamine/poly(vinyl alcohol) anisotropic hydrogel for strain sensor and bioelectrodes - Shuang Chen; Bingyan Guo; Jiajun Yu; Zhuojun Yan; Rui Liu; Chaojie Yu; Zhongming Zhao; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Seven mechanisms of oxygen evolution reaction proposed recently: A mini review - Zihang Feng; Chuanlin Dai; Peng Shi; Xuefei Lei; Rui Guo; Biao Wang; Xuanwen Liu; Junhua You (Chemical Engineering Journal, 2024)

Chameleon inspired high-temperature thermochromic traffic light type photonic crystal sensors toward early fire detection and visual sensing - Qingwen Shi; Jinxing Liang; Xuyi Wang; Kaixiang Yao; Yidan Tang; Chen Pan; Jiuxiao Sun; Rui Liu; Haiying Tan; Tao Tang (Chemical Engineering Journal, 2024)

Ultrafine FeCuAgCeGd–based high–entropy nanozyme: Preparation, catalytic mechanism, and point–of–care detection of dopamine in human serum - Rui Sheng; Yue Liu; Taimei Cai; Rong Wang; Gan Yang; Tao Wen; Fangjian Ning; Hailong Peng (Chemical Engineering Journal, 2024)

Two-dimensional peak-valley alternating self-supporting electrode accelerating nitrate electrocatalytic reduction: Ammonia synthesis and wastewater treatment - Yuelong Liu; Haoran Zhang; Rui Bai; Haijian Wang; Yan Zhao; Yingtang Zhou; Xue Zhao (Chemical Engineering Journal, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Scale-up of microalgal systems for decarbonization and bioproducts: Challenges and opportunities - Peilun Xu; Shengxi Shao; Jun Qian; Jingjing Li; Rui Xu; Jin Liu; Wenguang Zhou (Bioresource Technology, 2024)

Global Sensitivity Analysis of Crop Parameters Based on AquaCrop Model - Wei Li; Rui Song; Muhammad Awais; Leilei Ji; Shuo Li; Mingjiang Liu; Tao Lang; Handong Qi (Water Resources Management, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Integrative transcriptome and metabolome analysis reveals the discrepancy in the accumulation of active ingredients between Lycium barbarum cultivars - Xuexia Liu; Han Gao; Yasmina Radani; Sijun Yue; Ziping Zhang; Jianning Tang; Jinzhong Zhu; Rui Zheng (Planta, 2024)

Characterization of CYP82 genes involved in the biosynthesis of structurally diverse benzylisoquinoline alkaloids in Corydalis yanhusuo - Xiuyu Liu; Ying Ma; Junling Bu; Conglong Lian; Rui Ma; Qishuang Li; Xiang Jiao; Zhimin Hu; Yun Chen; Suiqing Chen; Juan Guo; Luqi Huang (Plant Molecular Biology, 2024)

Analysis of landslide deformation in eastern Qinghai Province, Northwest China, using SBAS-InSAR - Haibo Tian; Pinglang Kou; Qiang Xu; Yuxiang Tao; Zhao Jin; Ying Xia; Jiangfan Feng; Rui Liu; Yongcheng Gou (Natural Hazards, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

Research on satellite data-driven algorithm for ground-level ozone concentration inversion: case of Yunnan, China - Weiqiang Yu; Tao Feng; Xingwei Man; Huan Lin; Haonan Zhang; Rui Liu (Earth Science Informatics, 2024)

Optimizing ZWD estimation strategies for enhanced PPP-RTK performance - Rui Gao; Fei Ye; Yang Liu; Jiuping Zha; Robert Odolinski; Chalermchon Satirapod; Baocheng Zhang (GPS Solutions, 2024)

Improving GNSS PPP-RTK through global forecast system zenith wet delay augmentation - Rui Gao; Zhizhao Liu; Robert Odolinski; Baocheng Zhang (GPS Solutions, 2024)
The precise point positioning real-time kinematic (PPP-RTK) is a high-precision global navigation satellite system (GNSS) positioning technique that combines the advantages of wide-area coverage in precise point positioning (PPP) and of rapid convergence in real-time kinematic (RTK). However, the PPP-RTK convergence is still limited by the precision of slant ionospheric delays and tropospheric zenith wet delay (ZWD), which affects the PPP-RTK network parameters estimation and user positioning performance. The present study aims to construct a PPP-RTK model augmented with a priori ZWD values derived from the global forecast system (GFS) product (a global numerical weather prediction (NWP) model) to improve the PPP-RTK performance. This study gives a priori ZWD values and conversion based on the GFS products, and the full-rank GFS-augmented undifferenced and uncombined (UDUC) PPP-RTK network model is derived. To verify the performance of GFS-augmented UDUC PPP-RTK, a comprehensive evaluation using 10-day GNSS observation data from three different GNSS station networks in the United States (US), Australia, and Europe is conducted. The results show that with the GFS ZWD a priori information, PPP-RTK performance significantly improves at the initial filtering stage, but this advantage gradually decays over time. Based on 10-day positioning results for all user stations, the GFS ZWD-augmented PPP-RTK approach reduces the average convergence time by 46% from 10.0 to 5.4 min, the three-dimensional root-mean-square (3D-RMS) error by 5.7% from 3.5 to 3.3 cm, and the time to first fix (TTFF) value by 35.8% from 6.7 to 4.3 min, all when compared to the traditional PPP-RTK without GFS ZWD constraints.

Long-term straw return to a wheat-maize system results in topsoil organic C saturation and increased yields while no stimulating or reducing yield-scaled N2O and NO emissions - Zhisheng Yao; Yanqiang Wang; Rui Wang; Xiaogang Wang; Yan Wang; Xunhua Zheng; Chunyan Liu; Bo Zhu; Minghua Zhou; Yan Liu; Klaus Butterbach-Bahl (Agricultural and Forest Meteorology, 2024)

Complete genome sequence of a novel dsRNA virus from the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Yunxia Ni; Hui Zhao; Xintao Liu; Rui Qiu; Shujun Li; Hongyan Liu (Archives of Virology, 2024)

ATF4 in cellular stress, ferroptosis, and cancer - Hu Tang; Rui Kang; Jiao Liu; Daolin Tang (Archives of Toxicology, 2024)

Salinity as a key factor affecting viral activity and life strategies in alpine lakes - Lin Zang; Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Xuanying Song; Yunlan Yang; Lanlan Cai; Keshao Liu; Guannan Mao; Mukan Ji; Rui Zhang (Limnology and Oceanography, 2024)
Viruses are major players in the biosphere, yet little is known about their dynamics and life strategies in alpine lakes, particularly those on the Tibetan Plateau. We investigated microbial abundance, viral dynamics, and viral life strategies in 10 high‐altitude Tibetan lakes and found that they harbor high levels of active viruses. Salinity was identified as a crucial factor influencing viral abundance, dynamics, as well as viral life strategies. Lytic and lysogenic viral productions in moderate‐ and high‐salinity lakes were significantly higher than those in freshwater lakes. A trade‐off between viral life strategies resulted in a switch from lysis to lysogeny in high‐salinity lakes. Virus‐mediated cell lysis and virus decay in sampled Tibetan lakes could release about 162.72 and 2.84 μ g C L −1 d −1 , respectively. These findings revealed the crucial role of viruses in the carbon cycle of Tibetan lakes, and a switch in viral life strategies may impact their contribution to the carbon cycle. The potential impact of salinity changes triggered by climate change on the carbon cycle in alpine lakes worldwide is highlighted.

Correction to: A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Unraveling sources of cyanate in the marine environment: insights from cyanate distributions and production during the photochemical degradation of dissolved organic matter - Rui Wang; Jihua Liu; Yongle Xu; Li Liu; Kenneth Mopper (Frontiers in Marine Science, 2024)
Cyanate is a nitrogen and energy source for diverse marine microorganisms, playing important roles in the nitrogen cycle. Despite the extensive research on cyanate utilization, the sources of this nitrogen compound remain largely enigmatic. To unravel the sources of cyanate, distributions and production of cyanate during photochemical degradation of natural dissolved organic matter (DOM) were investigated across various environments, including freshwater, estuarine, coastal areas in Florida, and the continental and slope regions of the North American mid-Atlantic Ocean (NATL). Cyanate production was also examined during the photochemical degradation of exudates from a typical strain of Synechococcus , an important phytoplankton component. To deepen our understanding of the sources and production mechanisms of cyanate, its production was assessed during the photochemical degradation of a natural seawater DOM supplemented with five nitrogen–containing compounds with distinguishing structures and functional groups. Generally, cyanate exhibited higher concentrations in the Florida coastal, estuarine, and freshwater environments than the NATL. However, cyanate distribution did not consistently align with its production rates. Despite significantly low concentrations in the NATL, DOM from this region exhibited cyanate production rates comparable to estuarine and Florida coastal environments. Although relatively high cyanate concentrations were observed in the freshwaters, DOM in this environment exhibited very low cyanate production rates. A highly significant correlation was observed between cyanate and chlorophyll a (Chl a ) concentrations in these areas. Moreover, in most estuarine and NATL stations, cyanate concentration and production rate in the Chl a maximum layer were significantly higher than in other layers. Cyanate was produced during the photochemical degradation of the Synechococcus exudates. The cyanate production was significantly enhanced when the natural seawater DOM was supplemented with GlycylGlycine, 4-(methylamino) benzoic acid, 4-[ethyl(methyl)amino] benzaldehyde or methyl 2-aminobenzoate. Our study implies that photochemical degradation of marine DOM, especially phytoplankton-derived DOM, is a substantial source of cyanate in the ocean. Additionally, cyanate may form during the degradation of peptides and small aromatic compounds in DOM, providing novel insights into the nitrogen cycle.

A DEM-based approach for modeling the thermal-mechanical behavior of frozen soil - Ruohan Sun; Run Liu; Huan Zhang; Rui Zhang; Yu Jiang; Ruilong Yin (European Journal of Environmental and Civil Engineering, 2024)

A novel ZnCo2O4/BiOBr p-n/Z-scheme heterojunction photocatalyst for enhancing photocatalytic activity - Tao Xiong; Qi Feng; Cimei Fang; Rui Chen; Yanxi Wang; Longjun Xu; Chenglun Liu (Environmental Science and Pollution Research, 2024)

Investigating the spatio–temporal characteristics of lower atmospheric ducts across the China seas by performing a long–term simulation using the WRF model - Qi Liu; Xiaofeng Zhao; Jing Zou; Tong Hu; Zhijin Qiu; Bo Wang; Zhiqian Li; Chaoran Cui; Rui Cao (Frontiers in Marine Science, 2024)
In this work, a diagnostic scheme for lower atmospheric ducts was established based on the Weather Research and Forecasting (WRF) model. More specifically, a 10-year simulation test was conducted for the China seas to investigate the spatio-temporal characteristics of the lower atmospheric ducts phenomenon. Compared with the sounding data, the long-term simulations showed a high temporal correlation and the root mean square error of the modified atmospheric refractivity remained between 4 M and 7 M. Based on the simulations, significant regional differences in the occurrence probability of lower atmospheric ducts were detected from south to north. Among them, the surface ducts near the sea surface exhibited the highest occurrence probability, with higher probabilities being recorded in autumn and winter, and the probability gradually increased with the decreasing latitude. The spatio-temporal characteristics of duct height, thickness, and strength were generally consistent. In the seas at mid-latitudes, strong ducts mostly occurred in the spring and autumn, with the single-layer ducts being predominant and the first layer duct showing stronger characteristics than the second layer. In the lower latitude regions, the situation was exactly the opposite. The first duct layer, which existed throughout the year, exhibited weaker characteristics with less pronounced seasonal variations. On the other hand, the second duct layer demonstrated stronger features.

A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

Study on somatic embryogenesis of cinnamomum camphora based on transcriptome sequencing - Yilang Liu; Haoran Guo; Xiaoling Kang; Rui Wu; Meijing Yuan; Li Du (Brazilian Journal of Botany, 2024)

Unveiling the role of the Notch signaling pathway and dtx4a/b: Implications for Paralichthys olivaceus ovarian development - Yuxiang Liu; Jiangbo Qu; Rui Li; Jie Qi; Quanqi Zhang (Aquaculture, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

Robustness of the anammox process at low temperatures and low dissolved oxygen for low C/N municipal wastewater treatment - Rui Wang; Jinjin Liu; Qiong Zhang; Xiyao Li; Shuying Wang; Yongzhen Peng (Water Research, 2024)

Enhancing urban climate resilience: A holistic evaluation of urban forest disservices in the aftermath of typhoons - Wan-Yu Liu; Chen-Rui Liu; Chun-Cheng Lin (Urban Climate, 2024)

A review on aroma-active compounds derived from branched-chain amino acid in fermented meat products: Flavor contribution, formation pathways, and enhancement strategies - Lei Chen; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Trends in Food Science & Technology, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Susceptibility and exposure risk to airborne aerosols in intra-urban microclimate: Evidence from subway system of mega-cities - Zhijian Liu; Mingtao Ding; Chenxing Hu; Rui Rong; Chaofan Lin; Guangpeng Yao; Xuqiang Shao; Guangya Jin (Science of The Total Environment, 2024)

Understanding phosphorus mobilization mechanisms in acidic soil amended with calcium-silicon-magnesium-potassium fertilizer - Jilin Lei; Junhui Yin; Shuo Chen; Owen Fenton; Rui Liu; Qing Chen; Bingqian Fan; Shuai Zhang (Science of The Total Environment, 2024)

Recent advances in the role of dissolved organic matter during antibiotics photodegradation in the aquatic environment - Yinghui Guo; Bo Peng; Jinggan Liao; Weicheng Cao; Yaojun Liu; Xiaodong Nie; Zhongwu Li; Rui Ouyang (Science of The Total Environment, 2024)

Manganese disrupts the maturation and degradation of axonal autophagosome leading to hippocampal synaptic toxicity in mice via the activation of LRRK2 on phosphorylation of Rab10 - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Bin Xu (Science of The Total Environment, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Cement kiln geared up to dispose industrial hazardous wastes of megacity under industrial symbiosis - Kailingli Liao; Zeshi Feng; Jin Wu; He Liang; Yuhan Wang; Wenfei Zeng; Yichun Wang; Jinping Tian; Rui Liu; Lyujun Chen (Resources, Conservation and Recycling, 2024)

Constructing high-resolution fingerprints and analyzing complex pollution source of electronic waste recycling base - Rui Wang; Lu Zhan; Zhenming Xu; Yukun Liu (Resources, Conservation and Recycling, 2024)

Topological spin-orbit-coupled fermions beyond rotating wave approximation - Han Zhang; Wen-Wei Wang; Chang Qiao; Long Zhang; Ming-Cheng Liang; Rui Wu; Xu-Jie Wang; Xiong-Jun Liu; Xibo Zhang (Science Bulletin, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

Analysis of factors affecting the performance of air gun source under shallow water conditions: Insights from the non-ideal gas air gun wavelet model - Mingxin Zhao; Jiangbo Huang; Cai Li; Jiang Li; Jiangfeng Zheng; Rui Han; Huaishan Liu (Ocean Engineering, 2024)

Peroxydisulfate activation by B-BC@Fe3S4 for norfloxacin degradation: Radical and non-radical pathways - Hengrui Zhang; Rui Sun; Tianyu Zheng; Xiaolong Wang; Qingyuan Wang; Lei Liu; Haiyan Yang; Xuan Xing (Journal of Water Process Engineering, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

Exploring nonlinear responses of lake nutrients and algal blooms to restoration measures: A three-dimensional flux network modelling approach - Yanxin Sun; Qingsong Jiang; Rui Zou; Wenjing Ma; Mengchen Hu; Yihui Chen; Yong Liu (Journal of Hydrology, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

One-step strategy for efficient Cr(VI) removal via phytate modified zero-valent iron: Accelerated electron transfer and enhanced coordination effect - Rui Gan; Yuxuan Ye; Ziyi Zhan; Qiuyue Zhang; Yuwei Deng; Yingjie Liu; Haochen Li; Jun Wan; Xuanyuan Pei; Qiang Li; Fei Pan (Journal of Hazardous Materials, 2024)

Metabolomics reveals how spinach plants reprogram metabolites to cope with intense stress responses induced by photoaged polystyrene nanoplastics (PSNPs) - Daofen Huang; Ling Ding; Shuhua Wang; Rui Ding; Xinran Qiu; Jianlong Li; Zhengdong Hua; Shasha Liu; Renren Wu; Xujun Liang; Xuetao Guo (Journal of Hazardous Materials, 2024)

Nanoconfined catalytic membrane assembled by nitrogen-doped carbon encapsulating Fe-based nanoparticles for rapid removal of 2,4-dichlorophenol in wastewater by peroxymonosulfate activation - Taigang Ma; Hejun Ren; Meijun Liu; Rui Zhou (Journal of Hazardous Materials, 2024)

Ecological succession of abundant and rare subcommunities during aerobic composting in the presence of residual amoxicillin - Liangyang Mao; Jie Kang; Rui Sun; Jiaxin Liu; Jingping Ge; Wenxiang Ping (Journal of Hazardous Materials, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Occurrence, distribution and ecological risk assessment of herbicide residues in cropland soils from the Mollisols region of Northeast China - Rui Li; Wenyou Hu; Hanqiang Liu; Biao Huang; Zhongjun Jia; Feng Liu; Yuguo Zhao; Khalid Saifullah Khan (Journal of Hazardous Materials, 2024)

Factors affecting chemical and textural properties of dried tuber, fruit and vegetable - Yue Li; Han Zhao; Kexin Xiang; Dajing Li; Chunju Liu; Haiou Wang; Wenqian Pang; Liying Niu; Rui Yu; Xiyun Sun (Journal of Food Engineering, 2024)

Chemical looping gasification of lignite to syngas using phosphogypsum: Overview and prospects - Jie Yang; Changye Han; Lan Shao; Rui Nie; Senlin Dong; Hongpan Liu; Liping Ma (Journal of Cleaner Production, 2024)

Realizing synergy between pollution reduction and carbon mitigation in industrial parks: From model development to tool application - Yizheng Lyu; Lujun Chen; Jinping Tian; Rui Liu; Quan Zhou (Journal of Cleaner Production, 2024)

Titanium carbide-based nanocomposite: A promising reinforcing material for enzymatic CO2 conversion - Menglei Mao; Ruqing Chong; Feixue Sun; Rui Gao; Zihui Meng; Xinlong Fan; Wenfang Liu (Journal of Cleaner Production, 2024)

New insights into the interaction of sodium hexametaphosphate with coal slime and its application in the purification of kaolin - Chengwen Wang; Yanxiu Wang; Wei Sun; Runqing Liu; Yingdi Dong; Rui Xu; Dandan Huang; Le Tao (Journal of Cleaner Production, 2024)

Tracing spatial patterns of lacustrine groundwater discharge in a closed inland lake using stable isotopes - Xiaohui Ren; Ruihong Yu; Rui Wang; Jianfang Kang; Xiangwei Li; Pengxuan Zhang; Tingxi Liu (Journal of Environmental Management, 2024)

GPR-TransUNet: An improved TransUNet based on self-attention mechanism for ground penetrating radar inversion - Ge Junkai; Sun Huaifeng; Shao Wei; Liu Dong; Yao Yuhong; Zhang Yi; Liu Rui; Liu Shangbin (Journal of Applied Geophysics, 2024)

A quantitative model to estimate major oxide abundances on the Moon based on in situ reflectance spectral data of Chang'e missions - Zhenxing Zhao; Yazhou Yang; Xing Wu; Yang Liu; Feng Zhang; Rui Xu; Zhiping He; Yangting Lin; Yongliao Zou (Icarus, 2024)

The superior HDS catalyst derived from a new Waugh Co-Mo polyoxometalate via cationic substitution - Jilei Liang; Mengmeng Wu; Lu Qi; Shanqin Qian; Haiyun Rui; Yunqi Liu; Chenguang Liu (Fuel, 2024)

Effect of carbon modifier on characteristics and catalytic properties of zeolite–carbon hybrid supported Zr towards γ-valerolactone production - Zhongdi Liu; Rui Zhang; Huai Liu; Junhua Zhang; Yong Sun; Naya Li; Lincai Peng (Fuel, 2024)

Effect of Rhodotorula mucilaginosa inoculation on the aroma development of a fermented vegetables simulated system - Rui Wang; Yi Zeng; Jiaqian Liang; Huixin Zhang; Junjie Yi; Zhijiia Liu (Food Research International, 2024)

Open roads and bridge: Preservation of fresh beef by a packaging film constructed from photosensitizing bacterial cellulose - Rui Chen; Yajie Zhang; Zuwang Zhang; Lenan Yao; Lizhi Liu; Jianlong Wang; Rong Wang (Food Chemistry, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Dual stabilization of O/W/O double emulsions by proteins: An interfacial perspective - Zijian Zhi; Hao Li; Indi Geurs; Benny Lewille; Rui Liu; Paul Van der Meeren; Koen Dewettinck; Filip van Bockstaele (Food Hydrocolloids, 2024)

De-branching of starch molecules enhanced the complexation with chitosan and its potential utilization for delivering hydrophobic compounds - Min Liu; Min Zhuang; Dengdeng Li; Jinxu Fan; Rui Wang; Xuanyu Wang; Sheng Ke; Ming Ning; Zhongkai Zhou (Food Hydrocolloids, 2024)

Innovative multistep modifications of β-Lactoglobulin for enhanced emulsifying and antioxidant activities - Qingchun Zhang; Rui Wang; Jianfei He; Wei Tang; Jianhua Liu (Food Hydrocolloids, 2024)

Chlorogenic acid improves common carp (Cyprinus carpio) liver and intestinal health through Keap-1/Nrf2 and NF-κB signaling pathways: Growth performance, immune response and antioxidant capacity - Guo-Jun Shang; Si-ying Liu; Rui Zhu; Deng-Lai Li; Si-Tong Meng; Yin-tao Wang; Li-Fang Wu (Fish & Shellfish Immunology, 2024)

Occurrence, physicochemical properties and environmental behavior of polychlorinated dibenzothiophenes: A comprehensive review and future perspectives - Chunmeng Ye; Yong Tu; Hong Ling; Yong Chen; Yang Liu; Rui Zhang; Xuesheng Zhang (Environmental Research, 2024)

Exploration of natural processes and anthropogenic inputs by Zn isotopes in suspended particulate matter: A case study from the Lancang River in Southwest China - Yang Tang; Guilin Han; Rui Qu; Jinke Liu; Man Liu (Environmental Pollution, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Multi-task deep learning for large-scale buildings energy management - Rui Wang; Rakiba Rayhana; Majid Gholami; Omar E. Herrera; Zheng Liu; Walter Mérida (Energy and Buildings, 2024)

Effects of environmental and nutritional labels on the dietary choices of consumers: Evidence from China - Xue Sun; Rui Wang; Pan He; Beibei Liu (Environmental Impact Assessment Review, 2024)

Equilibrating provincial carbon increments for residential buildings in China under carbon peaking constraints - Liu Chen; Rui Li; Jinbo Zhang; Weiguang Cai; Kaiqiang Zhang; Yida Sun (Environmental Impact Assessment Review, 2024)

Efficient geo-electromagnetic modeling techniques for complex geological structures: A karst MT example - Minghong Liu; Huaifeng Sun; Rui Liu; Liqiang Hu; Ruijin Kong; Shangbin Liu (Computers & Geosciences, 2024)

A programmable quantum dot nanosensor guided by three-way junction skeleton-mediated cascade signal amplification for sensitive detection of circRNAs in breast cancer - Wen-jing Liu; Rui Song; Dongming Yang; Shulin Zhao; Chun-yang Zhang (Chemical Engineering Journal, 2024)

Chameleon-inspired supramolecular materials based on cucurbit[7]uril and viologens exhibiting full-color tunable photochromic behavior - Dong-Xue Xia; Xin Wang; Wen-Qi Sun; Rui-Lian Lin; Jing-Xin Liu; Ying-Wei Yang (Chemical Engineering Journal, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

Catalytic oxidation of VOCs and CO on cobalt-based Materials: Strategies and mechanisms for improving activity and stability - Yanfei Zheng; Weinuo Xu; Jining Yang; Cangpeng Shan; Yunchong Wang; Rui Han; Guolong Zang; Qingling Liu (Chemical Engineering Journal, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Fucosylated chondroitin sulfate from sea cucumber Stichopus chloronotus alleviate the intestinal barrier injury and oxidative stress damage in vitro and in vivo - Huanan Yin; Rui Li; Jing Liu; Yanying Sun; Lei Zhao; Jiaojiao Mou; Jie Yang (Carbohydrate Polymers, 2024)

Structural characterization and osteogenic differentiation-promoting activity of polysaccharide purified from Chroogomphus rutilus - Ying Zhou; Lanzhou Li; Zhen Sun; Rui Liu; Yanfeng Zhu; Jingzheng Yi; Yutong Li; Min Hu; Di Wang (Carbohydrate Polymers, 2024)

Experimental study on the dealkalization of red mud using the freeze-thaw and acid washing method - Dahu Rui; Mingpu Li; Mintae Kim; Jun Zhang; Wenjun Nie; Shuren Wang; Guoyu Li; Shengjie Liu (Cold Regions Science and Technology, 2024)

Biochar loaded with ferrihydrite and Bacillus pseudomycoides enhances remediation of co-existed Cd(II) and As(III) in solution - Rui Cao; Guodong Kang; Weiwen Zhang; Jihai Zhou; Wangliang Xie; Zhenzhen Liu; Li Xu; Feng Hu; Zhen Li; Huixin Li (Bioresource Technology, 2024)

Controlling airborne pathogen within Fangcang shelter hospitals: Aerodynamic analysis of bioaerosols released from various locations through experiment and simulation - Chuan Jiang; Zhijian Liu; Xia Xiao; Haiyang Liu; Junzhou He; Rui Rong; Jingwei Liu; Zhenzhe Huang; Yongxin Wang (Building and Environment, 2024)

Improving categorical and continuous accuracy of precipitation forecasts by integrating Empirical Quantile Mapping and Bernoulli-Gamma-Gaussian distribution - Lingjie Li; Zhaode Yun; Yong Liu; Yintang Wang; Wenpeng Zhao; Yan Kang; Rui Gao (Atmospheric Research, 2024)

Influence of atmospheric circulation on the stable isotope of precipitation in the monsoon margin region - Siyu Lu; Guofeng Zhu; Gaojia Meng; Xinrui Lin; Yuwei Liu; Dongdong Qiu; Yuanxiao Xu; Qinqin Wang; Longhu Chen; Rui Li; Yinying Jiao (Atmospheric Research, 2024)

Moment Tensor and Stress Field Inversions of Mining-Induced Seismicity in A Thick-Hard Roof Zone - Chun-Hui Song; Cai-Ping Lu; Hai-Quan Liu; Jie-Fang Song; Cheng-Yu Liu; Hua-Wei Cui; Jin-Rui Zhang (Rock Mechanics and Rock Engineering, 2024)

Data-Driven Approaches for Vibroacoustic Localization of Leaks in Water Distribution Networks - Rongsheng Liu; Salman Tariq; Ibrahim A. Tijani; Ali Fares; Beenish Bakhtawar; Harris Fan; Rui Zhang; Tarek Zayed (Environmental Processes, 2024)
This study aims to propose Micro-electromechanical System (MEMS) accelerometers for leak localization in the water distribution network and assess the performance of machine learning models in accurately estimating leak locations. Intensive field experimentation was conducted to collect data for model development. Machine learning algorithms were employed to develop leak localization models, specifically artificial neural network (ANN) and support vector machine (SVM). Seventeen time-domain and frequency-domain features were extracted, and feature selection was performed using the backward elimination method. The results indicate that the ANN and SVM models are suitable classifiers for localizing leak distance. Both models achieved leak location predictions with over 80% accuracy, and the mean absolute errors were measured at 0.858 and 0.95 for the ANN and SVM models, respectively. The validation results demonstrated that the models maintained accuracies close to 80% when the distance between sensors and the leak was less than 15 m. However, the performance of the model deteriorates when leaks occur at distances greater than 15 m. This study demonstrates the applicability of MEMS accelerometers for leak localization in water distribution networks. The findings highlight the promising potential of employing MEMS accelerometers-based ANN and SVM models for accurate leak localization in urban networks, even under real-world, uncontrolled conditions. However, the current model exhibits limited performance in long-distance leak localization, requiring further research to address and resolve this issue.

Summer electricity consumption and its drivers in urban areas - Feng Gao; Zhenzhi Jiao; Shunyi Liao; Rui Liu; Zhisai Hu; Yang Liu; Hongbao Li; Wangyang Chen; Xin Chen; Guanyao Li (Applied Geography, 2024)

Portable fluorescent lateral flow assay for ultrasensitive point-of-care analysis of acute myocardial infarction related microRNA - Junnan Zhao; Han Han; Zhenzhen Liu; Jin Chen; Xiaoxian Liu; Yinuo Sun; Bingwei Wang; Baohua Zhao; Yuanfeng Pang; Rui Xiao (Analytica Chimica Acta, 2024)

Simultaneous detection of dual microRNAs related to EV71 using ICP-MS based on metal nanoparticle labeling with hybridization chain reaction - Yuxin Wang; Lijun Shao; Zhigang Zhao; Chao Huang; Yanni Jiao; Dapeng Sun; Rui Liu; Dafeng Jiang; Xibao Gao (Analytica Chimica Acta, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Purification and Characterization of a Novel Anticoagulant Peptide from Protein Hydrolysate of Eupolyphaga sinensis Walker - Xidong Li; Xuefei Zhuang; Huifen Li; Linmei Pan; Rui Liu; Huaxu Zhu; Zhishu Tang (International Journal of Peptide Research and Therapeutics, 2024)

Bibliometric analysis on mercury emissions from coal-fired power plants: a systematic review and future prospect - Qi Liu; Jiajia Gao; Guoliang Li; Yang Zheng; Rui Li; Tao Yue (Environmental Science and Pollution Research, 2024)

Green growth path dependence momentum under the prism of COP26: the role of financial deepening, ICT development, and export diversification - Rui Hu; Baodan Liu; Sidra Sohail (Environmental Science and Pollution Research, 2024)

Enhancing ENSO predictions with self-attention ConvLSTM and temporal embeddings - Chuang Rui; Zhengya Sun; Wensheng Zhang; An-An Liu; Zhiqiang Wei (Frontiers in Marine Science, 2024)
El Niño-Southern Oscillation (ENSO), a cyclic climate phenomenon spanning interannual and decadal timescales, exerts substantial impacts on the global weather patterns and ecosystems. Recently, deep learning has brought considerable advances in the accurate prediction of ENSO occurrence. However, the current models are insufficient to characterize the evolutionary behavior of the ENSO, particularly lacking comprehensive modeling of local-range and longrange spatiotemporal interdependencies, and the incorporation of calendar monthly and seasonal properties. To make up this gap, we propose a Two-Stage SpatioTemporal (TSST) autoregressive model that couples the meteorological factor prediction with ENSO indicator prediction. The first stage predicts the meteorological time series by leveraging self-attention ConvLSTM network which captures both the local and the global spatial-temporal dependencies. The temporal embeddings of calendar months and seasonal information are further incorporated to preserves repeatedly-occurring-yet-hidden patterns in meteorological series. The second stage uses multiple layers to extract higher level of features from predicted meteorological factors progressively to generate ENSO indicators. The results demonstrate that our model outperforms the state-of-the-art ENSO prediction models, effectively predicting ENSO up to 24 months and mitigating the spring predictability barrier.

The residues and health risk assessment of polychlorinated biphenyls (PCBs) in Pheretima (an earthworm-derived traditional medicine) from southeastern China - Yun-Jing Zhang; Jing Sun; Xiao-Jiang Chen; Rui Cheng; Zhi-Tong Liu; Ling Cao; You-Long Feng (Environmental Science and Pollution Research, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

In silico prediction and a systematic toxicology-based in vivo investigation uncovering the mechanism of aquatic toxicity caused by beta-lactam antibiotics - Ruixian Guo; Xinyan Ma; Huibo Xu; Yuanyuan Ma; Rui Zhang; Xinyan Liu; Binan Lu; Jingpu Zhang; Ying Han (Chemosphere, 2024)

Improved binocular localization of kiwifruit in orchard based on fruit and calyx detection using YOLOv5x for robotic picking - Changqing Gao; Hanhui Jiang; Xiaojuan Liu; Haihong Li; Zhenchao Wu; Xiaoming Sun; Leilei He; Wulan Mao; Yaqoob Majeed; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Neonicotinoids: Advances in hazards of residues, screening of aptamers and design of aptasensors - Jingcheng Huang; Haifang Wang; Haowei Dong; Mengyue Liu; Lingjun Geng; Jiashuai Sun; Zhen Guo; Rui Xu; Giovanna Marrazza; Xia Sun; Yemin Guo (Trends in Food Science & Technology, 2024)

Failure mechanism of rock masses with complex geological conditions in a large underground cavern: A case study - Jin-Shuai Zhao; Shu-Qian Duan; Bing-Rui Chen; Lei Li; Ben-Guo He; Peng-Xiang Li; Guo-Feng Liu (Soil Dynamics and Earthquake Engineering, 2024)

Seismic performance of LNG tanks in deep soil site considering soil-foundation-structure interaction - Zaixian Li; Su Chen; Rui Zhang; Xiang Liu; Xiaojun Li (Soil Dynamics and Earthquake Engineering, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Reproducibility in nontarget screening (NTS) of environmental emerging contaminants: Assessing different HLB SPE cartridges and instruments - Wenhao Jia; He Liu; Yini Ma; Guolong Huang; Yaxiong Liu; Bo Zhao; Danping Xie; Kaibo Huang; Rui Wang (Science of The Total Environment, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

Impacts of climate change and human activity on the potential distribution of Aconitum leucostomum in China - Li Xu; Yuan Fan; Jianghua Zheng; Jingyun Guan; Jun Lin; Jianguo Wu; Liang Liu; Rui Wu; Yujia Liu (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Satellite observed aboveground carbon dynamics in Africa during 2003–2021 - Mengjia Wang; Philippe Ciais; Rasmus Fensholt; Martin Brandt; Shengli Tao; Wei Li; Lei Fan; Frédéric Frappart; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; et al. (Remote Sensing of Environment, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Effects of ultrasound-assisted cooking on the physicochemical properties and microstructure of pork meatballs - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Meat Science, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Dispersion of sandy sediments during marine–continental transition: An integrated study from the Late Paleozoic western Ordos Basin - Zhiwei Wang; Lei Liu; Jianling Hu; Feng Wang; Dan Li; Jingqi Zhang; Shuyue Zhu; Rui Zhang; Fei Zhao; Chenggong Zhang; Siyi Fu; Hongde Chen (Marine and Petroleum Geology, 2024)

CO2 storage capacity estimation by considering CO2 Dissolution: A case study in a depleted gas Reservoir, China - Youwei He; Mengyun Liu; Yong Tang; Cunqi Jia; Yong Wang; Zhenhua Rui (Journal of Hydrology, 2024)

The effect of climate oscillations on skipjack tuna (Katsuwonus pelamis) in the Indian Ocean - Shigang Liu; Liyan Zhang; Rui Wang; Puqing Song; Xing Miao; Hai Li; Yuan Li; Longshan Lin (Journal of Marine Systems, 2024)

Individual ambient ozone exposure during pregnancy and adverse birth outcomes: Exploration of the potentially vulnerable windows - Chenqing Zhang; Jie Yang; Jing Wei; Yuansheng Liu; Huiping Zhu; Xiaobo Li; Jiajia Wang; Rui Chen (Journal of Hazardous Materials, 2024)

Novel vacuum UV/ozone/peroxymonosulfate process for efficient degradation of levofloxacin: Performance evaluation and mechanism insight - Jinying Du; Chuang Wang; Meilin Sun; Guoliang Chen; Chenglin Liu; Xiaoyong Deng; Rui Chen; Zhiwei Zhao (Journal of Hazardous Materials, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Soy protein isolate amyloid fibril-coated ZrO2 nanoparticles anchored in the polyurethane sponge for rapid and effective fluoride adsorption in the wide pH range - Wenjing Lu; Chunhui Zhang; Zhiwei Lin; Peidong Su; Zhaowei Qin; Xuezhi Li; Rui Wang; Yunchang Liu; Peiyao Luo; Kepeng Qiu (Journal of Environmental Chemical Engineering, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Analysis of soot formation and oxidation processes in the diesel engine fueled by n-octanol/biodiesel blends based on a detailed soot population balance model - Jing Li; Shiqi Gong; Yifei Liang; Shaohua Wu; Rui Liu; Wenming Yang (Fuel, 2024)

High temperature reduction of divalent mercury to elemental mercury for Hg-CEMS - Haiyang Li; Lina Sun; Xiaoshuo Liu; Xunlei Ding; Ao Shen; Rui Jin; Jiangyi Tong; Haitao Hu; Yufeng Duan (Fuel, 2024)

Numerical investigation on the spray characteristics of biodiesel with gas-assisted atomization injection - Rui Liu; Lingfeng Zhong; Songhong Li; Jing Li; Haocheng Ji (Fuel, 2024)

Evolution of carbon deposits during ethylene aromatization over Zn/ZSM-5 - Rui Geng; Yacong Liu; Yanxia Guo; Mei Dong; Sen Wang; Weibin Fan; Jianguo Wang; Zhangfeng Qin (Fuel, 2024)

Experimental study on the mass burning rate and flame tilt angle of annular pool fires under cross air flow - Ping Huang; Rui Zhang; Chunxiang Liu; Xinyue Wu; Shanshan Chen; Jinhao Li; Man Li; Longxing Yu (Fuel, 2024)

Physicochemical, microbiological and metabolomics changes in yogurt supplemented with lactosucrose - Rui Xue; Jing Liu; Min Zhang; Tariq Aziz; Shifa Felemban; Manal M Khowdiary; Zhennai Yang (Food Research International, 2024)

Fermentation enhances the amelioration effect of bee pollen on Caco-2 monolayer epithelial barrier dysfunction based on NF-κB-mediated MLCK-MLC signaling pathway - Huifang Zhang; Min Liu; Fanfen Song; Xiaoling Zhu; Qun Lu; Rui Liu (Food Research International, 2024)

Differentiation of antioxidants in reducing oxidation and improving quality of ready-to-eat roasted shrimp after thermal sterilization - Shuo Wang; Songyi Lin; Rui Liang; Kexin Liu; Xiuhan Chen; Lei Chen; Shuang Li; Na Sun (Food Chemistry, 2024)

Enhanced O/W emulsion stability and betanin protection using yeast protein and chitooligosaccharide: Comparative insights from complex coacervation and layer-by-layer methods - Jiangnan Hu; Rui Yang; Runxuan Chen; Chang Liu; Xinmei Sha; Ku Li; Hui Guo; Yuyu Zhang (Food Hydrocolloids, 2024)

GC-IMS determination of volatile organic compounds as potential indicators of wheat germination rate - Yu Liu; Shuwei Ren; Qianqian Sun; Boli Guo; Yingquan Zhang; Ming Li; Rui Zhang (Food Bioscience, 2024)

TRPML1 contributes to antimony-induced nephrotoxicity by initiating ferroptosis via chaperone-mediated autophagy - Lei Liu; Chao Luo; Dongnan Zheng; Xuehai Wang; Rui Wang; Wenjie Ding; Zhaoping Shen; Peng Xue; Shali Yu; Yifei Liu; Xinyuan Zhao (Food and Chemical Toxicology, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Microbial community of municipal drinking water in Hangzhou using metagenomic sequencing - Wei Lan; Haiyang Liu; Rui Weng; Yaxiong Zeng; Jian Lou; Hongxin Xu; Yunsong Yu; Yan Jiang (Environmental Pollution, 2024)

Antagonistic effect of mercury and excess nitrogen exposure reveals provenance-specific phytoremediation potential of black locust–rhizobia symbiosis - Rui Liu; Bin Hu; Emmanouil Flemetakis; Michael Dannenmann; Christoph-Martin Geilfus; Robert Haensch; Dingyong Wang; Heinz Rennenberg (Environmental Pollution, 2024)

Refined three-dimensional pile element formulation for second-order analysis of pile-supported structures accounting for complex loading conditions - Weihang Ouyang; Rui Bai; Si-Wei Liu; Siu-Lai Chan (Engineering Structures, 2024)

Superfast hydrous-molten salt erosion to fabricate large-size self-supported electrodes for industrial-level current OER - Jie Deng; Zhichao Wang; Hao Yang; Rui Jian; Yufeng Zhang; Ping Xia; Wei Liu; Olivier Fontaine; Yachao Zhu; Luming Li; Si Chen (Chemical Engineering Journal, 2024)

Hollow-adjustable polymer microneedles for prolonged hypoglycemic effect on diabetic rats - Tianqi Liu; Yanfang Sun; Wenjing Zhang; Rui Wang; Xinyu Lv; Lei Nie; Amin Shavandi; Khaydar E. Yunusov; Guohua Jiang (Chemical Engineering Journal, 2024)

Boosting ion diffusion kinetics of Fe2O3/MoC@NG via heterointerface engineering and pseudocapacitance behavior: An alternative high-rate anode for high‐capacity lithium dual-ion batteries - Juan Ding; Yudai Huang; Wenhua Cheng; Rui Sheng; Zhenjie Liu; Xingchao Wang; Yong Guo; Jiulin Wang; Dianzeng Jia; Xincun Tang; Lei Wang (Chemical Engineering Journal, 2024)

Pretreatment greatly facilitates ethyl levulinate production from catalytic alcoholysis of Napier grass stem - Huai Liu; Yanping Kong; Weipeng Song; Rui Zhang; Junhua Zhang; Yong Sun; Lincai Peng (Chemical Engineering Journal, 2024)

High-performance Bi0.4Sb1.6Te3 alloy prepared by a low-cost method for wearable real-time power supply and local cooling - Xingzhong Zhang; Ziyu Wang; Yue Hou; Yong Liu; Liangwei Hu; Wenhao Xie; Jing Shi; Jianhong Wei; Rui Xiong (Chemical Engineering Journal, 2024)

Microbial response and spatial profiling of nitrite-producing denitrification granular sludge in-situ exposed to high nitrite stress - Jiarui Fan; Rui Du; Qingtao Liu; Cong Li; Yongzhen Peng (Chemical Engineering Journal, 2024)

Impact of pretreatment with photocatalysis sequential coupling Fenton oxidation on physicochemical properties, pyrolysis behaviors, and product distribution of walnut shell - Rui Wang; Zhuwei Liu; Lin Li; Yuanyuan Zhang; Qing Dong; Zengguang Huang; Qiang Cheng (Chemical Engineering Journal, 2024)

Two birds with one stone: Gold “bridging” both nanozyme and immunosensor for sensitive double-response detection of T-2 toxin - Rui Shu; Sijie Liu; Cong Zhao; Xi Lan; Yuechun Li; Jianlong Wang; Nannan Qiu; Daohong Zhang (Chemical Engineering Journal, 2024)

Synthesis of n-butanol from ethanol over Pt-Y/beta catalyst: Synergistic catalysis of yttrium and platinum site - Haowei Liu; Tao Zheng; Tianli Hui; Rui Zhang; Xianghai Meng; Wenshuai Zhu; Haiyan Liu; Zhichang Liu (Chemical Engineering Journal, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

Improving bioelectrochemical performance by sulfur-doped titanium dioxide cooperated with Zirconium based metal–organic framework (S-TiO2@MOF-808) as cathode in microbial fuel cells - Qin Qi; Guofu Huang; Rui Li; Jiale Yu; Xiaomin Chen; Zhen Liu; Yanyan Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2024)

Anaerobic co-fermentation of waste activated sludge with corn gluten meal enhanced phosphorus release and volatile fatty acids production: Critical role of corn gluten meal dosage on fermentation stages and microbial community traits - Zhipeng Zhang; Rui Liu; Yaqiong Lan; Wei Zheng; Lujun Chen (Bioresource Technology, 2024)

Nitrogen removal characteristics of novel bacterium Klebsiella sp. TSH15 by assimilatory/dissimilatory nitrate reduction and ammonia assimilation - Jilong Ren; Jiajun Tang; Hongping Min; Dingding Tang; Rui Jiang; Yanchen Liu; Xia Huang (Bioresource Technology, 2024)

Short-term exposure to ambient air pollution and hospital admissions for angina among older adults in South China - Luxi Xu; Ruijun Xu; Yunshao Ye; Rui Wang; Jing Wei; Chunxiang Shi; Qiaoxuan Lin; Ziquan Lv; Suli Huang; Qi Tian; Yuewei Liu (Atmospheric Environment, 2024)

Analysis of emission evolution and synergistic reduction effect of air pollutants and CO2 from Chinese coal-fired power plants - Tao Yue; Qi Liu; Yali Tong; Jiajia Gao; Yang Zheng; Guoliang Li; Rui Li (Atmospheric Pollution Research, 2024)

Cycloaspeptide H, a cyclopentapeptide from the endophytic fungus Penicillium virgatum - Ben-Chao Li; Liu-Xia Lv; Li-Li Huang; Jia-Tong Zhou; Xi-Shan Huang; Jun Li; Rui-Yun Yang; Wei-Feng Xu (Natural Product Research, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Hydrogen sulfide promoted cell differentiation, antioxidant ability, and flavonoids accumulation in Ginkgo biloba L. suspension cells - Jin-ling Lu; Yu-chen Hu; Ying Chen; Rui Liu; Jing-jing Di; Ting-ting Feng; Fu-liang Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Progress in the Application of Microneedles in Eye Disorders and the Proposal of the Upgraded Microneedle with Spinule - Qiannan Yang; Tingting Zhang; Yujie Wu; Qianyue Liang; Wanqi Zhao; Rui Liu; Xin Jin (Pharmaceutical Research, 2024)

Investigating the Immunogenic Cell Death-Dependent Subtypes and Prognostic Signature of Triple-Negative Breast Cancer - Youyang Shi; Yuanyuan Wu; Feifei Li; Kexin Jiang; Xiaofang Fang; Yu Wang; Xiaoyun Song; Rui Wang; Lixin Chen; Jinzhou Zheng; Chunyu Wu; Yuenong Qin; et al. (Phenomics, 2024)

Polarization induced covalent/hydrogen bonding adsorption of NH4+ and K+ in soils: comparison study on permanently and variably charged soils - Dian Liu; Rui Tian; Xinmin Liu; Hang Li (Journal of Soils and Sediments, 2024)

Quercetin improved hepatic circadian rhythm dysfunction in middle-aged mice fed with vitamin D-deficient diet - Rui Li; Guiping Wang; Ruitong Liu; Lan Luo; Ying Zhang; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2024)

Integrating bulk-RNA sequencing and single-cell sequencing analyses to characterize adenosine-enriched tumor microenvironment landscape and develop an adenosine-related prognostic signature predicting immunotherapy in lung adenocarcinoma - Tao Han; Jing Wu; Yafeng Liu; Jiawei Zhou; Rui Miao; Jianqiang Guo; Zhi Xu; Yingru Xing; Ying Bai; Dong Hu (Functional & Integrative Genomics, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Risk assessment and source identification of soil heavy metals: a case study of farmland soil along a river in the southeast of a mining area in Southwest China - Huajian Chi; Xin Liu; Xiaofang Yang; Rui Zhang; Ting Xia; Yiping Sun; Kan Hu; Fangfang Hao; Yong Liu; Shengchun Yang; Qingwen Deng; Xiaodong Wen (Environmental Geochemistry and Health, 2024)

Blood Pressure Estimation Based on PPG and ECG Signals Using Knowledge Distillation - Hui Tang; Gang Ma; Lishen Qiu; Lesong Zheng; Rui Bao; Jing Liu; Lirong Wang (Cardiovascular Engineering and Technology, 2024)

Seismic performance of a nonhomogeneous slope reinforced by anchored piles using centrifuge tests - Tong Zheng; Qiangqiang Sun; Hongshuai Liu; Wenhao Qi; Rui Sun (Bulletin of Engineering Geology and the Environment, 2024)

Competition for nitrogen between plants and microorganisms in grasslands: effect of nitrogen application rate and plant acquisition strategy - Li Zhang; Jie Liu; Jiazhen Xi; Rui Pang; Anna Gunina; Shurong Zhou (Biology and Fertility of Soils, 2024)

Problem identification and revitalization strategies for the recovery and reconstruction of traditional villages in the Ms 6.8 Luding Earthquake - Chao Huang; Jian Qiu; Chun Liu; Rui Jiang; Chuanrong Zhao; Yi Zhang (Journal of Mountain Science, 2024)

Tourism development potential and obstacle factors of cultural heritage: Evidence from traditional music in Xiangxi - Xianyong Zhang; Baofa Peng; Lulu Zhou; Chunyang Lu; Yali Wang; Rui Liu; Hui Xiang (Journal of Geographical Sciences, 2024)

Dynamic Effect of Landslides Triggered by Earthquake: A Case Study in Moxi Town of Luding County, China - Hongfu Zhou; Fei Ye; Wenxi Fu; Bin Liu; Tian Fang; Rui Li (Journal of Earth Science, 2024)

SLCO1B1 Polymorphisms are Associated with the Susceptibility to Pulmonary Tuberculosis in Chinese Females - Wei Li; Wei Liu; Xiong Wang; Rui Dou; Zunmin Zhu (Biochemical Genetics, 2024)

Molecular characterization of a novel mycovirus from binucleate Rhizoctonia AG-A strain A46 - Rui Shi; Xiaohan Mo; Zebin Chen; Wurong Chen; Shuhui Yu; He Liu; Yuchuan Li; Lili Dai; Yanqiong Li (Archives of Virology, 2024)

Speciation analysis and toxicity evaluation of arsenolipids—an overview focusing on sea food - Caiyan Li; Jing Chen; Zhuo Wang; Bingbing Song; Kit-Leong Cheung; Jianping Chen; Rui Li; Xiaofei Liu; Xuejing Jia; Sai-Yi Zhong (Archives of Toxicology, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Super Resolution Mapping of Scatterometer Ocean Surface Wind Speed Using Generative Adversarial Network: Experiments in the Southern China Sea - Xianci Wan; Baojian Liu; Zhizhou Guo; Zhenghuan Xia; Tao Zhang; Rui Ji; Wei Wan (Journal of Marine Science and Engineering, 2024)
This paper designed a Generative Adversarial Network (GAN)-based super-resolution framework for scatterometer ocean surface wind speed (OSWS) mapping. An improved GAN, WSGAN, was well-trained to generate high-resolution OSWS (~1/64 km) from low-resolution OSWS (~12.5 km) retrieved from scatterometer observations. The generator of GAN incorporated Synthetic Aperture Radar (SAR) information in the training phase. Therefore, the pre-trained model could reconstruct high-resolution OSWS with historical local spatial and texture information. The training experiments were executed in the South China Sea using the OSWS generated from the Advanced SCATterometer (ASCAT) scatterometer and Sentinel-1 SAR OSWS set. Several GAN-based methods were compared, and WSGAN performed the best in most sea states, enabling more detail mining with fewer checkerboard artifacts at a scale factor of eight. The model reaches an overall root mean square error (RMSE) of 0.81 m/s and an overall mean absolute error (MAE) of 0.68 m/s in the collocation region of ASCAT and Sentinel-1. The model also exhibits excellent generalization capability in another scatterometer with an overall RMSE of 1.11 m/s. This study benefits high-resolution OSWS users when no SAR observation is available.

Boron removal in seawater desalination by progressive freezing-melting - Rui Mei; Tongguo Zhao; Yan Zhang; Hao Lin; Chen Zhao; Lin Lin; Yihong Zou; Yucan Liu (Environmental Science and Pollution Research, 2024)

A new method for preventing sidewall preferential flow in the internal erosion simulation using un-resolved CFD–DEM - Leilei Liu; Rui Chen; Zhaofeng Li; Chao Zhou; Xiaojiao Li (Acta Geophysica, 2024)
Accurately assessing the erodibility of geomaterials is of great significance for the design of earthen structures and the prevention of the associated failure induced by seepage force. Recently, the un-resolved Computational Fluid Dynamics–Discrete Element Method (CFD–DEM) has been widely used to investigate internal erosion. However, due to the use of wall boundary and the fact that the fixed CFD domain cannot be changed with the soil sample’s volume contraction during the erosion test, a larger porosity at the boundary of the CFD domain is commonly formed, resulting in sidewall preferential flow (i.e., relatively more fine particles migrate along the boundary of the DEM domain) and thereby overestimating the soil erodibility. In this study, a new method based on particle boundary is developed to tackle this problem. The newly proposed particle boundary can prevent its particles from erosion via inter-particle bonding and transfer stress from servo walls to the simulated sample. An optimal particle boundary thickness is determined by considering sample contraction and computational efficiency. The performance of the new method was compared with the conventional method and also verified using experimental results. The results show that the newly proposed method has significantly improved the uniformity of fluid velocity distribution. Furthermore, the cumulative eroded mass of fine particles in the new model is approximately 15% lower than in the conventional model. It is convincingly demonstrated that the new method can simulate internal erosion better and give a more accurate assessment of geomaterial erodibility.

New 4',5'-methylenedioxyflavone derivatives from the whole plant of sarcandra glabra - Ya-Qiu Qin; Wei Liu; Rui Yin; Ping-Ting Xiao; Zi-Yuan Wang; Tian-Qing Huang; E-Hu Liu (Natural Product Research, 2024)

Effect of inorganic anions on hydrothermal removal of impurities Fe/Al from Cu-bearing polymetallic leachate - Ting Su; Fanrong Kong; Yu Chen; Jiancong Liu; Rui Bian; Suiyi Zhu (Environmental Science and Pollution Research, 2024)

Burning and plume flow behaviors of annular pool fires: with and without air entrainment through the pool center - Ping Huang; Rui Zhang; Chunxiang Liu; Xinyue Wu; Dimin Chen; Shanshan Chen; Longxing Yu (Environmental Science and Pollution Research, 2024)

Simultaneous realization of heavy metal Cd solidification and chloride separation in municipal solid waste incineration fly ash: Mechanism and DFT analysis - Fuli Liu; Ze Liu; Yu Gao; Rui Liu; Dongmin Wang; Baomin Wang; Yan You (Chemosphere, 2024)

Consequences of excess urea application on photosynthetic characteristics and nitrogen metabolism of Robinia pseudoacacia seedlings - Yong Zhang; Rui Liu; Zhenshan Liu; Yanping Hu; Zhuyuan Xia; Bin Hu; Heinz Rennenberg (Chemosphere, 2024)

Mitigating cadmium accumulation in dicotyledonous vegetables by iron fertilizer through inhibiting Fe transporter IRT1-mediated Cd uptake - Zhong-Rui Xu; Ting-Ting You; Wen-Yi Liu; Kang Ye; Fang-Jie Zhao; Peng Wang (Chemosphere, 2024)

3D-based precise evaluation pipeline for maize ear rot using multi-view stereo reconstruction and point cloud semantic segmentation - Rui Yang; Yong He; Xiangyu Lu; Yiying Zhao; Yanmei Li; Yinhui Yang; Wenwen Kong; Fei Liu (Computers and Electronics in Agriculture, 2024)

Cation exchange resins enhance anaerobic digestion of sewage sludge: Roles in sequential recovery of hydrogen and methane - Hui Geng; Ying Xu; Rui Liu; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Influences of hydrodynamics on microbial community assembly and organic carbon composition of resuspended sediments in shallow marginal seas - Yangli Che; Chaoran Lin; Shen Li; Jiao Liu; Longhai Zhu; Shilei Yu; Nan Wang; Haoshuai Li; Mutai Bao; Yang Zhou; Tonghao Si; Rui Bao (Water Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Prediction interaction responses between railway subgrade and shield tunnelling using machine learning with sparrow search algorithm - Xiang Liu; Kuichen Li; Annan Jiang; Qian Fang; Rui Zhang (Transportation Geotechnics, 2024)

Methane emission reduction in China's natural gas industry: Construction of technology inventory and selection of optimal technology programs - Nu Li; Jianliang Wang; Rui Liu; Mikael Höök (Sustainable Production and Consumption, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Analysis of water quality influencing factors under multi-source data fusion based on PLS-SEM model: An example of East-Liao River in China - Mula Na; Xingpeng Liu; Zhijun Tong; Bilige Sudu; Jiquan Zhang; Rui Wang (Science of The Total Environment, 2024)

Microbial traits drive soil priming effect in response to nitrogen addition along an alpine forest elevation gradient - Tiantian Ma; Yabin Zhan; Wenjie Chen; Zhuonan Hou; Shengyang Chai; Junling Zhang; Xinjun Zhang; Ruihong Wang; Rui Liu; Yuquan Wei (Science of The Total Environment, 2024)

Assessment for the data processing performance of non-target screening analysis based on high-resolution mass spectrometry - He Liu; Rui Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2024)

Inhibition of algal blooms by residual antibiotics in aquatic environments: Design, screening, and validation of antibiotic alternatives - Jianglong Ling; Yong Niu; Di Liu; Rui Li; Ye Ruan; Xixi Li (Science of The Total Environment, 2024)

Emission characteristics of intermediate volatility organic compounds from a Chinese gasoline engine under varied operating conditions: Influence of fuel, velocity, torque, rotational speed, and after-treatment device - Rongzhi Tang; Song Guo; Kai Song; Ying Yu; Rui Tan; Hui Wang; Kefan Liu; Ruizhe Shen; Shiyi Chen; Limin Zeng; Zhou Zhang; Wenbin Zhang; et al. (Science of The Total Environment, 2024)

Fungus reduces tetracycline-resistant genes in manure treatment by predation of bacteria - Lei Liu; Qianxi Yin; Yu Hou; Rui Ma; Yi Li; Zhenyu Wang; Ganggang Yang; Yu Liu; Hailei Wang (Science of The Total Environment, 2024)

Emission characteristics, environmental impact, and health risk assessment of volatile organic compounds (VOCs) during manicure processes - Run Hao; Jianling Sun; Rui Liu; Huan Zhao; Zhen Yao; Hailin Wang; Zhengping Hao (Science of The Total Environment, 2024)

Forager-farmer transition at the crossroads of East and Southeast Asia 4900 years ago - Minmin Ma; Minxia Lu; Rui Sun; Zhonghua Zhu; Dorian Q. Fuller; Jianxin Guo; Guanglin He; Xiaomin Yang; Lingling Tan; Yongxiu Lu; Jiajia Dong; Ruiliang Liu; et al. (Science Bulletin, 2024)

Characteristics of quartz grains in the middle and lower reaches of the Hutubi River, NW China, and its paleo-environmental significance - Dianjia Tan; Yunqiang Ma; Zhizhong Li; Jianhui Jin; Rui Liu; Xiaojun Zou; Tonglian Tao (Sedimentary Geology, 2024)

Nano-selenium repaired the damage caused by fungicides on strawberry flavor quality and antioxidant capacity by regulating ABA biosynthesis and ripening-related transcription factors - Yuping Liu; Rui Liu; Feifei Li; Simin Yu; Yufan Nie; Jia-Qi Li; Canping Pan; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Pesticide Biochemistry and Physiology, 2024)

Effect of a rotatable water-drop plate on vortex-induced vibration of cylinder - Boyang Li; Yongjian Zhong; Baoshou Zhang; Rui Zhang; Yaqi Liu; Jie Lu; Canpeng Li (Ocean Engineering, 2024)

Evolution of Silurian phytogeography, with the first report of Aberlemnia (Rhyniopsida) from the Pridoli of West Junggar, Xinjiang, China - Bing-Cai Liu; Rui-Wen Zong; Kai Wang; Jiao Bai; Yi Wang; Hong-He Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Revealing the membrane fouling behavior and interfacial interaction mechanism in a combined visible light photocatalysis-ultrafiltration system for advanced purification of NOM - Rui Yu; Yanling Yang; Liping Tian; Xing Li; Chunjiao Liu; Tianjie Sun; Haiqing Chang; Zhiwei Zhou (Journal of Water Process Engineering, 2024)

Spatial and temporal distribution of the microbial community structure in the receiving rivers of the middle and lower reaches of the Yangtze River under the influence of different wastewater types - Rui Bian; Shier Huang; Xiaofeng Cao; Weixiao Qi; Jianfeng Peng; Huijuan Liu; Xinghua Wu; Chong Li; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Degradation profile of environmental pollutant 17β-estradiol by human intestinal fungus Aspergillus niger RG13B1 and characterization of genes involved in its degradation - Qi-Meng Zhu; Chao Wang; Jing-Wen Liu; Rui Zhang; Xiu-Lan Xin; Juan Zhang; Cheng-Peng Sun; Xiao-Chi Ma (Journal of Hazardous Materials, 2024)

A photo-enzyme coupled system for carbon dioxide conversion to solar fuel: The rate-matching and compatibility between photocatalysis and enzyme catalysis - Qiyong Liao; Rui Gao; Feixue Sun; Ruqing Chong; Zihui Meng; Wenfang Liu (Journal of Cleaner Production, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Digital economy, structural deviation, and regional carbon emissions - Bo Xie; Rui Liu; Rajeev Dwivedi (Journal of Cleaner Production, 2024)

Inactivation of pathogenic microorganisms in water by electron beam excitation multi-wavelength ultraviolet irradiation: Efficiency, influence factors and mechanism - Yong-Qiang Li; Rui Sun; Chong-Miao Zhang; Zi-Xuan Liu; Rui-tao Chen; Jian Zhao; Hua-dong Gu; Huan-Cai Yin (Journal of Environmental Management, 2024)

Natural terpene-based derivatives to control postharvest sclerotinia rot and the involved potential mechanism - Jiuhui Ye; Xin Liu; Rui Zhou; Tuoping Hui; Jian Li; Juntao Feng; Zhiqing Ma; Yanqing Gao (International Journal of Food Microbiology, 2024)

Selective solvent extraction of Cu(II) from aqueous solutions using an acyl-based thiourea: Extraction study and DFT analysis of reaction mechanism - Xiaoping Huang; Kai Jin; Ruyi Zhang; Yutao Gong; Jianxian Zeng; Rui Zhang; Yuan Liu; Jianrong Xue (Hydrometallurgy, 2024)

Research progress on the construction of oxygen vacancy defects and application in photocatalytic oxidation of elemental mercury - Xin Yang; Zijian Xiang; Jiang Wu; Ping He; Yongfeng Qi; Shuo Chen; Yizheng Lu; Rui Xie; Zhengyu Liu; Chuman He (Fuel, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

A metabolomics discrimination-based strategy for screening the antithrombin active markers of perilla seeds: A natural oil crop - Suyi Liu; Xingyue Jin; Rui Wang; Xue Meng; Kunze Du; Jin Li; Xiumei Gao; Yanxu Chang (Food Chemistry, 2024)

Electrospinning is a potential way for preparing edible plant protein-based nanofibers with porous surface using safflower seed meal - Yanling Yang; Chuang Peng; Dong Zeng; Zhengjie Yang; Xiaohu Wang; Shuang Zhang; Yucheng Bai; Lujing Kuang; Lizhi Guo; Yonghua Qin; Hairong Xiong; Jiawei Wan; et al. (Food Hydrocolloids, 2024)

Identification of large yellow croakers (Larimichthys crocea) scavenger receptor genes: Involvement in immune response to Pseudomonas plecoglossicida infection and hypoxia-exposure experiments - Xuanyang Sun; Ning Bao; Chen Rui; Yadong Xue; Qian Fang; Tianyu Zheng; Ziyang Lin; Xiumei Liu; Xubo Wang (Fish & Shellfish Immunology, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

New insights into micro-algal astaxanthin's effect on deoxynivalenol-induced spleen lymphocytes pyroptosis in Cyprinus carpio: Involving mitophagy and mtROS-NF-κB-dependent NLRP3 inflammasome - Lei Diao; Wenjie Liu; Yawei Xu; Bin Zhang; Lingnan Meng; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2024)

Synthesis of amorphous-MnO2/Clinoptilolite and its utilization for NH4+-N oxidation in an anoxic environment - Caocong Liu; Yiyuan Zhuo; Yuzhe Chen; Yuanxiang Mao; Qiushi Shen; Jiangsen Ma; Rui Ma; Linsong Cheng; Fangying Ji; Xiaoyi Xu (Environmental Research, 2024)

Influence of mineralized organic carbon in marine sediments on ecological heavy metal risk: Bohai Bay case study - Congxiao Li; Yan Zhang; Rui Chen; Nayu Wang; Jingjing Liu; Fude Liu (Environmental Research, 2024)

Migration pathway and solidification mechanism of heavy metal Pb during the conversion of municipal solid waste incineration fly ash into ettringite and simultaneously purification of chloride salts solution process - Fuli Liu; Ze Liu; Yu Gao; Rui Liu; Dongmin Wang; Baomin Wang; Yan You (Environmental Pollution, 2024)

Effects of UHPC shear key on strengthening shear performances of wet joint in prefabricated composite beams - Hao Wang; Ning Wang; Xiao-gang Liu; Qing-rui Yue; Jing-liang Yan; Yu Zhang (Engineering Structures, 2024)

Decomposition and decoupling analysis of carbon emissions in China's construction industry using the generalized Divisia index method - Yuan Liu; Lei Gan; Weiguang Cai; Rui Li (Environmental Impact Assessment Review, 2024)

Membrane fouling mitigation and EPS reduction by CNTs-TiO2-PEDOT modified anode-membrane in Membrane Electro-Bioreactor (MEBR) treating mariculture wastewater - Jing Song; Yihan Li; Shihan Wang; Rui Han; Yu Ba; Ying Liu; Shengqiang Fan (Desalination, 2024)

Polyrate 2023: A computer program for the calculation of chemical reaction rates for polyatomics. New version announcement - Rubén Meana-Pañeda; Jingjing Zheng; Junwei Lucas Bao; Shuxia Zhang; Benjamin J. Lynch; José C. Corchado; Yao-Yuan Chuang; Patton L. Fast; Wei-Ping Hu; Yi-Ping Liu; Gillian C. Lynch; Kiet A. Nguyen; et al. (Computer Physics Communications, 2024)

Expansive microbial metabolic versatility and spatial biodiversity of anammox coupling with denitrification granular sludge under different feeding strategies - Cong Li; Rui Du; Qingtao Liu; Jiarui Fan; Yongzhen Peng (Chemical Engineering Journal, 2024)

Novel insights into mass transfer-controlled radical-mediated co-pyrolysis of lignin with typical plastics - Yuyang Fan; Chao Liu; Zhengxue Zhang; Jia Ouyang; Fuli Deng; Ruixue Zhao; Huiyan Zhang; Rui Xiao (Chemical Engineering Journal, 2024)

1,4-Dioxane intervention enables simultaneous valorization of biomass-based C5 and C6 sugars to furfural over Hβ zeolite - Yujia He; Rui Zhang; Weipeng Song; Huai Liu; Junhua Zhang; Wenlong Jia; Lincai Peng (Chemical Engineering Journal, 2024)

Square-wave alternating voltage driving promotes nanowire-assisted electroporation inactivation and fouling resistance of pathogenic bacteria for water disinfection - Ying-Wen Lu; Yang Wang; Yi-Rui Liu; Hai Liu (Chemical Engineering Journal, 2024)

Ultra-stretchable, sensitive and breathable electronic skin based on TPU electrospinning fibrous membrane with microcrack structure for human motion monitoring and self-powered application - Yu Tian; Mengjie Huang; Yalong Wang; Yanjun Zheng; Rui Yin; Hu Liu; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2024)

Strong enhancement on electron transfer pathway of peroxymonosulfate activation for rapid organic pollutant degradation in wastewater by iron encapsulated into nitrogen-doped carbon: Iron-cores as electron supply stations - Taigang Ma; Hejun Ren; Meijun Liu; Jinhao Duan; Zhonghui Han; Rui Zhou (Chemical Engineering Journal, 2024)

Urea-boosted gas-exfoliation synthesis of lignin-derived porous carbon for zinc ion hybrid supercapacitors - Beichen Xue; Chaozhen Liu; Xiaofeng Wang; Yi Feng; Jiahuan Xu; Feng Gong; Rui Xiao (Chemical Engineering Journal, 2024)

RuO2/CeO2 heterostructure anchored on carbon spheres as a bifunctional electrocatalyst for efficient water splitting in acidic media - Yun Wu; Rui Yao; Kaiyang Zhang; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2024)

Fischer-Tropsch synthesis to α-Olefins with low CO2 selectivity on a Co2C catalyst - Yiwen Liu; Chengyang He; Xingmao Jiang; Rui Zhang; Xinying Liu; Diane Hildebrandt; Xiaojun Lu (Chemical Engineering Journal, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Critical review on the pulsed electrochemical technologies for wastewater treatment: Fundamentals, current trends, and future studies - Fangyuan Liu; Rui Zhou; Chunpeng Zhang; Zhenghong Wu; Hejun Ren; How Yong Ng (Chemical Engineering Journal, 2024)

One pot synthesis of hydrophobic nanochitin aerogel via tert-butyl alcohol/water binary solvents as antibacterial and renewable oil superabsorbent - Liang Liu; Xinxia Li; Rui Zhou; Yimin Fan (Carbohydrate Polymers, 2024)

Thermo-hydro-mechanical coupled model of unsaturated frozen soil considering frost heave and thaw settlement - Qianqian Liu; Guoqing Cai; Chenxin Zhou; Rui Yang; Jian Li (Cold Regions Science and Technology, 2024)

Influence of talking behavior of infected patients and the associated exposure risk in a ventilated negative-pressure ward - Zhijian Liu; Zhe Han; Lina Hu; Chenxing Hu; Rui Rong (Building and Environment, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Astragaloside IV Inhibits Rotenone-Induced α-syn Presentation and the CD4 T-Cell Immune Response - Mengdi Wang; Fengjiao Sun; Xiaofeng Han; Nan Wang; Yalan liu; Jinfeng Cai; Shanshan Tong; Rui Wang; Hongcai Wang (Molecular Neurobiology, 2024)

Large DNA fragment knock-in and sequential gene editing in Plasmodium falciparum: a preliminary study using suicide-rescue-based CRISPR/Cas9 system - Junnan Lu; Ying Tong; Rui Dong; Yijun Yang; Wen Hu; Minghong Zhang; Quan Liu; Siting Zhao; John H. Adams; Li Qin; Xiaoping Chen (Molecular and Cellular Biochemistry, 2024)

Integrative transcriptomic and metabolomic analyses reveal the phenylpropanoid and flavonoid biosynthesis of Prunus mume - Rui Wu; Chengcheng Qian; Yatian Yang; Yi Liu; Liang Xu; Wei Zhang; Jinmei Ou (Journal of Plant Research, 2024)

Sympatric munias in tropical areas segregate spatially through different nest site selections to achieve coexistence - Chen-Wei Guo; Li-Li Li; Chen-Yang Liu; Ru-Chuan He; Rui-Chang Quan (Acta Oecologica, 2024)

Imperfect but effective crypsis and flower-visiting strategy in a crab spider - Zichang Li; Long Yu; Guocheng Yu; Rui Zhong; Yao Zhao; Jie Liu; Yu Peng (Behavioral Ecology and Sociobiology, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Climate warming could free cold‐adapted trees from C‐conservative allocation strategy of storage over growth - Quan Zhou; Hang Shi; Rui He; Haikun Liu; Wenting Zhu; Shengjun Wu; Quanfa Zhang; Haishan Dang (Global Change Biology, 2024)
Carbon allocation has been fundamental for long‐lived trees to survive cold stress at their upper elevation range limit. Although carbon allocation between non‐structural carbohydrate (NSC) storage and structural growth is well‐documented, it still remains unclear how ongoing climate warming influences these processes, particularly whether these two processes will shift in parallel or respond divergently to warming. Using a combination of an in situ downward‐transplant warming experiment and an ex situ chamber warming treatment, we investigated how subalpine fir trees at their upper elevation limit coordinated carbon allocation priority among different sinks (e.g., NSC storage and structural growth) at whole‐tree level in response to elevated temperature. We found that transplanted individuals from the upper elevation limit to lower elevations generally induced an increase in specific leaf area, but there was no detected evidence of warming effect on leaf‐level saturated photosynthetic rates. Additionally, our results challenged the expectation that climate warming will accelerate structural carbon accumulation while maintaining NSC constant. Instead, individuals favored allocating available carbon to NSC storage over structural growth after 1 year of warming, despite the amplification in total biomass encouraged by both in situ and ex situ experimental warming. Unexpectedly, continued warming drove a regime shift in carbon allocation priority, which was manifested in the increase of NSC storage in synchrony to structural growth enhancement. These findings imply that climate warming would release trees at their cold edge from C‐conservative allocation strategy of storage over structural growth. Thus, understanding the strategical regulation of the carbon allocation priority and the distinctive function of carbon sink components is of great implication for predicting tree fate in the future climate warming.